Constraining the stable iron isotopic signature of easily reducible iron: the role of leaching time and extractant type - Berenice Ebner; Susann Henkel; Katja Laufer-Meiser; Anette Meixner; Simone A. Kasemann; Male Köster; Sabine Kasten (Chemical Geology, 2026)

Understanding ecosystem responses to recurrent marine heatwaves - Emily Lester; Stanley Mastrantonis; Sharyn M. Hickey; Anna Lafratta; Jessica A. Benthuysen; Eben Afrifa-Yamoah; Arani Chandrapavan; Martial Depczynski; Richard D. Evans; David V. Fairclough; Christopher J. Fulton; Marthe Monique Gagnon; et al. (Biological Conservation, 2026)

Wuthuga (dugong) population status in Gathaagudu (Shark Bay) sea country - Holly Raudino; Amanda Hodgson; Chris Cleguer; Kym Reeve; Molly Moustaka; Osmar Luiz; Simone Strydom; Kathy Murray; Neilisha Oakley; Tariq McDonald; Abby Leyendekkers; Jay Hayes; et al. (Frontiers in Marine Science, 2026)
Introduction Monitoring trends in wildlife populations and their response to pressures is integral but challenging for conservation managers. Wuthuga (dugongs (Dugong dugon)) are increasingly vulnerable as extreme climatic events, such as marine heatwaves and flooding, intensify with a warming climate and increasingly impact the seagrass they are dependent upon. Methods This study estimated wuthuga abundance using two methodologies: conventional observer aerial surveys, as part of a time-series of surveys, alongside aerial imagery, in Gathaagudu (Shark Bay), Western Australia in 2023. We compare the contemporary abundance estimates with long term monitoring data (1989 – 2018) to identify temporal trends in abundance and distribution. Results Over time the observer-derived estimates of wuthuga in Gathaaguda has ranged from the highest estimate in 1999 of 13929 (± SE 1652) to the lowest in 2023 of 8688 (± SE 1119). The wuthuga population has remained stable over time, with no statistical difference discernable when density is modelled. Methods were compared for the area of highest wuthuga density in 2023 (survey block 4), the observer-derived wuthuga abundance estimate was 4551 (± SE 926) and the image-derived estimate 5748 (± SE 1765). The abundance estimates yielded from both methodologies were not statistically different. For both approaches, abundance estimates were modelled using standard approaches to account for perception and availability bias. Of all wuthuga sighted in Gathaagudu in 2023, ~9.6% were calves, which is within the range of calf proportions found in past surveys. Discussion Due to wuthuga reproductive biology, the proportion of calves observed during aerial surveys may be a useful secondary indicator of population condition and seagrass availability preceding the survey. The proportion of calves observed in 2023 is an encouraging indicator of population condition. The relative stability and size of the Gathaagudu wuthuga population highlights its global importance to the persistence of the species.

Revealing the presence and genetic identification of the rare and critically endangered deep-sea Sandy skate (Leucoraja circularis) in the Adriatic Sea - Andrej A. Gajić; Simone Di Crescenzo; Chiara Pani; Rita Cannas; Emina Karalić (Regional Studies in Marine Science, 2026)

Effects of personality traits and context congruency on participant engagement in traditional central location tests and congruent versus incongruent digital immersive environments during affective product testing - Annu Mehta; Caroline Giezenaar; A. Jonathan R. Godfrey; Rebekah E. Orr; Simone Poggesi; Meika Foster; Joanne Hort (Food Quality and Preference, 2026)

Correction: [FeFe] hydrogenases with modified azadithiolate bridgeheads serve as unidirectional hydrogen oxidation catalysts - Manon T. Lachmann; James A. Birrell; Simone Morra; Patricia Rodríguez-Maciá (JBIC Journal of Biological Inorganic Chemistry, 2026)

Enhancing satellite chlorophyll estimates using in situ environmental data in the freshwater-influenced Canadian Arctic Archipelago - Frances Simone Crable; Sabine Marty; Kai Sørensen; Pierre Franqois Jaccard; Verena Meraldi; Miquel A. Gonzalez-Meler; Andrew L. King (Frontiers in Marine Science, 2026)
Estimating chlorophyll-a (Chl-a) concentrations from satellite ocean color data remains challenging in the Arctic, where freshwater inputs, colored dissolved organic matter (CDOM), suspended particles, and low sun elevation alter optical properties and influence blue–green reflectance. Here, we combine satellite and in situ observations to examine how freshwater-driven optical variability shapes satellite-derived Chl-a across the Canadian Arctic Archipelago (CAA). Continuous underway observations were collected by a FerryBox system aboard the MS Roald Amundsen during August–September 2022 and matched with MODIS-OC3M Level-3 Chl-a (4 km, ± 2 days, 0.1° bins; n = 758). Satellite-derived Chl-a showed large differences relative to in situ observations, with a mean positive bias of 0.69 log 10 units and a root-mean-square error of 0.73 log 10 units, corresponding to an approximate 4.9-fold difference. These differences were strongly structured by environmental gradients, with the largest discrepancies occurring in low-salinity, CDOM-rich waters influenced by the Mackenzie River and decreasing eastward toward clearer, marine-dominated regions of Lancaster Sound. Previously-developed Arctic-tuned algorithms were applied to examine how regional models represent these gradients with the CAA. These approaches reduced overall bias and also resulted in substantial spatial variability linked to freshwater and optical gradients. To further account for these nonlinear environmental effects, a generalized additive model (GAM) incorporating salinity, CDOM, and temperature was applied, resulting in closer agreement between satellite-derived and in situ Chl-a, particularly in the Kitikmeot Sea. These findings demonstrate that freshwater-driven optical variability is a primary control on the calculation of satellite-derived Chl-a in Arctic shelf systems and that integrating environmental predictors into observational frameworks improves the interpretation of ocean color data in optically complex regions.

Multigenerational exposure to per- and polyfluoroalkyl substances (PFAS) negatively impacts the reproductive health of male mice - Leah Gillespie; Jacinta H. Martin; Amanda L. Anderson; Natalie A. Trigg; John E. Schjenken; Shannon P. Smyth; Ilana R. Bernstein; Simone J. Stanger; Logan McElhone; Colin C. Conine; Fay Waldrip; Erin J. Campbell; et al. (Environmental Research, 2026)

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Thiazolidinedione-triazole hybrids: design, synthesis, and biological evaluation as dual inhibitors of α-amylase and aldose reductase with antioxidant activity for antidiabetic therapy - Eman E. Nasr; Mohamed R. Elnagar; Nahed Nasser Eid El-Sayed; Marwa I Serag; Mostafa M. Elbadawi; Adel S. El-Azab; Simone Brogi; Hazem A. Ghabbour; Abdelrahman Hamdi; Alaa A.- M. Abdel-Aziz (Molecular Diversity, 2026)

Marine conservation: linking taxonomy, Red Listing, and public engagement - Torben Riehl; Monika Böhm; Simone N. Brandão; Angelika Brandt; Chong Chen; Gregory D. Edgecombe; Hosea J. ‶Ze″ Frank; Austin J. Gallagher; Rebecca Goldburg; Pat Hutchings; Fabrizio M. Machado; Volker Mosbrugger; et al. (Trends in Ecology & Evolution, 2026)

A dataset of plant communities invaded by Acacia sp. pl. and Robinia pseudoacacia in Italy - Eugenia Siccardi; Alice Misuri; Alicia Teresa Rosario Acosta; Claudia Angiolini; Dario Azzaro; Gianluigi Bacchetta; Simonetta Bagella; Elena Barni; Giuseppe Bazan; Maria E. Boi; Gianmaria Bonari; Giuseppe Brundu; et al. (Plant Biosystems, 2026)
The full extent of the ecological threat posed by non-native invasive leguminous N-fixing trees to Italian ecosystems has not been thoroughly documented at the national level. This study, conducted by the Working Group on Alien Species of the Italian Botanical Society, aims to develop a comprehensive dataset that provides information on invaded and non-invaded areas, supporting multi-scale ecological analyses on the impact of black locust ( Robinia pseudoacacia ) and different Acacia sensu lato species across Italy. We conducted paired vegetation surveys across 18 distinct invasion contexts, comparing invaded and non-invaded plant communities. These invasion contexts were selected opportunistically by the participating research groups, based on the availability of well-documented sites where the focal species were already established and exerting ecologically relevant effects. Overall, we conducted 342 vegetation surveys across 10 Italian administrative regions and identified 824 plant species. Our surveys highlighted areas affected by five invasive species, including A. dealbata, A. mearnsii, A. saligna , Vachellia karroo , and R. pseudoacacia . Most of the surveys focused on areas invaded by A. saligna . The plant formations investigated fall under 23 EUNIS habitat codes and 10 Natura 2000 habitats. The most frequently occurring vegetation types under the EUNIS code are temperate and Mediterranean-montane scrub, and the most frequently investigated habitat is priority habitat 2250*: Coastal dunes with Juniperus sp. pl. This dataset provides a robust baseline that can facilitate more detailed assessments of the impacts of these invasive species on native ecosystems.

From dive slates to digital imagery: an evaluation of the effect of coral reef assessment methods on benthic and substrate compositions and an alignment between methods - Tri A. Hadi; Ian R. Tibbetts; Giyanto; Novi S. Adi; Peter J. Mumby; Simone P. Blomberg (Coral Reefs, 2026)
Various underwater survey methods have been used for coral reef assessment and long-term monitoring; however, comparing data across different methods remains challenging and can obscure ecological patterns. This study compared and aligned three commonly used survey methods in Indonesia, including line-intercept transects (LIT) and point-intercept transects (PIT) recorded on dive slates, and underwater photo transects (UPT), to improve data consistency and comparability. Surveys were conducted at 56 sites across four locations between 2013 and 2014. Two Bayesian Dirichlet models were fitted. The first model assessed the relative performance of the methods while accounting for random effects (location and site within location). The results indicated that UPT generally produced higher estimated per cent cover across most benthic and substrate categories; PIT was typically intermediate; and LIT tended to yield lower estimates for most categories, while relatively overestimating hard coral cover compared with UPT. Because of these discrepancies, the second model was developed to convert LIT or PIT data into UPT-equivalent compositions. While the predictive models have limitations, the predictions for most categories were relatively reliable and, in general, statistically indistinguishable from the observed UPT data, especially at the community level. These models can be iteratively refit to improve regional generalisability by adding observations from different sites and locations, or applied to new sites and locations by excluding the random effect at the cost of increased uncertainty. Overall, this approach improves data comparability and consistency, supporting long-term monitoring and conservation efforts by making conventional and modern methods more directly comparable.

Human-induced trait shifts reshape predator–prey interactions - Eamonn I.F. Wooster; Chris J. Jolly; Dale G. Nimmo; Ben J. Ashton; Mauricio Cantor; Martin J. Whiting; R. Keller Kopf; Simone Des Roches; Alexandra J.R. Carthey; Lauren A. Stanton; Euan G. Ritchie; Michael G. Bertram; et al. (Trends in Ecology & Evolution, 2026)

Higher plasma serine levels are associated with favorable values of metabolic health markers among middle-aged and older adults in The Maastricht Study - Thomas Olsen; Amany Elshorbagy; Elena C. Tore; Nasser E. Bastani; Emma Stolt; Gabriëlla A. M. Blokland; Coen D. A. Stehouwer; M. Eline Kooi; Jacobus F. A. Jansen; Simone J. P. M. Eussen; Pol Grootswagers; Helga Refsum; et al. (GeroScience, 2026)

Quinazoline-sulfonamide hybrids as multitarget anticancer agents: inhibition of carbonic anhydrase IX/XII isoforms and VEGFR-2 with in vitro and in silico validation - Mohamed A. Zeidan; Mohammad M. Al-Sanea; Mohamed R. Elnagar; Mohamed M. Tawfik; Hamed W. El-Shafey; Samar S. Tawfik; Simone Brogi; Abdelrahman Hamdi (Molecular Diversity, 2026)

[FeFe] hydrogenases with modified azadithiolate bridgeheads serve as unidirectional hydrogen oxidation catalysts - Manon T. Lachmann; James A. Birrell; Simone Morra; Patricia Rodríguez-Maciá (JBIC Journal of Biological Inorganic Chemistry, 2026)
Semi-synthetic [FeFe] hydrogenases hold exciting potential as tuneable artificial metalloenzymes for efficient hydrogen conversion (H 2 $$\rightleftharpoons$$ 2 H + + 2e − ). This work investigates the role of the bridgehead ligand in the [FeFe] hydrogenase active site through the study of two bridgehead-modified active-site variants (2-oxapropane 1,3-dithiolate, ODT, and propane 1,3-dithiolate, PDT). Replacing the native 2-azapropane 1,3-dithiolate (ADT) bridgehead with ODT or PDT significantly modifies the active site’s electronic structure and disrupts proton-transfer; yet, some catalytic activity remains, suggesting that alternative catalytic pathways may exist. Notably, when adsorbed onto an electrode, the ODT enzymes operate as proficient catalysts for hydrogen oxidation at higher oxidative overpotentials, achieving current densities of up to 1 mA cm − 2 , comparable to those observed for the respective ADT enzyme under the same conditions. Electrochemical analysis reveals similar catalytic behaviour between the ODT and PDT enzymes, suggesting that a proton transfer pathway between the active site and the protein environment still operates, albeit disrupted, in both bridgehead variants under these conditions. Insights into the electronic and catalytic interplay of these modifications could advance the optimisation of semi-synthetic [FeFe] hydrogenases and design of new bioinspired catalysts. Graphical abstract

Where is natural capital being used in policy-making? Results from an international review - Simone Martino; Ishaan Patil; Stanislav Martinat; Jose Antonio Ballesteros-Figueroa; Kerry A. Waylen (Ecosystem Services, 2026)

Perspective on yeast-3-hybrid assays for target identification of bioactive natural products - Jonas A. Stehlin; Claudia Ascher; Simone Moser (Phytochemistry Reviews, 2026)
While an immense number of natural products have been screened for bioactivity using a variety of phenotypic assays, elucidation of their protein targets remains a significant bottleneck limiting further clinical research. Next to conventional pulldown assays and modern developments, such as cellular thermal shift assays (CETSA), yeast three-hybrid (Y3H) has emerged as a powerful yet underutilized tool that provides a low-barrier avenue for target identification of the challenging natural products space. Still, adoption of Y3H in natural products research has been slow in spite of successful target identification of a diverse range of small molecules reported in literature. In this perspective, we present the underlying methodology and its limitations as well as possible future developments and how it may accelerate and complement the target ID of natural compounds. We encourage natural product researchers to increase efforts on target elucidation of their lead compounds and propose Y3H as an approach, which could be integrated into existing workflows. Graphical abstract

N-Acetylcysteine Dose and Treatment Duration in High-Risk Acetaminophen Ingestions Treated Within Eight Hours: A Retrospective Cohort Study - C. James Watson; Michael D. Simpson; Nishita Saraiya; Christopher A. Wilkosz; Michael B. Yu; Michele M. Burns; Mark J. Neavyn; Karen E. Simone; Tania D. Strout (Journal of Medical Toxicology, 2026)
Introduction Toxicologists may use high dose n-acetylcysteine (HD-NAC) for early-treated high-risk acetaminophen ingestions (EHRAI) given concerns over standard NAC (S-NAC) dosing’s efficacy. We utilize the novel, clinically relevant outcome of mean additional 16-hour NAC maintenance infusions (NMI) to evaluate differences in treatment duration for EHRAI patients treated with S-NAC versus HD-NAC. Methods Retrospective multistate poison center study from 1/1/2019-7/4/2024 of patients ≥ 13-years-old who were treated with S-NAC or HD-NAC within eight hours of a high-risk acetaminophen ingestion. The primary outcome was mean additional NMI. Secondary outcomes were NAC infusion duration, hepatotoxicity, coagulopathy, transplant, and death. Sensitivity analyses evaluated for robustness of findings. Results Of 127 included cases, 52.0% (66/127) received HD-NAC. 7.1% (9/127) had anti-peristaltic co-ingestions. HD-NAC cases received more fomepizole (23.1% versus 1.6%; difference 21.1%). Acetaminophen concentrations controlled for time since ingestion were similar (mean acetaminophen ratio for HD-NAC: 2.7, IQR: 2.3, 3.3 versus S-NAC: 2.4, IQR: 2.2, 2.7; difference − 0.3). 26.0% (33/127) received NMI solely for residual detectable serum acetaminophen. There was no difference in mean additional NMI (HD-NAC: 0.53 versus S-NAC: 0.38; p = 0.240). Median NAC infusion durations were equal across groups (21.0; IQR: 21.0, 37.0; difference 0.0) ( p = 0.137). One patient per group developed hepatotoxicity; there were no transplants or deaths. Sensitivity analyses yielded similar results. Conclusions We found no difference in mean NMI for EHRAI based on NAC dose. These findings support additional NMI as an objective, common, clinically relevant outcome for acetaminophen toxicity research.

Non-native mollusc species in Brazil: a first national inventory and distributional overview - Fabrizio Marcondes Machado; Rodrigo B. Salvador; Igor C. Miyahira; Luiz Ricardo Lopes de Simone; Tarcilla C. de Lima; Mariana Osório Côrtes; Julia D. Sigwart; Angie Patiño Montoya; Vanessa S. Amaral; Paula Spotorno; Marcel Sabino Miranda; Augusto L. Ferreira Júnior; et al. (Biological Invasions, 2026)

Distribution, scale, and drivers of mass mortality events in Europe's freshwater bivalves - Daniel A. Cossey; Maria Urbańska; Ronaldo Sousa; Juergen Geist; Anna Maria Labecka; Şebnem Atasaral; Maciej Bonk; Liliya Bylyna; Frank P. L. Collas; Daniel Daill; Andreas H. Dobler; Noé Ferreira‐Rodríguez; et al. (Conservation Biology, 2026)
Mass mortality events (MMEs) are decimating populations and compromising key ecosystem functions around the globe. One taxon particularly vulnerable to MMEs is freshwater bivalve mollusks. This group has important ecosystem engineering capacities and includes highly threatened and highly invasive taxa. Thus, MMEs of freshwater bivalves have important implications for conservation and ecosystems. Despite this, little is known about the magnitude, frequency, duration, distribution, and causes of freshwater bivalve MMEs. Using a questionnaire, we compiled data from 239 reports describing freshwater bivalve MMEs across 22 European countries since 1960. With these data, we analyzed trends in MME timing, location, and magnitude; identified the species affected; and evaluated the suggested causes (including reporter certainty). We found that the frequency of reports of MMEs increased each year, MMEs affected a broad range of species, clear geographical patterns linking certain causes to specific locations were lacking, factors related to drying and habitat destruction predominated suggested causes, and considerable uncertainty surrounded the causes of many MMEs, particularly those associated with potential pollutants and disease agents. Based on our findings, we recommend the standardization of many aspects of MME research (e.g., reporting and recovery assessment protocols), increased surveying for MMEs, further investigation into the causes of MMEs, especially those with significant uncertainty, and immediate actions to improve waterbody management, mitigate the effects of high temperatures, and further protect freshwater bivalves through the development and implementation of appropriate management actions and legislation.

The role of modifiable risk factors on the cerebral myelin content and cognition: findings from The Maastricht Study - Gerhard S. Drenthen; Walter H. Backes; Sebastian Köhler; Kay Deckers; Miranda T. Schram; Simone J. P. M. Eussen; Willemijn J. Jansen; Jacobus F. A. Jansen (GeroScience, 2026)
Lifestyle-related factors may affect cognition and increase the risk of developing dementia. However, the neurobiological mechanisms underlying the effect of lifestyle-related factors on the brain are not yet fully understood. Myelin, a vital element of brain health, has previously been shown to be involved in dementia-related cognitive decline. However, whether it plays a role in the relation between lifestyle-related factors and cognitive performance has not been studied. The cerebral myelin content of 4653 participants (51% female, aged 59 ± 9 years) from The Maastricht Study was estimated using the T1w/FLAIR-ratio, and lifestyle-related factors were summarized using the LIBRA-score. Multivariable linear regression models, corrected for the effects of age, sex and education, were used to investigate whether lifestyle-related factors are associated with myelin. Moreover, whether myelin can partly explain the relationship between lifestyle-related factors and cognition was explored using a mediation analysis across three cognitive domains (memory, executive functioning and processing speed). An unhealthy lifestyle (i.e. higher LIBRA score) is significantly associated to a lower cerebral myelin content ( β = −0.24, 95% CI [−0.26 −0.22], and p < 0.001). Furthermore, lower cerebral myelin content associates to worse cognitive performance ( β = 0.14, 95% CI [0.11 0.17], and p < 0.001). Moreover, myelin has a partially mediating effect of 15%, indicating that it partly explains the relation between lifestyle-related factors and cognition. These results show that myelin content might help explain the mechanisms through which lifestyle-related factors influence cognition, potentially allowing for specific and early lifestyle interventions aimed at preventing or delaying cognitive decline and dementia. Graphical abstract

Dendropsophin 1, an antimicrobial peptide from skin secretion of the tree frog Dendropsophus columbianus, exhibits tissue repair potential - Isabella S. Cassimiro; Bruno A. Ferreira; Simone R. Deconte; Taís C. Lima; Francyelle B.R. Moura; Mariana S. Castro; Fernanda A. Araújo (Toxicon, 2026)

Two-phase leakage detection strategy supported by district metering areas - G. Messa; G. Acconciaioco; S. Ripani; L. Bozzelli; A. Simone; O. Giustolisi (Journal of Water Process Engineering, 2026)

Context matters: How congruency of digital immersive environment and meal context affect consumer evaluations of plant-based products at two different levels of liking - Rebekah Orr; Caroline Giezenaar; A. Jonathan. R. Godfrey; Simone Poggesi; Joanne Hort (Food Quality and Preference, 2026)

CO2 fluxing and carbon assimilation by arc melts during magma–limestone interaction - Frances M. Deegan; Manfredo Capriolo; Valentin R. Troll; Franz A. Weis; Sara Callegaro; Simone Colucci; Carmela Freda; Valeria Misiti; László E. Aradi; Henrik Skogby; Herlan Darmawan; Harri Geiger (Chemical Geology, 2026)

Ecotoxicological effects of drilling cuttings waste from oil wells: sensitivity of soil invertebrates and plants - Dara C. M. V. P. da Cruz; Higor E. F. Lorin; Fabrielle P. dos Reis; Cibele A. de Costa; Simone B. da Fontoura; Heraldo N. de Souza; Everaldo Zonta; Júlia C. Niemeyer (Ecotoxicology, 2026)

Barcoding‐Inferred Biodiversity of Shallow‐Water Indo‐Pacific Demosponges - Dirk Erpenbeck; Adrian Galitz; Michael L. Berumen; Gabriele Büttner; Cécile Debitus; Moritz Dirnberger; Merrick Ekins; Kathryn Hall; Leonard Namuth; Sylvain Petek; Neda Rahnamae; Maggie M. Reddy; et al. (Journal of Biogeography, 2026)
Aim The Indo‐Pacific is the world's largest marine biogeographic region. It is characterised by different degrees of connectivity among its subregions and harbours the majority of demosponge species currently known to science. Comparisons between regional sponge faunas have been undertaken in the past, mostly based on morphological species identification. The Sponge Barcoding Project, in tandem with regional DNA taxonomy campaigns, provides one of the largest DNA‐based taxonomic data collections from sponges of the Indo‐Pacific. Here, we utilise the barcoding data in the most extensive molecular biodiversity study of sponges to date, which reveals patterns of shallow‐water demosponge faunal connectivity, endemism and distribution in the Indo‐Pacific with a level of resolution unavailable in prior morphology‐based studies. Location Demosponge specimens in this study cover 13 marine provinces (MPs) of the Indo‐Pacific. Methods We classified demosponge barcodes from 1910 sponge samples into 701 molecular operational taxonomic units (MOTUs) using 28S rRNA. MOTU composition of the MPs was compared based on Jaccard and Sørenson dissimilarities and other biodiversity indices. Results Our data corroborated high endemism in MPs (up to 84.1% endemic MOTUs). Faunal overlaps are between the Red Sea and the Gulf, which displayed small connectivity with other MPs in the Western Indian Ocean. The Western Indian Ocean is a strong faunistic boundary to the Central Indo‐Pacific, to which the Polynesian sponge faunas were comparatively isolated as well. Main Conclusions Our data corroborate case studies on sponges that generally reject the presence of cosmopolitan or otherwise widespread sponge species, instead revealing high levels of regional endemism. This is consistent with similar observations and hypotheses in other marine invertebrates, and highlights the need for close regional monitoring to identify biodiversity changes. Connectivity among Indo‐Pacific MPs differs for demosponges in many aspects from that of other marine taxa, hypothetically due to their shorter pelagic larval phase.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Mycorrhizal fungal associations of the fringed orchids (Platanthera) in the US, inter- and intra-species variation - Melissa K. McCormick; Ida Hartvig; Simone A. Evans; Julianne McGuinness; Stephanie Lyon; Zöe Knapp; Jason Ligon; Lauren Eserman; Emily Coffey; Dennis F. Whigham (Biodiversity and Conservation, 2026)
Understanding which orchid mycorrhizal fungi (OMF) are needed to support orchid growth is critical for their conservation. We used DNA sequencing and network analysis of OMF collections from the North American Orchid Conservation Center, along with published sequences, to compare the OMF associated with 28 species and 4 natural hybrids in the genus Platanthera . We found that relatedness of orchid species was generally a poor predictor of OMF associates. However, species in sections Fimbriata and Blephariglottis that co-occurred and formed natural hybrids associated with multiple fungi that were completely shared among co-occurring species. Differences in mycorrhizal associates within species mapped onto orchid genetic differences that distinguished geographic regions (mountains vs. coast vs. inland, not strictly geographic distance). Orchids that were specialized or moderately specialized in their OMF associations required relatively few samples to describe the bulk of their associated OMF, while generalized orchids required considerably more samples to describe their associated OMF. These results provide insight into species differences in mycorrhizal associations and can be used to guide management actions, as well as providing a foundation for future research.

Conservation genomics of the fringed orchids (Platanthera) in the Eastern US – species boundaries and genetic structure across landscapes - Ida Hartvig; Jason Ligon; Maria Sophie Bünner; Simone A. Evans; Lauren Eserman; Dennis F. Whigham; Emily Coffey; Melissa K. McCormick (Biodiversity and Conservation, 2026)
Taxonomic ambiguity, frequent hybridization, and limited resolution of species boundaries continue to constrain orchid conservation strategies. In this study, we employed population genomic analyses across nine taxa of Platanthera native to eastern North America to critically reassess species boundaries and evaluate spatial patterns of genetic structure. Utilizing 3RADseq-derived SNP datasets, we delineated species limits, identified cryptic hybridization, and resolved regional genetic differentiation within and among taxa in two focal species complexes: the orange-fringed complex ( Platanthera sect. Blephariglotti s) and the purple-fringed complex (subgen. Fimbriata ). Our findings revealed extensive hybridization and introgression in sympatric populations in the orange fringed complex with asymmetrical gene flow and geographically structured genetic signatures indicating historical and ongoing hybrid zones. In contrast, the range-restricted taxa P. integrilabia exhibited genetic homogeneity, suggesting limited gene flow and underscoring their conservation priority. Within the purple-fringed complex, the identified genomic clusters indicate a complex relationship between genotypes and morpho-types and a potential legacy from post-glacial recolonization, combined with ongoing hybridization. Our results challenge several current species definitions and emphasize the importance of integrating genomic data in defining Evolutionarily Significant Units (ESUs). These insights inform revised conservation priorities for eastern North American Platanthera , highlighting the need to protect both genetically distinct lineages and dynamic hybrid zones as reservoirs of evolutionary potential.

Replacing Conventional Fertilization with Organomineral Fertilizer in ‘Hass’ Avocado Trees Improves Chlorophyll Indices and Fruit Size: A Bootstrap Simulation Approach - Marllon F. S. dos Santos; Rodrigo J. Milan; Bruna M. Costa; Tatiana E. Cantuarias-Avilés; Idemauro A. R. de Lara; Simone R. da Silva (Applied Fruit Science, 2026)
Modern agriculture faces significant challenges related to the depletion of finite resources used in fertilizer production. In response to this situation, the market has been adapting by developing biofertilizers or organomineral fertilizers, which incorporate an organic fraction into their composition. These fertilizers provide nutrients more gradually, reducing leaching. Studies on this topic are scarce for avocado trees, whose global production has been increasing. For this reason, the present research aimed to compare conventional fertilization with organomineral fertilization in ‘Hass’ avocado trees. A total of 20 plants per treatment were used in a commercial orchard, with treatments providing the same amount of nutrients. Variables related to vegetative growth, gas exchange, and productive data were evaluated. Data analysis was performed using bootstrap simulations, a resampling technique with 10,000 simulations, which enabled the construction of confidence intervals for the variables being assessed, resulting in an experimental optimization. Although no significant differences were detected in overall yield, the organomineral treatment showed increases of up to 10% in chlorophyll levels, 17.69% in fruit weight, and 8.35% and 9.18% in fruit length and diameter, respectively, compared to the conventional treatment. The bootstrap technique proved effective for analyzing this type of experiment, confirming the benefits of replacing conventional fertilization with organomineral fertilization, which provides nutrients more efficiently and sustainably.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Patient Advocate–Trainee Engagement in Oncology Education: Insights from a Short Pilot Survey - Christina A. Simone-Soule; Sara E. Burke; Dema Abul-Enin; Charita Kunta; Adeseye Adekeye; Phuoc Tran; Amy Leader; Adam P. Dicker; Nicole L. Simone (Journal of Cancer Education, 2026)
Patient advocates represent the voice of the patient community and bring a unique perspective to research. We hypothesized that including patient advocates in research training would increase trainees ability to communicate their science, understand the impact of their work and increase their empathy for patients. An IRB-approved survey was administered to assess the impact of patient advocate feedback on trainees who presented their research via posters at our Radiation Oncology Research Symposium. Trainees reported demographics and self-assessed their use of lay language, changes in empathy, understanding the impact of their research, and potential future implications. The binomial proportion test and Fisher’s exact test were used to determine significance. The survey was completed by 80% (28/35) of trainees who participated in the poster session and interacted with patient advocates. Trainees were predominantly younger (60.7% under 30yo) and people of color (60.7%). Almost all trainees (96.4%) were comfortable talking to advocates but only 89.29% were comfortable using lay language. Trainees agreed (75%) that interacting with advocates increased their empathy. Most trainees (71.4%) believed patient advocates helped them understand the significance of their research and 64.3% believed advocates helped them develop new research ideas. Most trainees would like advocates at future poster presentations (85.7%), but did not want them to participate in study design or analysis. Gender and training level did not affect trainees’ ability to communicate in lay language, their empathy for patients, or understanding of their work’s clinical relevance. Including patient advocates in poster sessions may improve trainees ability to present their research in lay language, increase their empathy and understand the clinical impact of their research. Future radiation oncology training should consider including the patient advocate voice to improve the tangible connection between research and real-world impact.

Response to the letter to the editor by Vinderola et al. (2025) Trends in Food Science & Technology 165, 105289 - Simone Guglielmetti; Marie-Eve Boyte; Cathy L. Smith; Arthur C. Ouwehand; George Paraskevakos; Jessica A. Younes (Trends in Food Science & Technology, 2026)

Prioritising domestic locations for marine biosecurity management within a regional vessel network - Cal Faubel; Oliver Floerl; Kyle Hilliam; Simone L Stevenson; Eric A Treml (Biological Conservation, 2025)

The microbiome’s hidden influence: preclinical insights into inflammatory responses in necrotizing enterocolitis - Briana M. Peterson; Ina Rudloff; Nadia S. Deen; Sara K. Di Simone; Ramesh M. Nataraja; Gergely Toldi; Maurizio Pacilli; Steven P. Garrick; Steven X. Cho; Marcel F. Nold; Samuel C. Forster; Claudia A. Nold-Petry (Seminars in Immunopathology, 2025)
Necrotizing enterocolitis (NEC) is the most common surgical emergency in preterm infants; nonetheless, besides supportive measures, no treatment is available. NEC significantly increases length of hospitalization of preterm infants, causes severe morbidity and up to 70% mortality. Despite limited understanding of the underlying mechanisms, prematurity, dysbiosis and an underdeveloped immune system are known to increase the risks of developing NEC. The low weight of preterm infants (often < 2000 g) and unpredictable progression of NEC hinder clinical research; hence, most of our mechanistic understanding of NEC pathophysiology has arisen from animal models. Recent advances in bacterial genomic analyses highlighted the intestinal microbiome’s key role in NEC, strengthening the concept that this disease results from an interaction between the patient’s developing immune system and their microbiome. This notion is supported by the moderate effect of probiotics in preventing NEC. Here, we review the current knowledge on how the immune system interacts with the intestinal microbiome in early life, including in relation to NEC, describe the current evidence from cohort studies, clinical trials, in vivo and in vitro models used to study NEC, and methods to modulate the immune system and microbiome in early life. Knowledge on the early-life microbiome and immune system in health and diseases, including NEC, can be harnessed to develop novel and urgently needed immunomodulatory and microbiota-based therapeutics.

DUBR non-coding RNA regulates gene expression by affecting AP-1 enhancer accessibility - Simone D. Hall; Khoa Tran; Jonathan Zhu; Tong Su; Colleen A. McHugh (Functional & Integrative Genomics, 2025)
Non-coding RNAs (ncRNAs) are finely tuned cellular regulators important for human cell growth and cancer progression. DUBR ( Dppa2 upstream binding RNA, also known as linc00883) is a nuclear ncRNA first discovered in mice for its role in regulating myoblast differentiation through interactions with chromatin and DNA methyltransferases. High expression levels of this ncRNA are predictive of poor patient outcome in colon adenocarcinoma, suggesting that DUBR may be involved in controlling cancer growth. To elucidate its function, we used RAP-MS and RNA immunoprecipitation techniques which revealed its interaction with epigenetic maintenance proteins in the human colon cancer cell line HCT116. Further, ATAC-seq and RNA-seq were used to address its function in regulating the epigenome and transcriptome of HCT116 cells. Here we report that DUBR is a regulator of human colon cancer cell line HCT116 survival. Additionally, we find that the ncRNA DUBR regulates AP-1 transcription factor binding site accessibility at enhancers of genes involved in differentiation and morphogenesis through interactions with epigenetic proteins such as NuRD complex members HDAC1 and CHD4.

Nano-coating with silicon dioxide to reduce the occurrence of bacterial contamination in a pig abattoir drinking system - Celine Buder; Nina Langkabel; Alina Kirse; Mirjam Kalusa; Simone A. Fietz; Diana Meemken (Folia Microbiologica, 2025)
A recently discovered source for infection of slaughter pigs, and thus entry for bacteria into the food chain, is the installed drinking equipment in lairage pens of pig abattoirs. To mitigate this, nano-coating of stainless steel, currently used in human medicine fields as well as in other parts of the food chain, appears as promising technology. In this study, silicon dioxide nano-coating was applied to six drinkers and installed for one and three months in a lairage of a pig abattoir, while results were compared with those of drinkers that had not been nano-coated. Laboratory examination of eight sample types related to the drinkers was conducted for total aerobic plate count, Enterobacteriaceae count, Pseudomonas spp. count, Salmonella presence, pathogenic Yersinia enterocolitica presence, Listeria monocytogenes presence and methicillin-resistant Staphylococcus aureus presence. The nipple drinker, which the pigs take into their mouth for drinking, was then examined using scanning electron microscopy and elemental analysis. The nano-coating did not produce statistically significant reductions in the loads or presence of these bacteria compared to the same but uncoated drinking equipment used under the same conditions. Further studies should focus on the implementation of combined methods, such as nano-coating and sanitary treatment, as well as modifications to the coating itself, to produce meaningful reductions of the bacterial loads on/in abattoir lairage drinking equipment.

Limosilactobacillus reuteri UN41 improves the survival rate and exhibits hepatoprotective effects in a murine model of Salmonella infection - Melina A. Cordeiro; Vivian C. Miranda; Katharina O. Barros; Paulo H. F. Carmo; Luísa M. Trindade; Simone O. A. Fernandes; Valbert N. Cardoso; Rosa M. E. Arantes; Mayra F. Ricci; Silvia B. Moura; Flaviano S. Martins (Brazilian Journal of Microbiology, 2025)

Climate (in)action? The relationship between CEO early-life experiences and corporate climate policies - Wiebke Szymczak; Simone A. Wagner; Timo Busch (Ecological Economics, 2025)

Phyllobilins derived from chlorophyll degradation are overlooked, bioactive phytochemicals in plant-based food - Christian Elvert; Fabian Hammerle; Christian Doppler; David Bernhard; Simone Moser; Cornelia A. Karg (Phytochemistry Letters, 2025)

Iron, manganese, and copper complexes protect saccharomyces cerevisiae from methyl methanesulfonate-induced genotoxicity and oxidative stress - Larissa M. M. Mattos; Davi A. Andrade; Alan N. S. Alves; Victória T. Ferreira; Simone S. C. Oliveira; Bruna B. Segat; André L. S. Santos; Adolfo Horn; Christiane Fernandes; Marcos D. Pereira (World Journal of Microbiology and Biotechnology, 2025)

Commercial and regulatory frameworks for postbiotics: an industry-oriented scientific perspective for non-viable microbial ingredients conferring beneficial physiological effects - Simone Guglielmetti; Marie-Eve Boyte; Cathy L. Smith; Arthur C. Ouwehand; George Paraskevakos; Jessica A. Younes (Trends in Food Science & Technology, 2025)

Ghost plumes hidden beneath Earth’s continents - Simone Pilia; Giampiero Iaffaldano; D. Rhodri Davies; Mohammad Ismaiel; Paolo A. Sossi; Scott Whattam; Dapeng Zhao; Hao Hu (Earth and Planetary Science Letters, 2025)

Adventively established Leptopilina japonica: a new opportunity for augmentative biocontrol of Drosophila suzukii - Marco Valerio Rossi-Stacconi; Paul K. Abram; Gianfranco Anfora; Elizabeth Beers; Antonio Biondi; Nicolas Borowiec; Juli Carrillo; Jana Collatz; Asia Colmagro; Benjamin Crossman Johnson; Kent Daane; Giovanni Dal Zotto; et al. (Journal of Pest Science, 2025)
The invasive spotted-wing drosophila, Drosophila suzukii , has emerged as a significant global pest over the past decade, threatening fruit production worldwide. The parasitoid Leptopilina japonica , presumed native to East Asia, has established adventive populations in Europe and North America and is increasingly recognized for its ability to parasitize substantial proportions of D. suzukii larvae across diverse habitats. Here, we provide a broad review of the biology, establishment, distribution, and potential impacts of L. japonica . Using field data from international monitoring programs, we document the seasonal dynamics of plant–host–parasitoid associations and assess evidence for L. japonica ’s impact on D. suzukii and non-target organisms. Findings indicate that L. japonica has successfully established in several areas where D. suzukii is present in Europe and North America, showing promise as a biological control agent to support sustainable pest management. Current data suggest it provides some suppression of D. suzukii populations with minimal non-target effects. However, long-term studies are necessary to clarify its food web interactions and efficacy as a biological control agent. In areas where L. japonica has been established, we propose its use in augmentative biological control programs to enhance its impacts in specific agricultural settings. Case-specific evaluations of its ecological effects and role in integrated pest management, supported by continued monitoring, are essential. The case of L. japonica illustrates the need for clear, research-informed policies to guide the use of adventively established non-indigenous natural enemies in pest management.

Recent evidence on the effectiveness of European protected areas for species conservation in the face of climate change - Leah A. Kelly; Fiona Burns; Simone Mordue; Simon R. Wotton; Meriel Harrison; Kate Jennings; Richard D. Gregory (Biodiversity and Conservation, 2025)

Diversity in Resource Use Strategies Promotes Productivity in Young Planted Tree Species Mixtures - Joel Jensen; Haben Blondeel; Joannès Guillemot; Florian Schnabel; Hernán Serrano‐León; Harald Auge; Lander Baeten; Nadia Barsoum; Jürgen Bauhus; Christel Baum; Raimundo Bermudez; Friderike Beyer; et al. (Global Change Biology, 2025)
Mixed‐species forestry is a promising approach to enhance productivity, increase carbon sequestration, and mitigate climate change. Diverse forests, composed of species with varying structures and functional trait profiles, may have higher functional and structural diversity, which are attributes relevant to a number of mechanisms that can influence productivity. However, it remains unclear whether the context‐dependent roles of functional identity, functional diversity, and structural diversity can lead to a generalized understanding of tree diversity effects on stand productivity. To address these gaps, we analyzed growth data from 83,600 trees from 89 species across 21 young tree diversity experiments spanning five continents and three biomes. Results revealed a positive saturating relationship between tree species richness and stand productivity, with reduced variability in growth rates among more diverse stands. Structural equation modeling demonstrated that functional diversity mediated the positive effects of species richness on productivity. We additionally report a negative relationship between structural diversity and productivity, which decreased with increasing species richness. When partitioning net diversity effects, we found that selection effects played a dominant role in driving the overall increase in productivity in these predominantly young stands, contributing 77% of the net diversity effect. Selection effects increased with diversity in wood density. Furthermore, acquisitive species with lower wood density and higher leaf nitrogen content had higher productivity in more diverse stands, while conservative species showed neutral to slightly negative responses to species mixing. Together, these results suggest that combining acquisitive with conservative species allows acquisitive species to drive positive selection effects while conservative species tolerate competition. Thus, contrasting resource‐use strategies can enhance productivity to optimize mixed‐species forestry, with potential for both ecological and economic benefits.

Borealisation of Plant Communities in the Arctic Is Driven by Boreal‐Tundra Species - Mariana García Criado; Isabel C. Barrio; James D. M. Speed; Anne D. Bjorkman; Sarah C. Elmendorf; Isla H. Myers‐Smith; Rien Aerts; Juha M. Alatalo; Katlyn R. Betway‐May; Robert G. Björk; Mats P. Björkman; Daan Blok; et al. (Ecology Letters, 2025)
Following rapid climate change, tundra plant communities are experiencing extensive compositional shifts. A conservation concern is the potential encroachment of boreal species into the tundra (‘borealisation’). Tundra borealisation has been sporadically reported, but not systematically quantified. Here, we synthesised data from across 32 study areas, spanning 1137 plots and 287 vascular plant species, resurveyed between 1981 and 2023. We (i) quantified tundra borealisation as the colonisation and increase in abundance of Boreal and Boreal‐Tundra species, (ii) assessed biogeographical, climatic and local borealisation drivers and (iii) identified species contributing to borealisation and their associated traits. Half of the plots experienced borealisation, although borealisation rates were not different to random expectation. Borealisation was greater in Eurasia, closer to the treeline, at higher elevations, in warmer and wetter regions, where climate change was limited, and where initial boreal abundance was lower. Boreal coloniser species were generally short‐statured, and more often shrubs and graminoids. Boreal species colonised around three times less frequently than Boreal‐Tundra species. Hence, our findings indicate that tundra borealisation is mainly driven by the spread of already established boreal‐low Arctic tundra species. These plant community composition changes could have cascading impacts on land‐atmosphere interactions, trophic dynamics and Indigenous and local livelihoods.

The ecology of the oxyscape in coastal ecosystems - Marco Fusi; Fabrice Stephenson; Sergio A. Navarrete; Fabian J. Tapia; John L. Largier; Ramona Marasco; Theresa Rueger; Chancey MacDonald; Daniele Daffonchio; Miriam Fernandez; Evie A. Wieters; Jenny Booth; et al. (Trends in Ecology & Evolution, 2025)

Beyond the initial boom: Energy transitions can improve rural development indicators - Simone Felton; David A. Fleming-Muñoz; Tom Measham (Journal of Rural Studies, 2025)

Oral Treatment with Saccharomyces cerevisiae CNCM I-3856 Mitigates the Inflammatory Response Experimentally Induced by Salmonella enterica subsp. enterica Serovar Typhimurium in Mice - Lara L. Campos; Samantha R. M. Oliveira; Maisa N. S. Amaral; Bruno Gallotti; Aline F. Oliveira; Rosa M. E. Arantes; Samantha Ribeiro-Souza; Katia D. Vital; Simone O. A. Fernandes; Valbert N. Cardoso; Jacques R. Nicoli; Flaviano S. Martins (Probiotics and Antimicrobial Proteins, 2025)

Forest Age Rivals Climate to Explain Reproductive Allocation Patterns in Forest Ecosystems Globally - Rachel E. Ward; Huanyuan Zhang‐Zheng; Kate Abernethy; Stephen Adu‐Bredu; Luzmilla Arroyo; Andrew Bailey; Jos Barlow; Erika Berenguer; Liana Chesini‐Rossi; Percival Cho; Cecilia A. L. Dahlsjö; Eder Carvalho das Neves; et al. (Ecology Letters, 2025)
Forest allocation of net primary productivity (NPP) to reproduction (carbon required for flowers, fruits, and seeds) is poorly quantified globally, despite its critical role in forest regeneration and a well‐supported trade‐off with allocation to growth. Here, we present the first global synthesis of a biometric proxy for forest reproductive allocation (RA) across environmental and stand age gradients from a compiled dataset of 824 observations across 393 sites. We find that ecosystem‐scale RA increases ~60% from boreal to tropical forests. Climate shows important non‐linear relationships with RA, but is not the sole predictor. Forest age effects are comparable to climate in magnitude (MAT: ß = 0.24, p = 0.021; old growth forest: ß = 0.22, p p = 0.001; soil N: ß = −0.07, p = 0.001). These results provide strong evidence that ecosystem‐scale RA is mediated by climate, forest age, and soil conditions, and is not a globally fixed fraction of positive NPP as assumed by most vegetation and ecosystem models. Our dataset and findings can be used by modellers to improve predictions of forest regeneration and carbon cycling.

Correction to: Equivalent Biot and Skempton Poroelastic Coefficients for a Fractured Rock Mass from a DFN Approach - Silvia De Simone; Caroline Darcel; Hossein A. Kasani; Diego Mas Ivars; Philippe Davy (Rock Mechanics and Rock Engineering, 2025)

Concurrent invasions of European starlings in Australia and North America reveal population‐specific differentiation in shared genomic regions - Natalie R. Hofmeister; Katarina C. Stuart; Wesley C. Warren; Scott J. Werner; Melissa Bateson; Gregory F. Ball; Katherine L. Buchanan; David W. Burt; Adam P. A. Cardilini; Phillip Cassey; Tim De Meyer; Julia George; et al. (Molecular Ecology, 2025)
A species' success during the invasion of new areas hinges on an interplay between the demographic processes common to invasions and the specific ecological context of the novel environment. Evolutionary genetic studies of invasive species can investigate how genetic bottlenecks and ecological conditions shape genetic variation in invasions, and our study pairs two invasive populations that are hypothesized to be from the same source population to compare how each population evolved during and after introduction. Invasive European starlings ( Sturnus vulgaris ) established populations in both Australia and North America in the 19th century. Here, we compare whole‐genome sequences among native and independently introduced European starling populations to determine how demographic processes interact with rapid evolution to generate similar genetic patterns in these recent and replicated invasions. Demographic models indicate that both invasive populations experienced genetic bottlenecks as expected based on invasion history, and we find that specific genomic regions have differentiated even on this short evolutionary timescale. Despite genetic bottlenecks, we suggest that genetic drift alone cannot explain differentiation in at least two of these regions. The demographic boom intrinsic to many invasions as well as potential inversions may have led to high population‐specific differentiation, although the patterns of genetic variation are also consistent with the hypothesis that this infamous and highly mobile invader adapted to novel selection (e.g., extrinsic factors). We use targeted sampling of replicated invasions to identify and evaluate support for multiple, interacting evolutionary mechanisms that lead to differentiation during the invasion process.

Grape ripening speed slowed down using natural variation - Luigi Falginella; Gabriele Magris; Simone D. Castellarin; Gregory A. Gambetta; Mark A. Matthews; Michele Morgante; Gabriele Di Gaspero (Theoretical and Applied Genetics, 2025)

Conspecific hyperparasitism in two Ornithodoros species (Ixodida: Argasidae) endemic to Brazil, and interspecific hyperparasitism between Amblyomma sculptum and Rhipicephalus microplus (Ixodida: Ixodidae) - Thiago F. Martins; Simone M. Simons; Caio Monteiro; Haile D. F. Chagas; Rafael A. Carvalho; Arthur M. Santana; Darci M. Barros-Battesti; Glauber M. B. de Oliveira; Livio M. Costa-Junior; Marcelo B. Labruna; Hermes R. Luz (Experimental and Applied Acarology, 2025)

Seasonal synchrony between vessel arrivals and larval production may influence the likelihood of biofouling introductions - Simone L. Stevenson; Ian Davidson; Julio Botero; Kay Critchell; Cal Faubel; Kyle Hilliam; Oliver Floerl; Melissa Welsh; Eric A. Treml (Biological Invasions, 2025)
Biofouling of ships and boats is a dominant global transport pathway for marine invasive species. Many biofouling non-indigenous species (NIS) can only be entrained by vessels and subsequently ‘discharged’ during the short-lived but highly mobile larval stage. This means their introduction to new locations is reliant on vessels arriving in suitable habitat while biofouling adults on the hull are spawning. Vessel arrivals and spawning are, however, both transient events. The influence of synchrony between shipping traffic and spawning on introductions of marine NIS is not well understood. Using New Zealand as a case study, we show that seasonality of domestic vessel arrivals is much more prevalent than for international vessel arrivals. Seasonality was identified in 35 of 58 nationwide locations receiving commercial maritime traffic. Seasonal locations most commonly experienced their shipping peaks during spring and summer, while troughs were most common during winter and autumn. This seasonal pattern produces more opportunities for introductions of spring–summer spawners, while potentially limiting introductions of autumn and winter spawners around New Zealand. Our findings indicate the importance of incorporating seasonality into models and risk-assessments of vessel-mediated incursions, and the need for more empirical data on the timing of introduction and entrainment events. There may be an opportunity to optimise surveillance and vector management efforts during periods of peak synchronicity, where the likelihood of incursions is higher.

Kynurenine pathway dysregulation in cognitive impairment and dementia: a systematic review and meta-analysis - Kyonghwan Choe; Lieke Bakker; Daniel L. A. van den Hove; Simone J. P. M. Eussen; Gunter Kenis; Inez H. G. B. Ramakers; Frans R. J. Verhey; Bart P. F. Rutten; Sebastian Köhler (GeroScience, 2025)
The kynurenine pathway (KP) might be involved in pathophysiological processes associated with dementia, but clinical studies reported contradictory results. This systematic review and meta-analysis summarized the available evidence for (i) differences in KP metabolites in patients with cognitive impairment compared to cognitively healthy individuals and (ii) associations between KP metabolites and cognitive functioning. English, full-length articles with prospective, cross-sectional, or case–control study designs, published in Pubmed, Embase, PsychINFO, or the Cochrane Database of Systematic Reviews up to October 2023, were included. Random-effects meta-analyses of standardized mean differences (SMD) were performed. Heterogeneity, meta-regression, small study bias, and study quality assessments were carried out. Of 8797 retrieved studies, 98 were eligible for the systematic review. Meta-analyses comparing Alzheimer’s disease (AD) dementia patients to controls (n = 27 studies) indicated lower CSF levels of tryptophan (SMD = − 0.26 [95% CI − 0.41, − 0.12]), 3-hydroxykynurenine (− 0.21 [− 0.39, − 0.04]), anthranilic acid (− 0.28 [− 0.48, − 0.08]), and quinolinic acid (− 0.38 [− 0.56, − 0.21]) in AD dementia, while CSF levels of kynurenic acid were higher (0.18 [0.01, 0.35]). Blood levels of tryptophan (− 0.39 [− 0.51, − 0.28]), kynurenic acid (− 0.31 [− 0.47, − 0.15]), xanthurenic acid (− 0.34 [− 0.54, − 0.15]), and 3-hydroxyanthranilic acid (− 0.42 [− 0.61, − 0.22]) were lower in AD dementia. For some of these metabolites, similar directions were observed in meta-analyses comparing individuals with mild cognitive impairment with controls, although the number of included studies in these analyses was relatively small (n = 11). Associations with cognitive test scores were inconclusive and generally non-significant. These results suggest that AD dementia is associated with lower blood levels of several KP metabolites. Findings challenge current assumptions of neurotoxic quinolinic acid levels being associated with dementia.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

How Do Synchrony in Survival and Productivity Influence Abundance Synchrony in European Landbirds? - Catriona A. Morrison; Jennifer A. Gill; Claire Buchan; Robert A. Robinson; Juan Arizaga; Oriol Baltà; Emanuel Baltag; Jaroslav Cepák; Pierre‐Yves Henry; Ian Henshaw; Zsolt Karcza; Petteri Lehikoinen; et al. (Ecology Letters, 2025)
Synchronous fluctuations in species' abundance are influenced by synchrony in underlying rates of productivity and survival. However, it remains unclear how rate synchrony varies in space and time, contributes to abundance synchrony, and differs among species. Using long‐term annual count (number of adults captured), adult survival and productivity (number of juveniles captured per adult) data for breeding land‐birds at ringing sites across Europe, we show that synchrony is strongest and largest scale in productivity and weakest and smallest scale in counts. However, counts fluctuate more synchronously with survival than they do with productivity. These patterns hold for species which do not migrate or only migrate within Europe (European‐residents) and those migrating to sub‐Saharan Africa (subSaharan‐migrants), but the periodicity of productivity and survival synchrony is longer in European‐residents than in subSaharan‐migrants. This suggests that survival and productivity synchrony may interact to weaken abundance fluctuations but are influenced by environmental drivers operating over differing timescales in European‐resident and subSaharan‐migrant species.

Early effects of anti-TNFα antibodies in horses with osteoarthritis - G. Perrone; C. Giampaoli; A. Lorenzo Smirnoff; A. Ochoa; R. Pareja; E. De Simone (Journal of Equine Veterinary Science, 2025)

Could Exotic Birds Play a Significant Role in the Emergence of Antibiotic-Resistant Microorganisms? - Gabriel H. S. Britto; Lara R. Gomes; João P. Pimenta; Simone Sommerfeld; Maysa V. C. Silva; Phelipe A. B. M. Peres; Paula F. S. Braga; Letícia R. M. Costa; Isabelle E. Pedrosa; Márcio B. Bandarra; Terezinha Knöbl; Belchiolina B. Fonseca (Current Microbiology, 2025)

Mechanistic aspects of the binding of acid–base ligands to ferric heme proteins - Andresa Messias; Melisa Carllinni Colombo; Juan Cruz Palermo; Jonathan A. Córdova; Giovanna De Simone; Paolo Ascenzi; Darío A. Estrin; Luciana Capece; Sara E. Bari (Biophysical Reviews, 2025)

Sustainable Land Use Enhances Soil Microbial Respiration Responses to Experimental Heat Stress - Rémy Beugnon; Nico Eisenhauer; Alfred Lochner; Margarete J. Blechinger; Paula E. Buhr; Simone Cesarz; Monica A. Farfan; Olga Ferlian; Amanda J. Rompeltien Howard; Yuanyuan Huang; Blanca S. Kuhlmann; Nora Lienicke; et al. (Global Change Biology, 2025)
Soil microbial communities provide numerous ecosystem functions, such as nutrient cycling, decomposition, and carbon storage. However, global change, including land‐use and climate changes, affects soil microbial communities and activity. As extreme weather events (e.g., heatwaves) tend to increase in magnitude and frequency, we investigated the effects of heat stress on the activity (e.g., respiration) of soil microbial communities that had experienced four different long‐term land‐use intensity treatments (ranging from extensive grassland and intensive grassland to organic and conventional croplands) and two climate conditions (ambient vs. predicted future climate). We hypothesized that both intensive land use and future climate conditions would reduce soil microbial respiration (H1) and that experimental heat stress would increase microbial respiration (H2). However, this increase would be less pronounced in soils with a long‐term history of high‐intensity land use and future climate conditions (H3), and soils with a higher fungal‐to‐bacterial ratio would show a more moderate response to warming (H4). Our study showed that soil microbial respiration was reduced under high land‐use intensity (i.e., −43% between extensive grassland and conventional cropland) and future climate conditions (−12% in comparison to the ambient climate). Moreover, heat stress increased overall microbial respiration (+17% per 1°C increase), while increasing land‐use intensity reduced the strength of this response (−25% slope reduction). In addition, increasing soil microbial biomass and fungal‐to‐bacterial ratio under low‐intensity land use (i.e., extensive grassland) enhanced the microbial respiration response to heat stress. These findings show that intensive land use and climate change may compromise the activity of soil microbial communities as well as their respiration under heatwaves. In particular, soil microbial communities under high‐intensity land use and future climate are less able to respond to additional stress, such as heatwaves, potentially threatening the critical ecosystem functions driven by soil microbes and highlighting the benefits of more sustainable agricultural practices.

The Triassic magmatism in southwestern Gondwana: An example of arc batholith construction in a retreating margin - Javiera González; Verónica Oliveros; Friedrich Lucassen; Christian Creixell; Felipe Coloma; Ricardo Velásquez; Laura Hernández; Paulina Vásquez; Simone A. Kasemann (Gondwana Research, 2025)

Current state of plant conservation translocations across Europe: motivations, challenges and outcomes - Sandrine Godefroid; Sam Lacquaye; Andreas Ensslin; Sarah Dalrymple; Thomas Abeli; Hannah Branwood; Inmaculada Ferrando Pardo; P. Pablo Ferrer Gallego; Elke Zippel; Luísa Gouveia; Carlos Alberto Lobo; Francisco Fernandes; et al. (Biodiversity and Conservation, 2025)

Tree Diversity Increases Forest Temperature Buffering via Enhancing Canopy Density and Structural Diversity - Florian Schnabel; Rémy Beugnon; Bo Yang; Ronny Richter; Nico Eisenhauer; Yuanyuan Huang; Xiaojuan Liu; Christian Wirth; Simone Cesarz; Andreas Fichtner; Maria D. Perles‐Garcia; Georg J. A. Hähn; et al. (Ecology Letters, 2025)
Global warming is increasing the frequency and intensity of climate extremes. Forests may buffer climate extremes by creating their own attenuated microclimate below their canopy, which maintains forest functioning and biodiversity. However, the effect of tree diversity on temperature buffering in forests is largely unexplored. Here, we show that tree species richness increases forest temperature buffering across temporal scales over six years in a large‐scale tree diversity experiment covering a species richness gradient of 1 to 24 tree species. We found that species richness strengthened the cooling of hot and the insulation against cold daily and monthly air temperatures and temperature extremes. This buffering effect of tree species richness was mediated by enhanced canopy density and structural diversity in species‐rich stands. Safeguarding and planting diverse forests may thus mitigate negative effects of global warming and climate extremes on below‐canopy ecosystem functions and communities.

Biocultural evolution, narratives, and emerging cultures of sustainability - Pierre D. Glynn; Kristan Cockerill; Jennifer F. Helgeson; Gregory J. Newman; Simone A. Glynn; Paul A. White (Mitigation and Adaptation Strategies for Global Change, 2025)
Biocultural evolution has created propensities that guide, largely unconsciously, how species think and behave. Human anthropocentrism leads to a lack of recognition of the propensities shared by Homo sapiens and other species. Human narratives and values reflect these propensities even as they also affect evolution and possible pathways of (un)sustainability for social-ecological systems (SES). Signals and narratives provide information and affective communication that simplify SES complexities and guide thought and behavior. This paper presents key propensities, signals, and a narrative typology to raise conscious awareness of their roles in shaping largely unconscious human priorities that emanate from biocultural evolution and that are unsuited to modern challenges. Four dimensions of values (i.e., experiential, utilitarian, communitarian, transcendental) are also considered, and the transcendental concept of a “realm of knowledge-ends” is presented. The concept posits that because of the cumulative knowledge that they represent, biological and cultural entities ought to be afforded worth and value as “ends-in-themselves”, transcending their immediate utilities. Local-to-regional-to-global approaches are mentioned that could help strive toward this goal and improve global SES sustainability. A case study from New Zealand illustrates how four foundational elements (biocultural propensities, signals, narratives, and values) in the conceptual framework presented by this paper can be used: (a) to enhance critical reflective thinking and analyze modern natural resources and environmental situations; and (b) to create and use records of engagement and decision-making for improved participatory processes and societal engagement. Paying attention to biocultural propensities, signals, narratives, and values can improve sustainability pathways.

Extracellular nicotinamide phosphoribosyltransferase (eNAMPT) drives abnormal pericyte-rich vasculature in triple-negative breast cancer - Marianna Moro; Federica Carolina Balestrero; Giorgia Colombo; Simone Torretta; Nausicaa Clemente; Valerio Ciccone; Erika Del Grosso; Sandra Donnini; Cristina Travelli; Fabrizio Condorelli; Sabina Sangaletti; Armando A. Genazzani; et al. (Angiogenesis, 2025)

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

Integrating Landscapes of Fear and Energy Reveals the Behavioural Strategies That Shape Predator–Prey Interactions - Michael A. Gil; Cyril J. Michel; Simone Olivetti; Vamsi Sridharan; Andrew M. Hein (Ecology Letters, 2025)
Disparate bodies of literature implicate risk avoidance and energy conservation as important drivers of animal movement decisions. Theory posits that these phenomena interact in ecologically consequential ways, but rigorous empirical tests of this hypothesis have been hampered by data limitations. We fuse fluid dynamics, telemetry, and attack data to reconstruct risk and energy landscapes traversed by migrating juvenile salmon and their predators. We find that migrants primarily use midriver microhabitats that facilitate migration at night. During daylight, predators become more aggressive in the midriver, and prey reduce midriver use in favour of nearshore microhabitats, resulting in increased energy expenditure and decreased migration efficiency. Predators attack most when migrants are not prioritising threat avoidance and during ephemeral periods of low lighting. Our findings suggest that predator–prey interactions result from an interplay between landscapes of fear and energy, which can determine the degree to which predators affect prey through mortality or fear.

Different dissolved organic matter sources sustain microbial life in a sandy beach subterranean estuary – an incubation study - Grace A. Abarike; Simone Brick; Bert Engelen; Jutta Niggemann (Frontiers in Marine Science, 2024)
In subterranean estuaries (STE), fresh and saline groundwater introduce dissolved organic matter (DOM) of different origin. This DOM serves as substrate for microorganisms that thrive in the STE. In high-energy beaches with dynamic porewater advection, microbial communities face frequent changes in groundwater composition, even at several meters depth. It is unknown how DOM from deep STE groundwater (> 5 m depth) is transformed by prevailing microbial communities. To address this question, we performed sediment incubations in flow-through reactors (FTRs) with deep (6 m depth) STE groundwater of low (1.6) and high salinity (29.1). FTR setups were sampled daily for quantification of dissolved organic carbon (DOC), and at start and end (day 13) of the incubation for analysis of DOM composition, microbial cell numbers and community composition. Solid-phase extracted DOM was molecularly characterized via ultrahigh-resolution Fourier-transform ion cyclotron resonance mass spectrometry. Both groundwater types contained mainly reworked DOM. Corroborating its presumed origin, the fresh groundwater had a more terrestrial DOM signature with a higher proportion of aromatic compounds compared to the saline groundwater. Over the course of the incubation, DOC concentrations increased primarily due to leaching of sedimentary organic matter, providing an additional source of DOM. In all setups, the DOM composition changed significantly from start to end, and similarly for fresh and saline groundwater. From the ~2700 molecular formulae (MF) detected on day 0, 34-35% were removed during the incubations, demonstrating the potential of deep STE microbial communities to degrade recalcitrant DOM that is supplied with the advective porewater flow. However, a substantial portion of MF (63-64%) was retained in both groundwater types, indicating that a fraction of deep STE-DOM is resistant to removal. Properties of MF that were newly detected on day 13 (26-28%) were indicative of labile DOM. Some of these newly detected MF were also identified in sediment-leachates, suggesting that beach sediments are a source of fresh DOM for the STE microbial communities. It is likely that due to longer groundwater residence time in the STE, continuous leaching and microbial processing shift the molecular composition of released DOM from more labile to more recalcitrant DOM.

Crustal seismicity and updated stress mapping in the Bolivian Orocline, Central Andes - Gonzalo A. Fernández M; Marcelo Assumpção; Simone Cesca; Mayra Nieto (Journal of South American Earth Sciences, 2024)

An inception framework hypothesis for karst development in the Burren, Ireland - Robert A. Watson; Colin Bunce; David Drew; Simone Fiaschi; Caoimhe Hickey; John Walsh; Eoghan P. Holohan (Geomorphology, 2024)

Advancing an integrated understanding of land–ocean connections in shaping the marine ecosystems of coastal temperate rainforest ecoregions - Brian P. V. Hunt; Simone Alin; Allison Bidlack; Heida L. Diefenderfer; Jennifer M. Jackson; Colleen T. E. Kellogg; Peter Kiffney; Kyra A. St. Pierre; Eddy Carmack; William C. Floyd; Eran Hood; Alexander R. Horner‐Devine; et al. (Limnology and Oceanography, 2024)
Land and ocean ecosystems are strongly connected and mutually interactive. As climate changes and other anthropogenic stressors intensify, the complex pathways that link these systems will strengthen or weaken in ways that are currently beyond reliable prediction. In this review we offer a framework of land–ocean couplings and their role in shaping marine ecosystems in coastal temperate rainforest (CTR) ecoregions, where high freshwater and materials flux result in particularly strong land–ocean connections. Using the largest contiguous expanse of CTR on Earth—the Northeast Pacific CTR (NPCTR)—as a case study, we integrate current understanding of the spatial and temporal scales of interacting processes across the land–ocean continuum, and examine how these processes structure and are defining features of marine ecosystems from nearshore to offshore domains. We look ahead to the potential effects of climate and other anthropogenic changes on the coupled land–ocean meta‐ecosystem. Finally, we review key data gaps and provide research recommendations for an integrated, transdisciplinary approach with the intent to guide future evaluations of and management recommendations for ongoing impacts to marine ecosystems of the NPCTR and other CTRs globally. In the light of extreme events including heatwaves, fire, and flooding, which are occurring almost annually, this integrative agenda is not only necessary but urgent.

Ecosystem engineers enhance the multifunctionality of an urban novel ecosystem: Population persistence and ecosystem resilience since the 1980s - Louise B. Firth; Anastasia Forbes; Antony M. Knights; Kathryn A. O'Shaughnessy; Wahaj Mahmood-Brown; Lewis Struthers; Ellie Hawcutt; Katrin Bohn; Martin D.J. Sayer; James Quinn; Jan Allen; Simone Dürr; et al. (Science of The Total Environment, 2024)

The Impact of Size-Dependent and Stress-Dependent Fracture Properties on the Biot and Skempton Coefficients of Fractured Rocks - Silvia De Simone; Caroline Darcel; Hossein A. Kasani; Diego Mas Ivars; Philippe Davy (Rock Mechanics and Rock Engineering, 2024)

The role of microbial communities in biogeochemical cycles and greenhouse gas emissions within tropical soda lakes - Thierry A. Pellegrinetti; Simone R. Cotta; Yara B. Feitosa; Paul L.A. Melo; Wanderlei Bieluczyk; Antonio M.M. Silva; Lucas W. Mendes; Hugo Sarmento; Plinio B. Camargo; Siu M. Tsai; Marli F. Fiore (Science of The Total Environment, 2024)

Impact of the extreme 2015-16 El Niño climate event on forest and savanna tree species of the Amazonia-Cerrado transition - Nayane C.C.S. Prestes; Beatriz S. Marimon; Paulo S. Morandi; Simone M. Reis; Ben Hur Marimon Junior; Wesley J.A. Cruz; Edmar A. Oliveira; Lucas H. Mariano; Fernando Elias; Denilson M. Santos; Adriane Esquivel-Muelbert; Oliver L. Phillips (Flora, 2024)

Comprehensive characterization of bacterial glycoconjugate vaccines by liquid chromatography - mass spectrometry - Fiammetta Di Marco; Agnes L. Hipgrave Ederveen; Guusje van Schaick; Alan B. Moran; Elena Domínguez-Vega; Simone Nicolardi; Constantin Blöchl; Carolien A. Koeleman; Renzo Danuser; Ali Al Kaabi; Viktoria Dotz; Jan Grijpstra; et al. (Carbohydrate Polymers, 2024)

Absence of claudin-3 does not alter intestinal absorption of phosphate in mice - Zsuzsa Radványi; Udo Schnitzbauer; Eva Maria Pastor-Arroyo; Simone Hölker; Nina Himmerkus; Markus Bleich; Dominik Müller; Tilman Breiderhoff; Nati Hernando; Carsten A. Wagner (Pflügers Archiv - European Journal of Physiology, 2024)
Intestinal absorption of phosphate is bimodal, consisting of a transcellular pathway and a poorly characterized paracellular mode, even though the latter one contributes to the bulk of absorption under normal dietary conditions. Claudin-3 ( Cldn3 ), a tight junction protein present along the whole intestine in mice, has been proposed to tighten the paracellular pathway for phosphate. The aim of this work was to characterize the phosphate-related phenotype of Cldn3 -deficient mice. Cldn3 -deficient mice and wildtype littermates were fed standard diet or challenged for 3 days with high dietary phosphate. Feces, urine, blood, intestinal segments and kidneys were collected. Measurements included fecal, urinary, and plasma concentrations of phosphate and calcium, plasma levels of phosphate-regulating hormones, evaluation of trans- and paracellular phosphate transport across jejunum and ileum, and analysis of intestinal phosphate and calcium permeabilities. Fecal and urinary excretion of phosphate as well as its plasma concentration was similar in both genotypes, under standard and high-phosphate diet. However, Cldn3 -deficient mice challenged with high dietary phosphate had a reduced urinary calcium excretion and increased plasma levels of calcitriol. Intact FGF23 concentration was also similar in both groups, regardless of the dietary conditions. We found no differences either in intestinal phosphate transport (trans- or paracellular) and phosphate and calcium permeabilities between genotypes. The intestinal expression of claudin-7 remained unaltered in Cldn3 -deficient mice. Our data do not provide evidence for a decisive role of Cldn3 for intestinal phosphate absorption and phosphate homeostasis. In addition, our data suggest a novel role of Cldn3 in regulating calcitriol levels.

Unveiling the antifungal mechanisms of CTP, a new copper(II)-theophylline/1,10-phenanthroline complex, on drug-resistant non-albicans Candida species - Heloisa F. Frota; Pedro F. Barbosa; Carolline M. A. Lorentino; Lorena R. F. Affonso; Lívia S. Ramos; Simone S. C. Oliveira; Lucieri O. P. Souza; Olufunso O. Abosede; Adeniyi S. Ogunlaja; Marta H. Branquinha; André L. S. Santos (BioMetals, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Nearshore microbial communities of the Pacific Northwest coasts of Canada and the U.S. - Linda D. Rhodes; Nicolaus G. Adams; Ramon Gallego Simon; Maria T. Kavanaugh; Simone R. Alin; Richard A. Feely (Frontiers in Marine Science, 2024)
A survey of marine pelagic coastal microbial communities was conducted over a large geographic latitude range, from Cape Mendocino in northern California USA to Queen Charlotte Sound in British Columbia Canada, during the spring to summer transition. DNA metabarcoding and flow cytometry were used to characterize microbial communities. Physical and chemical oceanography indicated moderate conditions during the survey with no widespread upwelling, marine heat wave, or other extreme conditions. However, four locations displayed features approaching acidified conditions: Heceta Head, Newport, Copalis Beach, and Cape Flattery. Although bacterial and archaeal communities at the Juan de Fuca canyon and northward had high similarity, those south of the Juan de Fuca canyon were well differentiated from each other. In contrast, eukaryotic microbial communities exhibited stronger geographic differentiation than bacterial and archaeal communities across the extent of the survey. Seawater parameters that were best predictors of bacterial and archaeal community structure were temperature, pH, and dissolved inorganic nutrients (nitrate, phosphate, silicate), while those that were best predictors of eukaryotic microbial community structure were salinity, dissolved oxygen, total alkalinity, and dissolved inorganic nutrients (nitrite, silicate). Although five bacterial and archaeal indicators for potentially corrosive waters were identified ( Colwellia , Nitrosopumilus , Nitrosopelagicus , Sup05 cluster, Sva0996 marine group), no eukaryotic microbial indicators were found. Potentially pathogenic taxa detected in the survey included four disease-causing bacteria for mammals, finfish, and/or shellfish ( Coxiella , Flavobacterium , Francisella , Tenacibaculum ), sixteen genera of microalgae capable of producing biotoxins, and fifteen parasitic species. This study demonstrates the value of coordinating microbial sampling and analysis with broad-scale oceanographic surveys to generate insights into community structures of these important pelagic trophic levels.

Inhibition of cancer induced coagulation and thrombosis by snake venom proteins - Miguel Engelhardt; Wolfgang M.J. Obermann; Simone König; Johannes A. Eble (Toxicon, 2024)

Snake venom components prevents platelets from being hijacked by tumor cells - Wolfgang M.J. Obermann; Miguel Engelhardt; Simone König; Mascha K. Feickert; Raquel Sanz-Soler; Johannes A. Eble (Toxicon, 2024)

Microglial responses to inflammatory challenge in adult rats altered by developmental exposure to polychlorinated biphenyls in a sex-specific manner - Katherine A. Walker; Simone T. Rhodes; Deborah A. Liberman; Andrea C. Gore; Margaret R. Bell (NeuroToxicology, 2024)

Formation and hydrothermal alteration of a volcanic center: Melt pooling and mass transfers at Langseth Ridge (Gakkel Ridge, Arctic Ocean) - Elmar Albers; Nele Behrendt; Alexander Diehl; Felix Genske; Patrick Monien; Simone A. Kasemann; Autun Purser; Antje Boetius; Wolfgang Bach (Marine Geology, 2024)

Recent deep-sea nematodes and agglutinated foraminifera select specific grains and bioclasts from their environments: Ecological implications - Sunil K. Das; Raj K. Singh; Mariem Saavedra-Pellitero; Julia Gottschalk; Carlos A. Alvarez Zarikian; Lester Lembke-Jene; Frank Lamy; Gisela Winckler; Jennifer L. Middleton; Helge W. Arz; Chandranath Basak; Anieke Brombacher; et al. (Marine Micropaleontology, 2024)

From time series to visibility algorithms: A novel approach to study the spread of SARS-CoV-2 in wastewater - A. Simone; A. Cesaro; G. Esposito (Journal of Water Process Engineering, 2024)

Circular and sustainable space: Findings from hyperspectral imaging - N. Aversano; G. Bonifazi; I. D'Adamo; R. Palmieri; S. Serranti; A. Simone (Journal of Cleaner Production, 2024)

Revelations of interannual dune evolution from the swiftest aeolian system on Mars by MRO/HiRISE long-term monitoring - Matthew Chojnacki; David A. Vaz; Pruthviraj J. Acharya; Simone Silvestro; Isaac B. Smith (Icarus, 2024)

Hydrodynamics of a highly stratified small estuary and the influence of nearby river plumes - I. Iglesias; F.A. Buschman; G. Simone; F. Amorim; A. Bio; L.R. Vieira; H. Boisgontier; L. Zaggia; V. Moschino; F. Madricardo; I. Sousa-Pinto; S.C. Antunes (Estuarine, Coastal and Shelf Science, 2024)

Late Miocene to Early Pliocene paleoceanographic evolution of the Central South Pacific: A deep-sea benthic foraminiferal perspective - Sunil K. Das; N. Mahanta; B. Sahoo; Raj K. Singh; Carlos A. Alvarez Zarikian; Manish Tiwari; Nishant Vats; Nihal; Frank Lamy; Gisela Winckler; Jennifer L. Middleton; Helge W. Arz; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Sphingosine is involved in PAPTP-induced death of pancreas cancer cells by interfering with mitochondrial functions - Sameer H. Patel; Gregory C. Wilson; Yuqing Wu; Simone Keitsch; Barbara Wilker; Andrea Mattarei; Syed A. Ahmad; Ildiko Szabo; Erich Gulbins (Journal of Molecular Medicine, 2024)
Pancreas ductal adenocarcinoma belongs to the most common cancers, but also to the tumors with the poorest prognosis. Here, we pharmacologically targeted a mitochondrial potassium channel, namely mitochondrial Kv1.3, and investigated the role of sphingolipids and mutated Kirsten Rat Sarcoma Virus (KRAS) in Kv1.3-mediated cell death. We demonstrate that inhibition of Kv1.3 using the Kv1.3-inhibitor PAPTP results in an increase of sphingosine and superoxide in membranes and/or membranes associated with mitochondria, which is enhanced by KRAS mutation. The effect of PAPTP on sphingosine and mitochondrial superoxide formation as well as cell death is prevented by sh-RNA-mediated downregulation of Kv1.3. Induction of sphingosine in human pancreas cancer cells by PAPTP is mediated by activation of sphingosine-1-phosphate phosphatase and prevented by an inhibitor of sphingosine-1-phosphate phosphatase. A rapid depolarization of isolated mitochondria is triggered by binding of sphingosine to cardiolipin, which is neutralized by addition of exogenous cardiolipin. The significance of these findings is indicated by treatment of mutated KRAS-harboring metastasized pancreas cancer with PAPTP in combination with ABC294640, a blocker of sphingosine kinases. This treatment results in increased formation of sphingosine and death of pancreas cancer cells in vitro and, most importantly, prolongs in vivo survival of mice challenged with metastatic pancreas cancer. Key messages Pancreatic ductal adenocarcinoma (PDAC) is a common tumor with poor prognosis. The mitochondrial Kv1.3 ion channel blocker induced mitochondrial sphingosine. Sphingosine binds to cardiolipin thereby mediating mitochondrial depolarization. Sphingosine is formed by a PAPTP-mediated activation of S1P-Phosphatase. Inhibition of sphingosine-consumption amplifies PAPTP effects on PDAC in vivo.

Discovery of novel direct small-molecule inhibitors targeting HIF-2α using structure-based virtual screening, molecular dynamics simulation, and MM-GBSA calculations - Behnaz Yazdani; Hajar Sirous; Francisco J. Enguita; Simone Brogi; Peter A. C. Wing; Afshin Fassihi (Molecular Diversity, 2024)

The relational shift in urban ecology: From place and structures to multiple modes of coproduction for positive urban futures - Steward T. A. Pickett; AbdouMaliq T. Simone; Pippin Anderson; Ayyoob Sharifi; Aliyu Barau; Fushcia-Ann Hoover; Daniel L. Childers; Timon McPhearson; Tischa A. Muñoz-Erickson; Chantal Pacteau; Morgan Grove; Niki Frantzeskaki; et al. (Ambio, 2024)
This perspective emerged from ongoing dialogue among ecologists initiated by a virtual workshop in 2021. A transdisciplinary group of researchers and practitioners conclude that urban ecology as a science can better contribute to positive futures by focusing on relationships, rather than prioritizing urban structures. Insights from other relational disciplines, such as political ecology, governance, urban design, and conservation also contribute. Relationality is especially powerful given the need to rapidly adapt to the changing social and biophysical drivers of global urban systems. These unprecedented dynamics are better understood through a relational lens than traditional structural questions. We use three kinds of coproduction—of the social-ecological world, of science, and of actionable knowledge—to identify key processes of coproduction within urban places. Connectivity is crucial to relational urban ecology. Eight themes emerge from the joint explorations of the paper and point toward social action for improving life and environment in urban futures.

Cytotoxic and molecular evaluation of spilanthol obtained from Acmella oleracea (L.) R. K. Jansen (jambu) in human gastric cancer cells - Mayra Suelen da S. Pinheiro; Daniele A. Moysés; Natasha C. R. Galucio; Willian Oliveira Santos; Jeferson R. Souza Pina; Luana C. Oliveira; Simone Yasue S. Silva; Sebastião da Cruz Silva; Nilton Ferreira Frazão; Patrícia Santana B. Marinho; Andrea L. F. Novais; André S. Khayat; et al. (Natural Product Research, 2024)

Effects of Inclusion of Food Purchase Restrictions and Incentives in a Food Benefit Program on Diet Quality and Food Purchasing: Results From a Randomized Trial - Lisa J. Harnack; J. Michael Oakes; Brian Elbel; Sarah A. Rydell; Tessa A. Lasswell; Nathan R. Mitchell; Sruthi Valluri; Simone A. French (Journal of the Academy of Nutrition and Dietetics, 2024)

When is it safe to go home? Post-predation assessment of risk and safety when personal information conflicts with social cues - Brian D. Wisenden; Cat M. Adkins; Seth A. Campbell; Shree Chakraborty; Madelyn E. Cloutier; Alex D. Doebler; Kathryn A. Hanson; Lou Hoff; Molly I. M. Johnson; Philip S. Larson; Claire M. Lukasik; Zoe R. Michaelson; et al. (Behavioral Ecology and Sociobiology, 2024)

Biological invasions are a population‐level rather than a species‐level phenomenon - Phillip J. Haubrock; Ismael Soto; Danish A. Ahmed; Ali R. Ansari; Ali Serhan Tarkan; Irmak Kurtul; Rafael L. Macêdo; Adrián Lázaro‐Lobo; Mathieu Toutain; Ben Parker; Dagmara Błońska; Simone Guareschi; et al. (Global Change Biology, 2024)
Biological invasions pose a rapidly expanding threat to the persistence, functioning and service provisioning of ecosystems globally, and to socio‐economic interests. The stages of successful invasions are driven by the same mechanism that underlies adaptive changes across species in general—via natural selection on intraspecific variation in traits that influence survival and reproductive performance (i.e., fitness). Surprisingly, however, the rapid progress in the field of invasion science has resulted in a predominance of species‐level approaches (such as deny lists), often irrespective of natural selection theory, local adaptation and other population‐level processes that govern successful invasions. To address these issues, we analyse non‐native species dynamics at the population level by employing a database of European freshwater macroinvertebrate time series, to investigate spreading speed, abundance dynamics and impact assessments among populations. Our findings reveal substantial variability in spreading speed and abundance trends within and between macroinvertebrate species across biogeographic regions, indicating that levels of invasiveness and impact differ markedly. Discrepancies and inconsistencies among species‐level risk screenings and real population‐level data were also identified, highlighting the inherent challenges in accurately assessing population‐level effects through species‐level assessments. In recognition of the importance of population‐level assessments, we urge a shift in invasive species management frameworks, which should account for the dynamics of different populations and their environmental context. Adopting an adaptive, region‐specific and population‐focused approach is imperative, considering the diverse ecological contexts and varying degrees of susceptibility. Such an approach could improve and refine risk assessments while promoting mechanistic understandings of risks and impacts, thereby enabling the development of more effective conservation and management strategies.

Tree diversity enhances predation by birds but not by arthropods across climate gradients - Carla Vázquez‐González; Bastien Castagneyrol; Evalyne W. Muiruri; Luc Barbaro; Luis Abdala‐Roberts; Nadia Barsoum; Jochen Fründ; Carolyn Glynn; Hervé Jactel; William J. McShea; Simone Mereu; Kailen A. Mooney; et al. (Ecology Letters, 2024)
Tree diversity can promote both predator abundance and diversity. However, whether this translates into increased predation and top‐down control of herbivores across predator taxonomic groups and contrasting environmental conditions remains unresolved. We used a global network of tree diversity experiments ( TreeDivNet ) spread across three continents and three biomes to test the effects of tree species richness on predation across varying climatic conditions of temperature and precipitation. We recorded bird and arthropod predation attempts on plasticine caterpillars in monocultures and tree species mixtures. Both tree species richness and temperature increased predation by birds but not by arthropods. Furthermore, the effects of tree species richness on predation were consistent across the studied climatic gradient. Our findings provide evidence that tree diversity strengthens top‐down control of insect herbivores by birds, underscoring the need to implement conservation strategies that safeguard tree diversity to sustain ecosystem services provided by natural enemies in forests.

Heavy metal and trace element concentrations in the blood of scalloped hammerhead sharks (Sphyrna lewini) from La Paz Bay, México - Darren A. Whitehead; Joel H. Gayford; Francesca Pancaldi; Jacopo Gobbato; Giulia Boldrin; Maria Tringali; James T. Ketchum; Felipe Galvan Magaña; Davide Seveso; Simone Montano (Marine Pollution Bulletin, 2024)

Understanding vessel noise across a network of marine protected areas - Megan F McKenna; Timothy J Rowell; Tetyana Margolina; Simone Baumann-Pickering; Alba Solsona-Berga; Jeffrey D Adams; John Joseph; Ella B Kim; Annebelle CM Kok; Anke Kügler; Marc O Lammers; Karlina Merkens; et al. (Environmental Monitoring and Assessment, 2024)
Protected areas are typically managed as a network of sites exposed to varying anthropogenic conditions. Managing these networks benefits from monitoring of conditions across sites to help prioritize coordinated efforts. Monitoring marine vessel activity and related underwater radiated noise impacts across a network of protected areas, like the U.S. National Marine Sanctuary system, helps managers ensure the quality of habitats used by a wide range of marine species. Here, we use underwater acoustic detections of vessels to quantify different characteristics of vessel noise at 25 locations within eight marine sanctuaries including the Hawaiian Archipelago and the U.S. east and west coasts. Vessel noise metrics, including temporal presence and sound levels, were paired with Automatic Identification System (AIS) vessel tracking data to derive a suite of robust vessel noise indicators for use across the network of marine protected areas. Network-wide comparisons revealed a spectrum of vessel noise conditions that closely matched AIS vessel traffic composition. Shifts in vessel noise were correlated with the decrease in vessel activity early in the COVID-19 pandemic, and vessel speed reduction management initiatives. Improving our understanding of vessel noise conditions in these protected areas can help direct opportunities for reducing vessel noise, such as establishing and maintaining noise-free periods, enhancing port efficiency, engaging with regional and international vessel quieting initiatives, and leveraging co-benefits of management actions for reducing ocean noise.

Antifungal potential of the new copper(II)-theophylline/1,10-phenanthroline complex against drug-resistant Candida species - Heloisa F. Frota; Carolline M. A. Lorentino; Pedro F. Barbosa; Lívia S. Ramos; Iuri C. Barcellos; Lucas Giovanini; Lucieri O. P. Souza; Simone S. C. Oliveira; Olufunso O. Abosede; Adeniyi S. Ogunlaja; Matheus M. Pereira; Marta H. Branquinha; et al. (BioMetals, 2024)

State of the California Current Ecosystem report in 2022: a tale of two La Niñas - Andrew R. Thompson; Rasmus Swalethorp; Michaela Alksne; Jarrod A. Santora; Elliott L. Hazen; Andrew Leising; Erin Satterthwaite; William J. Sydeman; Clarissa R. Anderson; Toby D. Auth; Simone Baumann-Pickering; Timothy Baumgardner; et al. (Frontiers in Marine Science, 2024)
2022 marked the third consecutive La Niña and extended the longest consecutive stretch of negative Oceanic Niño Index since 1998-2001. While physical and biological conditions in winter and spring largely adhered to prior La Niña conditions, summer and fall were very different. Similar to past La Niña events, in winter and spring coastal upwelling was either average or above average, temperature average or below average, salinity generally above average. In summer and fall, however, upwelling and temperature were generally average or slightly below average, salinity was close to average and chlorophyll a was close to average. Again, as during prior La Niña events, biomass of northern/southern copepods was above/below average off Oregon in winter, and body size of North Pacific krill in northern California was above average in winter. By contrast, later in the year the abundance of northern krill dropped off Oregon while southern copepods increased and body sizes of North Pacific krill fell in northern California. Off Oregon and Washington abundances of market squid and Pacific pompano (indicators of warm, non-typical La Niña conditions) were high. In the 20 th century, Northern anchovy recruitment tended to be high during cold conditions, but despite mostly warm conditions from 2015-2021 anchovy populations boomed and remained high in 2022. Resident seabird reproductive success, which tended in the past to increase during productive La Niña conditions was highly variable throughout the system as common murre and pelagic cormorant, experienced complete reproductive failure at Yaquina Head, Oregon while Brandt’s cormorant reproduction was average. At three sampling locations off central California, however, common murre reproduction was close to or above average while both pelagic and Brandt’s cormorant were above average. California sealion reproduction has been above average each year since 2016, and pup weight was also above average in 2022, likely in response not to La Niña or El Niño but continuous high abundance of anchovy. The highly variable and often unpredictable physical and biological conditions in 2022 highlight a growing recognition of disconnects between basin-scale indices and local conditions in the CCE. “July-December 2022 is the biggest outlier from individual “strong” La Niña (events) ever going back to the 50s.” – Nate Mantua

Amplified drying in South Asian summer monsoon precipitation due to anthropogenic sulfate aerosols - Suvarna Fadnavis; A. Asutosh; Prashant Chavan; Rakshit Thaware; Simone Tilmes (Environmental Pollution, 2024)

Corroboration and contradictions in global biodiversity indicators - Simone L. Stevenson; Kate Watermeyer; Simon Ferrier; Elizabeth A. Fulton; Hui Xiao; Emily Nicholson (Biological Conservation, 2024)

Evaluation of the Treatment with Akkermansia muciniphila BAA-835 of Chemotherapy-induced Mucositis in Mice - Ramon O. Souza; Vivian C. Miranda; Mônica F. Quintanilha; Bruno Gallotti; Samantha R. M. Oliveira; Janayne L. Silva; Jacqueline I. Alvarez-Leite; Luís C. L. Jesus; Vasco Azevedo; Kátia D. Vital; Simone O. A. Fernandes; Valbert N. Cardoso; et al. (Probiotics and Antimicrobial Proteins, 2024)

High Concentrations of Cannabidiol Induce Neurotoxicity in Neurosphere Culture System - Simone A. A. Romariz; Viviam Sanabria; Karina Ribeiro da Silva; Miguel L. Quintella; Bruna A. G. de Melo; Marimélia Porcionatto; Danilo Candido de Almeida; Beatriz M. Longo (Neurotoxicity Research, 2024)

Enhancing Tree Performance Through Species Mixing: Review of a Quarter-Century of TreeDivNet Experiments Reveals Research Gaps and Practical Insights - Leen Depauw; Emiel De Lombaerde; Els Dhiedt; Haben Blondeel; Luis Abdala-Roberts; Harald Auge; Nadia Barsoum; Jürgen Bauhus; Chengjin Chu; Abebe Damtew; Nico Eisenhauer; Marina V. Fagundes; et al. (Current Forestry Reports, 2024)

Assessing the ecological potential of reservoirs: a principal response curve (PRC) analysis approach - Edna Cabecinha; Miguel Â. Pardal; João A. Cabral; Sandra M. Monteiro; Rui Cortes; Maria J. Saavedra; Simone Varandas; Paul Van den Brink (Hydrobiologia, 2024)
Heavily modified water bodies (HMWB) have been seriously affected by human activities and natural processes promoting their imbalance, and impacting their functioning and biodiversity. This study explores a new approach of monitoring and assessing water quality in Mediterranean reservoirs using phytoplankton communities across a disturbance gradient, according to water framework directive. Phytoplankton and environmental data were sampled in 34 reservoirs over 8 years. Two types of reservoirs were analyzed: Type1 “run-of-river reservoirs” (located in the main rivers, with a low residence time); and Type2 “true reservoirs” (located in tributaries, with high residence time). The transition from deeper and colder reservoirs (reference sites) to shallow and warmer (impaired sites) was clear in Type2, correlated to organic pollution and mineral gradients. Impaired sites from both types showed a higher richness of tolerant taxa. Principal response curve (PRC) provided a concise summary of phytoplankton temporal dynamics and assessed ecosystem health for Mediterranean HMWBs. PRC will provide a powerful tool for environmental quality assessment and be incorporated into monitoring and assessment programs. This approach can help policymakers to manage natural capital to achieve multiple objectives, mainly increasing ecosystem services, and improve readability and interpretation of spatial patterns in temporal changes.

Groundwater is a hidden global keystone ecosystem - Mattia Saccò; Stefano Mammola; Florian Altermatt; Roman Alther; Rossano Bolpagni; Anton Brancelj; David Brankovits; Cene Fišer; Vasilis Gerovasileiou; Christian Griebler; Simone Guareschi; Grant C. Hose; et al. (Global Change Biology, 2024)
Groundwater is a vital ecosystem of the global water cycle, hosting unique biodiversity and providing essential services to societies. Despite being the largest unfrozen freshwater resource, in a period of depletion by extraction and pollution, groundwater environments have been repeatedly overlooked in global biodiversity conservation agendas. Disregarding the importance of groundwater as an ecosystem ignores its critical role in preserving surface biomes. To foster timely global conservation of groundwater, we propose elevating the concept of keystone species into the realm of ecosystems, claiming groundwater as a keystone ecosystem that influences the integrity of many dependent ecosystems. Our global analysis shows that over half of land surface areas (52.6%) has a medium‐to‐high interaction with groundwater, reaching up to 74.9% when deserts and high mountains are excluded. We postulate that the intrinsic transboundary features of groundwater are critical for shifting perspectives towards more holistic approaches in aquatic ecology and beyond. Furthermore, we propose eight key themes to develop a science‐policy integrated groundwater conservation agenda. Given ecosystems above and below the ground intersect at many levels, considering groundwater as an essential component of planetary health is pivotal to reduce biodiversity loss and buffer against climate change.

Hydrocarbon refrigerants boiling local heat transfer coefficients inside a Brazed Plate Heat Exchanger (BPHE) - Giovanni A. Longo; Simone Mancin; Giulia Righetti; Claudio Zilio (International Journal of Refrigeration, 2023)

Heavy metals and health risk assessment of Brazilian artisanal cheeses - Luciana S. Rocha; Gustavo Luis P.A. Ramos; Ramon S. Rocha; Bernardo F. Braz; Ricardo E. Santelli; Erick A. Esmerino; Monica Q. Freitas; Eliane T. Mársico; Adriana P.A. Bragotto; Simone L. Quitério; Adriano G. Cruz (Food Research International, 2023)

Equivalent Biot and Skempton Poroelastic Coefficients for a Fractured Rock Mass from a DFN Approach - Silvia De Simone; Caroline Darcel; Hossein A. Kasani; Diego Mas Ivars; Philippe Davy (Rock Mechanics and Rock Engineering, 2023)

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

Novel plant-associated genomoviruses from the Brazilian Cerrado biome - Flávia Milene B. Nery; Josiane G. Batista; Felipe Fochat. S. Melo; Simone G. Ribeiro; Leonardo S. Boiteux; Fernando L. Melo; Juliana Gabrielle I. Silva; Luciane de Nazaré A. Reis; Rita C. Pereira-Carvalho (Archives of Virology, 2023)

Comparative Description and Analysis of Oyster Aquaculture in Selected Atlantic Regions: Production, Market Dynamics, and Consumption Patterns - Johannes A. Iitembu; Daniel Fitzgerald; Themistoklis Altintzoglou; Pierre Boudry; Peter Britz; Carrie J. Byron; Daniel Delago; Sophie Girard; Colin Hannon; Marcia Kafensztok; Francisco Lagreze; Jefferson Francisco Alves Legat; et al. (Fishes, 2023)
In the face of an increasing world population and a subsequent need for an increase in sustainable and healthy food production, low trophic species, such as oysters, emerge as a promising alternative. However, regional variations in oyster production techniques, market dynamics, and consumption patterns create challenges for both the global and local industry’s growth. In this study, a descriptive qualitative analysis of oyster markets across seven Atlantic regions was carried out. The Pacific oyster (Crassostrea gigas) was found to be farmed in most Atlantic regions except the US but is classified as invasive in Sweden and potentially invasive in South Africa. Other farmed and/or harvested species include native species (C. gasar and C. rhizophorae) in Brazil, the American cupped oyster (C. virginica) in the US, and the European flat oyster (Ostrea edulis) in France, Sweden, and the US. In Irish farms, Pacific oysters are primarily for export to European markets. The marine aquaculture sectors of Sweden, South Africa, and Namibia, as well as Brazil’s farming for C. gasar, were found to be underdeveloped. This study also observed a variation in licensing, property rights, and regulatory frameworks. Financial challenges for small businesses, ecological implications of seed production techniques, biosecurity risks, and public health considerations are emphasized as critical areas for attention. This study offers valuable insights into the selected markets and can serve as a useful resource for policymakers, aquaculture practitioners, and stakeholders in optimizing global shellfish industry strategies.

Particulate matter pollution and non-targeted analysis of polar compounds in three regions of Brazil - Simone A. Pozza; Priscila B. Gonçalves; Felipe C. Wouters; Josiane A.S. Vendemiatti; Danilo C. Nogarotto; Edenir R. Pereira-Filho; Daniela M.M. Osório; Lincoln L. Romualdo; Joeci R. Godoi; Leonardo Hoinaski; Roberta C. Urban (Chemosphere, 2023)

Catching nano: Evaluating the fate and behaviour of nano-TiO2 in swimming pools through dynamic simulation modelling - Simone Heilgeist; Oz Sahin; Ryo Sekine; Rodney A. Stewart (Journal of Environmental Management, 2023)

Occurrence and distribution of emerging micropollutants in the central part of the German Bight - Pavel Ondruch; Michael P. Schluesener; Georg Dierkes; Kevin Jewell; Torben Kirchgeorg; Simone Hasenbein; Thomas A. Ternes; Arne Wick (Marine Pollution Bulletin, 2023)

Experimental assessment of low temperature phase change materials (PCM) for refrigerating and air conditioning applications - Dario Guarda; Giulia Righetti; Giovanni A. Longo; Claudio Zilio; Simone Mancin (International Journal of Refrigeration, 2023)

Evaluation of a Functional Craft Wheat Beer Fermented with Saccharomyces cerevisiae UFMG A-905 to treat Salmonella Typhimurium infection in mice - Samantha R. M. Oliveira; Lara L. Campos; Maisa N. S. Amaral; Bruno Galotti; Mayra F. Ricci; Katia D. Vital; Ramon O. Souza; Ana Paula T. Uetanabaro; Mateus S. Junqueira; Andreia M. Silva; Simone O. A. Fernandes; Valbert N. Cardoso; et al. (Probiotics and Antimicrobial Proteins, 2023)

Lithium enrichment in the Salar de Diablillos, Argentina, and the influence of Cenozoic volcanism in a basin dominated by Paleozoic basement - Carisa Sarchi; Friedrich Lucassen; Anette Meixner; Pablo J. Caffe; Raúl Becchio; Simone A. Kasemann (Mineralium Deposita, 2023)
Salars with lithium-rich brines are a characteristic feature of the Central Andes, but knowledge about the main sources of lithium and the mobilization processes of lithium in the salar deposits is still incomplete. This work focuses especially on the Salar de Diablillos (southern Puna) as part of a larger area that includes the neighboring Salar Centenario and Salar de Ratones. Building on the ability of Li as a tracer of silicate weathering, we investigate the Li content and isotope composition of samples from the depocenter and catchment of the Diablillos basin (3-D) and conduct a surface reconnaissance in the Centenario and Ratones depocenters to identify the key metallogenic processes. Radiogenic Sr and Nd isotope compositions are also provided to discriminate the main local Li sources. The isotope data in all three depocenters show that most of the Li in the brines and evaporite deposits are derived from Cenozoic volcanic rocks, despite the dominance of the Paleozoic basement in the catchment. In the Centenario and Ratones depocenters, near-surface chemical weathering appears to be the dominant Li mobilization process. In contrast, hydrothermal mobilization of Li also plays a role in the Salar de Diablillos, possibly related to the presence of a fractured basement with pressure zones and artesian conditions in the aquifer at depth. These fluids also show a larger element contribution from the basement.

A new firewall in the fight against breast cancer: in-vitro and in-silico studies correlating chemistry to apoptotic activity of Otostegia fruticosa - Somaia. A. Al-Madhagy; Sameh S. Gad; Eman S. Mostafa; Simone Angeloni; Muhammed A Saad; Omar M. Sabry; Giovanni Caprioli; Seham S. El-Hawary (Natural Product Research, 2023)

Constraining the mechanisms of aeolian bedform formation on Mars through a global morphometric survey - David A. Vaz; Simone Silvestro; Matthew Chojnacki; David C.A. Silva (Earth and Planetary Science Letters, 2023)

Demystifying image-based machine learning: a practical guide to automated analysis of field imagery using modern machine learning tools - Byron T. Belcher; Eliana H. Bower; Benjamin Burford; Maria Rosa Celis; Ashkaan K. Fahimipour; Isabela L. Guevara; Kakani Katija; Zulekha Khokhar; Anjana Manjunath; Samuel Nelson; Simone Olivetti; Eric Orenstein; et al. (Frontiers in Marine Science, 2023)
Image-based machine learning methods are becoming among the most widely-used forms of data analysis across science, technology, engineering, and industry. These methods are powerful because they can rapidly and automatically extract rich contextual and spatial information from images, a process that has historically required a large amount of human labor. A wide range of recent scientific applications have demonstrated the potential of these methods to change how researchers study the ocean. However, despite their promise, machine learning tools are still under-exploited in many domains including species and environmental monitoring, biodiversity surveys, fisheries abundance and size estimation, rare event and species detection, the study of animal behavior, and citizen science. Our objective in this article is to provide an approachable, end-to-end guide to help researchers apply image-based machine learning methods effectively to their own research problems. Using a case study, we describe how to prepare data, train and deploy models, and overcome common issues that can cause models to underperform. Importantly, we discuss how to diagnose problems that can cause poor model performance on new imagery to build robust tools that can vastly accelerate data acquisition in the marine realm. Code to perform analyses is provided at https://github.com/heinsense2/AIO_CaseStudy .

Corrigendum to ‘A horizon scan exercise for aquatic invasive alien species in Iberian inland waters’ Sci. Total Environ.869 (2023) 161798 - Francisco J. Oficialdegui; José M. Zamora-Marín; Simone Guareschi; Pedro M. Anastácio; Pablo García-Murillo; Filipe Ribeiro; Rafael Miranda; Fernando Cobo; Belinda Gallardo; Emili García-Berthou; Dani Boix; Andrés Arias; et al. (Science of The Total Environment, 2023)

Deglacial and Holocene sediment dynamics and provenances off Lancaster Sound: Implications for paleoenvironmental conditions in northern Baffin Bay - Emmanuel Okuma; Johanna Hingst; Jens Weiser; Lina Madaj; Jürgen Titschack; Christoph Vogt; Markus Kienast; Claude Hillaire-Marcel; Dierk Hebbeln; Simone A. Kasemann (Quaternary Science Reviews, 2023)

Trait interactions effects on tropical tree demography depend on the environmental context - Vitor de A. Kamimura; Priscilla de P. Loiola; Carlos P. Carmona; Marco A. Assis; Carlos A. Joly; Flavio A.M. Santos; Simone A. Vieira; Luciana F. Alves; Valéria F. Martins; Eliana Ramos; Rafael F. Ramos; Francesco de Bello (Perspectives in Plant Ecology, Evolution and Systematics, 2023)

Poriferans rift apart: molecular demosponge biodiversity in Central and French Polynesia and comparison with adjacent marine provinces of the Central Indo-Pacific - Adrian Galitz; Merrick Ekins; Eric Folcher; Gabriele Büttner; Kathryn Hall; John N. A. Hooper; Maggie M. Reddy; Simone Schätzle; Olivier P. Thomas; Gert Wörheide; Sylvain Petek; Cécile Debitus; et al. (Biodiversity and Conservation, 2023)
The distribution of marine sponges in the tropical Southwest Pacific Ocean is largely unexplored despite the vital ecological role of sponges in coral reefs and their value as sources of metabolites for drug design. Several collection campaigns to the French Polynesian archipelagos (Society, Marquesas, Tuamotu, Gambier, and Austral) were conducted to assess the bio- and chemodiversity of the island groups. In the course of these scientific expeditions, more than 200 identified sponge specimens were acquired, for which we were able to assign 102 Molecular Operational Taxonomic Units (MOTUs). Based on these MOTUs, we assessed, in the largest analysis of its kind for this area to date, the sponge composition and faunistic overlaps of the marine province Southeast Polynesia with Marquesas and Central Polynesia. We also compared the sponge fauna of these Eastern Indo-Pacific provinces with marine provinces of the adjacent Central Indo-Pacific realm. Our findings corroborate that sponge faunal similarity within marine realms is higher than among realms, and follows the marine barriers to gene flow observed for other taxa. We detected high levels of provincial endemism for marine sponges, consistent with findings from other Indo-Pacific regions. At the level of province, geographical distance and ocean surface currents influence faunal similarity, and constitute the primary factors for the connectivity of sponge faunas between the disjunct and remote island groups in the tropical Southwest Pacific Ocean.

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

A horizon scan exercise for aquatic invasive alien species in Iberian inland waters - Francisco J. Oficialdegui; José M. Zamora-Marín; Simone Guareschi; Pedro M. Anastácio; Pablo García-Murillo; Filipe Ribeiro; Rafael Miranda; Fernando Cobo; Belinda Gallardo; Emili García-Berthou; Dani Boix; Andrés Arias; et al. (Science of The Total Environment, 2023)

Invasive Aspergillosis in Patients with Acute Leukemia: Comparison Between Acute Myeloid and Acute Lymphoid Leukemia - Arnaldo L. Colombo; Maria Daniela Bergamasco; Simone A. Nouér; Paulo de Tarso Oliveira e Castro; Alessandro C. Pasqualotto; Flavio de Queiroz-Telles; Edson Abdala; Jessica F. Ramos; Diego R. Falci; Marcio Nucci (Mycopathologia, 2023)

Stimulation of platelet aggregation by affinity captured rhodocytin from the Malayan pit viper Calloselasma rhodostoma - Mascha K. Feickert; Raquel Sanz-Soler; Stephan Niland; Simone König; Johannes A. Eble; Wolfgang M.J. Obermann (Toxicon, 2023)

Developing a tactical nitrogen fertilizer management strategy for sustainable wheat production - Carolina Fabbri; Bruno Basso; Marco Napoli; Anna Dalla Marta; Simone Orlandini; Rafael A. Martinez-Feria (European Journal of Agronomy, 2023)

Simultaneous targeting of mitochondrial Kv1.3 and lysosomal acid sphingomyelinase amplifies killing of pancreatic ductal adenocarcinoma cells in vitro and in vivo - Sameer H. Patel; Magdalena Bachmann; Stephanie Kadow; Gregory C. Wilson; Mostafa M. L. Abdel-Salam; Kui Xu; Simone Keitsch; Matthias Soddemann; Barbara Wilker; Katrin Anne Becker; Alexander Carpinteiro; Syed A. Ahmad; et al. (Journal of Molecular Medicine, 2023)
Pancreas ductal adenocarcinoma (PDAC) remains a malignant tumor with very poor prognosis and low 5-year overall survival. Here, we aimed to simultaneously target mitochondria and lysosomes as a new treatment paradigm of malignant pancreas cancer in vitro and in vivo. We demonstrate that the clinically used sphingosine analog FTY-720 together with PAPTP, an inhibitor of mitochondrial Kv1.3, induce death of pancreas cancer cells in vitro and in vivo. The combination of both drugs results in a marked inhibition of the acid sphingomyelinase and accumulation of cellular sphingomyelin in vitro and in vivo in orthotopic and flank pancreas cancers. Mechanistically, PAPTP and FTY-720 cause a disruption of both mitochondria and lysosomes, an alteration of mitochondrial bioenergetics and accumulation of cytoplasmic Ca 2+ , events that collectively mediate cell death. Our findings point to an unexpected cross-talk between lysosomes and mitochondria mediated by sphingolipid metabolism. We show that the combination of PAPTP and FTY-720 induces massive death of pancreas cancer cells, thereby leading to a substantially delayed and reduced PDAC growth in vivo. Key messages FTY-720 inhibits acid sphingomyelinase in pancreas cancer cells (PDAC). FTY-720 induces sphingomyelin accumulation and lysosomal dysfunction. The mitochondrial Kv1.3 inhibitor PAPTP disrupts mitochondrial functions. PAPTP and FTY-720 synergistically kill PDAC in vitro. The combination of FTY-720 and PAPTP greatly delays PDAC growth in vivo.

Evaluating environmental controls on the exoskeleton density of larval Dungeness crab via micro computed tomography - Casey P. Saenger; Paul McElhany; Emily L. Norton; D. Shallin Busch; Samantha A. Siedlecki; Simone R. Alin; Richard A. Feely; Albert J. Hermann; Nina Bednaršek (Frontiers in Marine Science, 2023)
Dungeness crab ( Metacarcinus magister ) have significant socioeconomic value, but are threatened by ocean acidification (OA) and other environmental stressors that are driven by climate change. Despite evidence that adult harvests are sensitive to the abundance of larval populations, relatively little is known about how Dungeness megalopae will respond to these stressors. Here we evaluate the ability to use micro-computed tomography (μCT) to detect variations in megalope exoskeleton density and how these measurements reflect environmental variables and calcification mechanisms. We use a combination of field data, culture experiments, and model simulations to suggest resolvable differences in density are best explained by minimum pH at the time zoeae molt into megalopae. We suggest that this occurs because more energy must be expended on active ion pumping to reach a given degree of calcite supersaturation at lower pH. Energy availability may also be reduced due to its diversion to other coping mechanisms. Alternate models based on minimum temperature at the time of the zoea-megalope molt are nearly as strong and complicate the ability to conclusively disentangle pH and temperature influences. Despite this, our results suggest that carryover effects between life stages and short-lived extreme events may be particularly important controls on exoskeleton integrity. μCT-based estimates of exoskeleton density are a promising tool for evaluating the health of Dungeness crab populations that will likely provide more nuanced information than presence-absence observations, but future in situ field sampling and culture experiments are needed to refine and validate our results.

Diversity and enrichment of breeding material for resilience in European forests - Sanna Olsson; Benjamin Dauphin; Véronique Jorge; Delphine Grivet; Anna Maria Farsakoglou; Jose Climent; Paraskevi Alizoti; Patricia Faivre-Rampant; Sara Pinosio; Pascal Milesi; Simone Scalabrin; Francesca Bagnoli; et al. (Forest Ecology and Management, 2023)

Accelerated light carbon sequestration following late Paleocene-early Eocene carbon cycle perturbations - Victor A. Piedrahita; Xiang Zhao; Andrew P. Roberts; Eelco J. Rohling; David Heslop; Simone Galeotti; Laura Rodríguez-Sanz; Fabio Florindo; Katharine M. Grant (Earth and Planetary Science Letters, 2023)

Advancing best practices for assessing trends of ocean acidification time series - Adrienne J. Sutton; Roman Battisti; Brendan Carter; Wiley Evans; Jan Newton; Simone Alin; Nicholas R. Bates; Wei-Jun Cai; Kim Currie; Richard A. Feely; Christopher Sabine; Toste Tanhua; et al. (Frontiers in Marine Science, 2022)
Assessing the status of ocean acidification across ocean and coastal waters requires standardized procedures at all levels of data collection, dissemination, and analysis. Standardized procedures for assuring quality and accessibility of ocean carbonate chemistry data are largely established, but a common set of best practices for ocean acidification trend analysis is needed to enable global time series comparisons, establish accurate records of change, and communicate the current status of ocean acidification within and outside the scientific community. Here we expand upon several published trend analysis techniques and package them into a set of best practices for assessing trends of ocean acidification time series. These best practices are best suited for time series capable of characterizing seasonal variability, typically those with sub-seasonal (ideally monthly or more frequent) data collection. Given ocean carbonate chemistry time series tend to be sparse and discontinuous, additional research is necessary to further advance these best practices to better address uncharacterized variability that can result from data discontinuities. This package of best practices and the associated open-source software for computing and reporting trends is aimed at helping expand the community of practice in ocean acidification trend analysis. A broad community of practice testing these and new techniques across different data sets will result in improvements and expansion of these best practices in the future.

A new arsenal of polyphenols to make Parkinson's disease extinct: HPLC-MS/MS profiling, very interesting MAO-B inhibitory activity and antioxidant activity of Otostegia fruticosa - Somaia A. Al-Madhagy; Sameh S. Gad; Eman S. Mostafa; Simone Angeloni; Muhammed A. Saad; Omar M. Sabry; Giovani Caprioli; Seham S. El-Hawary (Natural Product Research, 2022)

Down a Rabbit Hole: Burrowing Behaviour and Larger Home Ranges are Related to Larger Brains in Leporids - Orlin S. Todorov; Coen Hird; Brian Kraatz; Emma Sherratt; Narelle Hill; Alexandra A. de Sousa; Simone Blomberg; Vera Weisbecker (Journal of Mammalian Evolution, 2022)
Studies on the evolution of brain size variation usually focus on large clades encompassing broad phylogenetic groups. This risks introducing ‘noise’ in the results, often obscuring effects that might be detected in less inclusive clades. Here, we focus on a sample of endocranial volumes (endocasts) of 18 species of rabbits and hares (Lagomorpha: Leporidae), which are a discrete radiation of mammals with a suitably large range of body sizes. Using 60 individuals, we test five popular hypotheses on brain size and olfactory bulb evolution in mammals. We also address the pervasive issue of missing data, using multiple phylogenetic imputations as to conserve the full sample size for all analyses. Our analyses show that home range and burrowing behaviour are the only predictors of leporid brain size variation. Litter size, which is one of the most widely reported constraints on brain size, was unexpectedly not associated with brain size. However, a constraining effect may be masked by a strong association of litter size with temperature seasonality, warranting further study. Lastly, we show that unreasonable estimations of phylogenetic signal (Pagel’s lamba) warrant additional caution when using small sample sizes, such as ours, in comparative studies.

Dismantling Parkinson’s disease with herbs: MAO-B inhibitory activity and quantification of chemical constituents using HPLC-MS/MS of Egyptian local market plants - Soha Ramadan; Manal M. Sabry; Muhammed A Saad; Simone Angeloni; Omar M. Sabry; Giovanni Caprioli; Soheir M. El Zalabani (Natural Product Research, 2022)

State of the California Current Ecosystem in 2021: Winter is coming? - Andrew R. Thompson; Eric P. Bjorkstedt; Steven J. Bograd; Jennifer L. Fisher; Elliott L. Hazen; Andrew Leising; Jarrod A. Santora; Erin V. Satterthwaite; William J. Sydeman; Michaela Alksne; Toby D. Auth; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2022)
In late 2020, models predicted that a strong La Niña would take place for the first time since 2013, and we assessed whether physical and biological indicators in 2021 were similar to past La Niñas in the California Current Ecosystem (CCE). The Pacific Decadal Oscillation and Oceanic Niño Index indeed remained negative throughout 2021; the North Pacific Gyre Oscillation Index, however, remained strongly negative. The seventh largest marine heatwave on record was unexpectedly present from April to the end of 2021; however, similar to past La Niñas, this mass of warm water mostly remained seaward of the continental shelf. As expected from past La Niñas, upwelling and chlorophyll were mostly high and sea surface temperature was low throughout the CCE; however, values were close to average south of Point Conception. Similar to past La Niñas, abundances of lipid-rich, northern copepods off Oregon increased. In northern California, unlike past La Niñas, the body size of North Pacific krill ( Euphausia pacifica ) was close to average. Predictably, overall krill abundance was above average in far northern California but, unexpectedly, below average south of Cape Mendocino. Off Oregon, similar to past La Niñas, larval abundances of three of six coastal species rose, while five of six southern/offshore taxa decreased in 2021. Off California, as expected based on 2020, Northern Anchovy ( Engraulis mordax ) were very abundant, while Pacific Sardine ( Sardinops sagax ) were low. Similar to past La Niñas, market squid ( Doryteuthis opalescens ) and young of the year (YOY) Pacific Hake ( Merluccius pacificus ), YOY sanddabs ( Citharichthys spp.), and YOY rockfishes ( Sebastes spp.) increased. Southern mesopelagic (e.g., Panama lightfish Vinciguerria lucetia , Mexican lampfish Triphoturus mexicanus ) larvae decreased as expected but were still well above average, while northern mesopelagic (e.g., northern lampfish Stenobrachius leucopsarus ) larvae increased but were still below average. In line with predictions, most monitored bird species had above-average reproduction in Oregon and California. California sea lion ( Zalophus californianus ) pup count, growth, and weight were high given the abundant Anchovy forage. The CCE entered an enduring La Niña in 2021, and assessing the responses of various ecosystem components helped articulate aspects of the system that are well understood and those that need further study.

Sr Isotope Ratios (87Sr/86Sr) in Water and Fish Otoliths as Estuarine Salinity Tracers: Case Studies from Three NW African Rivers - Sebastian N. Höpker; Henry C. Wu; Friedrich Lucassen; Oumar Sadio; Timothée Brochier; Ishmael Y. Nuworkpor; Simone A. Kasemann; Peter Merschel; Hildegard Westphal (Estuaries and Coasts, 2022)
Variations of strontium isotope ratios ( 87 Sr/ 86 Sr) in river systems are increasingly utilised to geochemically trace origin and movement patterns of migratory fish species. Accretionary calcified structures, such as otoliths, preserve 87 Sr/ 86 Sr signatures of the surrounding water during a fish’s lifetime. In this study, we present 87 Sr/ 86 Sr measurements of water samples and catfish otoliths collected in the estuaries of the Sine-Saloum (Senegal), the Gambia River (The Gambia), and the Volta River (Ghana) to assess their systematics and relationships with salinity. The three rivers possess distinct hydrological properties resulting in variable degrees of correlations between 87 Sr/ 86 Sr and salinity. The Gambia River ( 87 Sr/ 86 Sr of ~ 0.71209) proved exceptionally preconditioned for the approach due to well-defined geochemical end-members, allowing for quantitative estimates of salinity based on otolith 87 Sr/ 86 Sr measurements. The Volta River (~ 0.71392) presents a more complex case due the possible influence of multiple water sources to the main channel, while the inverse salinity gradient and excessive evaporation in the Sine-Saloum estuary (~0.70915) impede any significant correlations between 87 Sr/ 86 Sr and salinity. Bulk otolith 87 Sr/ 86 Sr values in the Gambia River and Volta River clearly depicted a mixed influence of seawater and riverine compositions, strongly encouraging the application of this approach for geochemical fingerprinting of critical NW African species.

Mendelian nightmares: the germline-restricted chromosome of songbirds - Pavel Borodin; Augustin Chen; Wolfgang Forstmeier; Simone Fouché; Lyubov Malinovskaya; Yifan Pei; Radka Reifová; Francisco J. Ruiz-Ruano; Stephen A. Schlebusch; Manuelita Sotelo-Muñoz; Anna Torgasheva; Niki Vontzou; et al. (Chromosome Research, 2022)
Germline-restricted chromosomes (GRCs) are accessory chromosomes that occur only in germ cells. They are eliminated from somatic cells through programmed DNA elimination during embryo development. GRCs have been observed in several unrelated animal taxa and show peculiar modes of non-Mendelian inheritance and within-individual elimination. Recent cytogenetic and phylogenomic evidence suggests that a GRC is present across the species-rich songbirds, but absent in non-passerine birds, implying that over half of all 10,500 bird species have extensive germline/soma genome differences. Here, we review recent insights gained from genomic, transcriptomic, and cytogenetic approaches with regard to the genetic content, phylogenetic distribution, and inheritance of the songbird GRC. While many questions remain unsolved in terms of GRC inheritance, elimination, and function, we discuss plausible scenarios and future directions for understanding this widespread form of programmed DNA elimination.

Analysis of the isolation valve system in water distribution networks using the segment graph - A. Simone; C. Di Cristo; O. Giustolisi (Water Resources Management, 2022)
The mechanical reliability of Water Distribution Networks (WDNs) is a relevant technical and scientific issue. During planned maintenance or unplanned interruptions, the affected area must be isolated by valves shutdown. This operation involves the alteration of the network structure, i.e., the domain of the hydraulic system, and for this reason the isolation valve system plays a central role. Some studies started to consider the presence of the isolation valve system in WDNs reliability analysis. Accordingly, this work uses the Complex Network Theory to analyse the isolation valve system performance and to assess the importance of the segments generated by valves shutdown. Differently from the classic complex network theory approach, in this work the recently proposed WDN-relevance-based betweenness centrality is applied to the segment graph to introduce information about the relevance of the different elements into the network, considering geometric and hydraulic parameters, such as length, demand, risk of disconnection, etc. The proposed strategy also suggests an improvement in the representation of the segment graph with respect to the presence of parallel edges. The strategy is presented using a small network, while it is demonstrated and discussed using a real WDN. The results indicate that the WDN-relevance-based betweenness centrality allows to effectively assess the importance of the segments generated by valves shutdowns, also providing indications to improve the isolation valve system design.

Could different aqueous humor and plasma cytokine profiles help differentiate between ocular sarcoidosis and ocular tuberculosis? - L. De Simone; M. Bonacini; R. Aldigeri; F. Alessandrello; V. Mastrofilippo; F. Gozzi; E. Bolletta; C. Adani; A. Zerbini; G. M. Cavallini; L. Fontana; C. Salvarani; et al. (Inflammation Research, 2022)

Correction to: Prevalence and patient‑rated relevance of complexity factors in medication regimens of community dwelling patients with polypharmacy - Viktoria S. Wurmbach; Steffen J. Schmidt; Anette Lampert; Simone Bernard; Andreas D. Meid; Eduard Frick; Michael Metzner; Stefan Wilm; Achim Mortsiefer; Bettina Bücker; Attila Altiner; Lisa Sparenberg; et al. (European Journal of Clinical Pharmacology, 2022)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Gene expression of sex steroid metabolizing enzymes and receptors in the skeletal muscle of migrant and resident subspecies of white-crowned sparrow (Zonotrichia leucophrys) - Jesse S. Krause; Trevor Watkins; Angus M. A. Reid; Jeffrey C. Cheah; Jonathan H. Pérez; Valerie R. Bishop; Marilyn Ramenofsky; John C. Wingfield; Simone L. Meddle (Oecologia, 2022)

Prevalence and patient-rated relevance of complexity factors in medication regimens of community-dwelling patients with polypharmacy - Viktoria S. Wurmbach; Steffen J. Schmidt; Anette Lampert; Simone Bernard; Andreas D. Meid; Eduard Frick; Michael Metzner; Stefan Wilm; Achim Mortsiefer; Bettina Bücker; Attila Altiner; Lisa Sparenberg; et al. (European Journal of Clinical Pharmacology, 2022)
Purpose To describe the prevalence of complexity factors in the medication regimens of community-dwelling patients with more than five drugs and to evaluate the relevance of these factors for individual patients. Methods Data were derived from the HIOPP-6 trial, a controlled study conducted in 9 general practices which evaluated an electronic tool to detect and reduce complexity of drug treatment. The prevalence of complexity factors was based on the results of the automated analysis of 139 patients’ medication data. The relevance assessment was based on the patients’ rating of each factor in an interview (48 patients included for analysis). Results A median of 5 (range 0–21) complexity factors per medication regimen were detected and at least one factor was observed in 131 of 139 patients. Almost half of these patients found no complexity factor in their medication regimen relevant. Conclusion In most medication regimens, complexity factors could be identified automatically, yet less than 15% of factors were indeed relevant for patients as judged by themselves. When assessing complexity of medication regimens, one should especially consider factors that are both particularly frequent and often challenging for patients, such as use of inhalers or tablet splitting. Trial registration The HIOPP-6 trial was registered retrospectively on May 17, 2021, in the German Clinical Trials register under DRKS-ID DRKS00025257.

Egg microbiota is the starting point of hatchling gut microbiota in the endangered yellow‐spotted Amazon river turtle - Ana Sofia Carranco; David Romo; Maria de Lourdes Torres; Kerstin Wilhelm; Simone Sommer; Mark A. F. Gillingham (Molecular Ecology, 2022)
Establishment and development of gut microbiota during vertebrates' early life are likely to be important predictors of health and fitness. Host‐parental and host‐environment interactions are essential to these processes. In oviparous reptiles whose nests represent a source of the parent's microbial inocula, the relative role of host‐selection and stochastic environmental factors during gut microbial assemblage remains unknown. We sampled eggs incubated in artificial nests as well as hatchlings and juveniles (up to 30 days old) of the yellow‐spotted Amazon river turtle ( Podocnemis unifilis ) developing in tubs filled with river water. We examined the relative role of the internal egg microbiota and the abiotic environment on hatchling and juvenile turtle's cloacal microbiota assemblages during the first 30 days of development. A mean of 71% of ASVs in hatched eggs could be traced to the nest environmental microbiota and in turn a mean of 77% of hatchlings' cloacal ASVs were traced to hatched eggs. Between day 5 and 20 of juvenile turtle's development, the river water environment plays a key role in the establishment of the gut microbiota (accounting for a mean of 13%–34.6% of cloacal ASVs) and strongly influences shifts in microbial diversity and abundance. After day 20, shifts in gut microbiota composition were mainly driven by host‐selection processes. Therefore, colonization by environmental microbiota is key in the initial stages of establishing the host's gut microbiota which is subsequently shaped by host‐selection processes. Our study provides a novel quantitative understanding of the host‐environment interactions during gut microbial assemblage of oviparous reptiles.

Antarctic Strain of Rhodotorula mucilaginosa UFMGCB 18,377 Attenuates Mucositis Induced by 5-Fluorouracil in Mice - Joana O. P. A. Coutinho; Mônica F. Quintanilha; Marina R. A. Campos; Enio Ferreira; Graciéle C. A. de Menezes; Luiz H. Rosa; Carlos A. Rosa; Katia D. Vital; Simone O. A. Fernandes; Valbert N. Cardoso; Jacques R. Nicoli; Fabiana C. P. Tiago; et al. (Probiotics and Antimicrobial Proteins, 2022)

Changes in sea ice and range expansion of sperm whales in the eclipse sound region of Baffin Bay, Canada - Natalie Posdaljian; Caroline Soderstjerna; Joshua M. Jones; Alba Solsona‐Berga; John A. Hildebrand; Kristin Westdal; Alex Ootoowak; Simone Baumann‐Pickering (Global Change Biology, 2022)
Sperm whales ( Physeter macrocephalus ) are a cosmopolitan species but are only found in ice‐free regions of the ocean. It is unknown how their distribution might change in regions undergoing rapid loss of sea ice and ocean warming like Baffin Bay in the eastern Canadian Arctic. In 2014 and 2018, sperm whales were sighted near Eclipse Sound, Baffin Bay: the first recorded uses of this region by sperm whales. In this study, we investigate the spatiotemporal distribution of sperm whales near Eclipse Sound using visual and acoustic data. We combine several published open‐source, data sets to create a map of historical sperm whale presence in the region. We use passive acoustic data from two recording sites between 2015 and 2019 to investigate more recent presence in the region. We also analyze regional trends in sea ice concentration (SIC) dating back to 1901 and relate acoustic presence of sperm whales to the mean SIC near the recording sites. We found no records of sperm whale sightings near Eclipse Sound outside of the 2014/2018 observations. Our acoustic data told a different story, with sperm whales recorded yearly from 2015 to 2019 with presence in the late summer and fall months. Sperm whale acoustic presence increased over the 5‐year study duration and was closely related to the minimum SIC each year. Sperm whales, like other cetaceans, are ecosystem sentinels, or indicators of ecosystem change. Increasing number of days with sperm whale presence in the Eclipse Sound region could indicate range expansion of sperm whales as a result of changes in sea ice. Monitoring climate change‐induced range expansion in this region is important to understand how increasing presence of a top‐predator might impact the Arctic food web.

Local drivers of heterogeneity in a tropical forest: epiphytic tank bromeliads affect the availability of soil resources and conditions and indirectly affect the structure of seedling communities - Tháles A. Pereira; Simone A. Vieira; Rafael S. Oliveira; Pablo A. P. Antiqueira; Gustavo H. Migliorini; Gustavo Q. Romero (Oecologia, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Oxepinamides L and M, two new oxepine-pyrimidinone-ketopiperazine type nonribosomal peptides from Aspergillus californicus - Yaojie Guo; Simone Ghidinelli; Mercedes de la Cruz; Thomas A. Mackenzie; Maria C. Ramos; Pilar Sánchez; Francisca Vicente; Olga Genilloud; Thomas O. Larsen (Natural Product Research, 2022)

The Effects of a Male Audience on Male and Female Mating Behaviour in the Blood-Sucking Bug Rhodnius prolixus - Gabriel A. De Simone; Lorena Pompilio; Gabriel Manrique (Neotropical Entomology, 2022)

Mice lacking growth-associated protein 43 develop cardiac remodeling and hypertrophy - Michele Bevere; Caterina Morabito; Simone Guarnieri; Maria A. Mariggiò (Histochemistry and Cell Biology, 2022)
Growth-associated protein 43 (GAP43) is found in skeletal muscle, localized near the calcium release units. In interaction with calmodulin (CaM), it indirectly modulates the activity of dihydropyridine and ryanodine Ca 2+ channels. GAP43–CaM interaction plays a key role in intracellular Ca 2+ homeostasis and, consequently, in skeletal muscle activity. The control of intracellular Ca 2+ signaling is also an important functional requisite in cardiac physiology. The aim of this study is to define the impact of GAP43 on cardiac tissue at macroscopic and cellular levels, using GAP43 knockout (GAP43 −/− ) newborn C57/BL6 mice. Hearts from newborn GAP43 −/− mice were heavier than hearts from wild-type (WT) ones. In these GAP43 −/− hearts, histological section analyses revealed a thicker ventricular wall and interventricular septum with a reduced ventricular chamber area. In addition, increased collagen deposits between fibers and increased expression levels of myosin were observed in hearts from GAP43 −/− mice. Cardiac tropism and rhythm are controlled by multiple intrinsic and extrinsic factors, including cellular events such those linked to intracellular Ca 2+ dynamics, in which GAP43 plays a role. Our data revealed that, in the absence of GAP43, there were cardiac morphological alterations and signs of hypertrophy, suggesting that GAP43 could play a role in the functional processes of the whole cardiac muscle. This paves the way for further studies investigating GAP43 involvement in signaling dynamics at the cellular level.

Corrigendum: State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2022)

Distinct Effects of the Hippocampal Transplantation of Neural and Mesenchymal Stem Cells in a Transgenic Model of Alzheimer’s Disease - Henrique C. Campos; Deidiane Elisa Ribeiro; Debora Hashiguchi; Deborah Y. Hukuda; Christiane Gimenes; Simone A. A. Romariz; Qing Ye; Yong Tang; Henning Ulrich; Beatriz Monteiro Longo (Stem Cell Reviews and Reports, 2022)

Sucrose intake by rats affected by both intraperitoneal oxytocin administration and time of day - Simone Rehn; Joel S. Raymond; Robert A. Boakes; Michael T. Bowen (Psychopharmacology, 2022)

Lithium and Sr isotopic composition of salar deposits in the Central Andes across space and time: the Salar de Pozuelos, Argentina - Anette Meixner; Ricardo N. Alonso; Friedrich Lucassen; Laura Korte; Simone A. Kasemann (Mineralium Deposita, 2022)
The Central Andes of South America host the largest known lithium resources in a confined area, but the primary lithium sources of the salar deposits and the mobilisation process of lithium are still a matter of speculation. Chemical weathering at or near the surface and leaching in hydrothermal systems of the active magmatic arc are considered the two main mechanisms of Li extraction from the source rock. The lithium and strontium isotope composition of typical salar deposits offer insights into the processes on how Li brine deposits in Andean evaporites are formed. Data from the Salar de Pozuelos indicate near-surface chemical weathering in a cold and dry climate as the dominant mobilisation process of Li, with evaporation being responsible for the enrichment. The Cenozoic ignimbrites are the favoured source rock for the Li, with subordinate additions from the Palaeozoic basement. The identification of the source rocks is supported by radiogenic Nd and Pb and stable B isotope data from salar deposits. A comparison with other Li brine and salt deposits in the Altiplano-Puna Plateau and its western foothills places the Salar de Pozuelos as an endmember of Li solubilisation by chemical weathering with only minor hydrothermal mobilisation of Li.

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Best Practice Data Standards for Discrete Chemical Oceanographic Observations - Li-Qing Jiang; Denis Pierrot; Rik Wanninkhof; Richard A. Feely; Bronte Tilbrook; Simone Alin; Leticia Barbero; Robert H. Byrne; Brendan R. Carter; Andrew G. Dickson; Jean-Pierre Gattuso; Dana Greeley; et al. (Frontiers in Marine Science, 2022)
Effective data management plays a key role in oceanographic research as cruise-based data, collected from different laboratories and expeditions, are commonly compiled to investigate regional to global oceanographic processes. Here we describe new and updated best practice data standards for discrete chemical oceanographic observations, specifically those dealing with column header abbreviations, quality control flags, missing value indicators, and standardized calculation of certain properties. These data standards have been developed with the goals of improving the current practices of the scientific community and promoting their international usage. These guidelines are intended to standardize data files for data sharing and submission into permanent archives. They will facilitate future quality control and synthesis efforts and lead to better data interpretation. In turn, this will promote research in ocean biogeochemistry, such as studies of carbon cycling and ocean acidification, on regional to global scales. These best practice standards are not mandatory. Agencies, institutes, universities, or research vessels can continue using different data standards if it is important for them to maintain historical consistency. However, it is hoped that they will be adopted as widely as possible to facilitate consistency and to achieve the goals stated above.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Freshwater systems and ecosystem services: Challenges and chances for cross-fertilization of disciplines - Ágnes Vári; Simone A. Podschun; Tibor Erős; Thomas Hein; Beáta Pataki; Ioan-Cristian Iojă; Cristian Mihai Adamescu; Almut Gerhardt; Tamás Gruber; Anita Dedić; Miloš Ćirić; Bojan Gavrilović; et al. (Ambio, 2022)
Freshwater ecosystems are among the most threatened in the world, while providing numerous essential ecosystem services (ES) to humans. Despite their importance, research on freshwater ecosystem services is limited. Here, we examine how freshwater studies could help to advance ES research and vice versa. We summarize major knowledge gaps and suggest solutions focusing on science and policy in Europe. We found several features that are unique to freshwater ecosystems, but often disregarded in ES assessments. Insufficient transfer of knowledge towards stakeholders is also problematic. Knowledge transfer and implementation seems to be less effective towards South-east Europe. Focusing on the strengths of freshwater research regarding connectivity, across borders, involving multiple actors can help to improve ES research towards a more dynamic, landscape-level approach, which we believe can boost the implementation of the ES concept in freshwater policies. Bridging these gaps can contribute to achieve the ambitious targets of the EU’s Green Deal.

A semi-automated, high throughput approach for O-glycosylation profiling of in vitro established cancer cell lines by MALDI-FT-ICR MS - Maximilianos Kotsias; Katarina Madunić; Simone Nicolardi; Radoslaw P. Kozak; Richard A. Gardner; Bas C. Jansen; Daniel I. R. Spencer; Manfred Wuhrer (Glycoconjugate Journal, 2021)
The study of protein O -glycosylation is important in biological research as O -glycans have been reported to regulate a multitude of molecular and cell biology processes occurring in cancer. It is known that alterations in O -glycosylation are involved in the development and progression of cancer. Their easy accessibility makes in vitro established cell lines suitable and useful models for studying biological mechanisms in disease. However, the O -glycosylation analysis of large numbers of samples, as required in systems biology and biomarker discovery studies, is often challenging. In the present study, O -glycans from three human colorectal cancer cell lines and two human pancreatic cancer cell lines were released by semi-automated, high throughput reductive β-elimination and analysed using ultrahigh resolution MALDI-FT-ICR MS. Automated data integration and processing was performed using MassyTools, where the analyte was automatically included for relative quantitation based on a range of selection criteria including signal-to-noise ratio, mass error and isotopic pattern quality scores. A total of 126 O -glycan compositions, ranging from a single monosaccharide to large oligosaccharides exhibiting complex glycan motifs, were detected. The use of ultrahigh resolution MALDI-FTICR MS enabled glycan identification and quantitation in the matrix region of the spectrum. This approach has the potential to be used for O -glycosylation analysis of large numbers of samples, such as patient sample cohorts.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Characterizing the Long-Term, Wide-Band and Deep-Water Soundscape Off Hawai’i - Karlina Merkens; Simone Baumann-Pickering; Morgan A. Ziegenhorn; Jennifer S. Trickey; Ann N. Allen; Erin M. Oleson (Frontiers in Marine Science, 2021)
Many animals use sound for communication, navigation, and foraging, particularly in deep water or at night when light is limited, so describing the soundscape is essential for understanding, protecting, and managing these species and their environments. The nearshore deep-water acoustic environment off the coast of Kona, Hawai’i, is not well documented but is expected to be strongly influenced by anthropogenic activities such as fishing, tourism, and other vessel activity. To characterize the deep-water soundscape in this area we used High-frequency Acoustic Recording Packages (HARPs) to record acoustic data year-round at a 200 or 320 kHz sampling rate. We analyzed data spanning more than 10 years (2007-2018) by producing measurements of frequency-specific energy and using a suite of detectors and classifiers for general and specific sound sources. This provided a time series for sounds coming from biological, anthropogenic and physical sources. The soundscape in this location is dominated by signals generated by humans and odontocete cetaceans (mostly delphinids), generally alternating on a diel cycle. During daylight hours the dominant sound sources are vessels and echosounders, with strong signals ranging from 10 Hz to 80 kHz and above, while during the night the clicks from odontocetes dominate the soundscape in mid-to-high frequencies, generally between 10 and 90 kHz. Winter-resident humpback whales are present seasonally and produce calls in lower frequencies (200-2,000 Hz). Overall, seasonal variability is relatively subtle, which is unsurprising given the tropical latitude and deep-water environment. These results, and particularly the inclusion of sounds from frequencies above 2 kHz, represent the first long-term analysis of a marine soundscape in the North Pacific, and the first assessment of the intense, daily presence of manmade noise at this site. The decadal time series allows us to characterize the dynamic nature of this location, and to begin to identify changes in the soundscape over time. This type of analysis facilitates protection of natural resources and effective management of human activities in an ecologically important area.

Phenotypic plasticity masks range‐wide genetic differentiation for vegetative but not reproductive traits in a short‐lived plant - Jesus Villellas; Johan Ehrlén; Elizabeth E. Crone; Anna Mária Csergő; Maria B. Garcia; Anna‐Liisa Laine; Deborah A. Roach; Roberto Salguero‐Gómez; Glenda M. Wardle; Dylan Z. Childs; Bret D. Elderd; Alain Finn; et al. (Ecology Letters, 2021)
Genetic differentiation and phenotypic plasticity jointly shape intraspecific trait variation, but their roles differ among traits. In short‐lived plants, reproductive traits may be more genetically determined due to their impact on fitness, whereas vegetative traits may show higher plasticity to buffer short‐term perturbations. Combining a multi‐treatment greenhouse experiment with observational field data throughout the range of a widespread short‐lived herb, Plantago lanceolata , we (1) disentangled genetic and plastic responses of functional traits to a set of environmental drivers and (2) assessed how genetic differentiation and plasticity shape observational trait–environment relationships. Reproductive traits showed distinct genetic differentiation that largely determined observational patterns, but only when correcting traits for differences in biomass. Vegetative traits showed higher plasticity and opposite genetic and plastic responses, masking the genetic component underlying field‐observed trait variation. Our study suggests that genetic differentiation may be inferred from observational data only for the traits most closely related to fitness.

Large‐scale drivers of relationships between soil microbial properties and organic carbon across Europe - Linnea C. Smith; Alberto Orgiazzi; Nico Eisenhauer; Simone Cesarz; Alfred Lochner; Arwyn Jones; Felipe Bastida; Guillaume Patoine; Thomas Reitz; François Buscot; Matthias C. Rillig; Anna Heintz‐Buschart; et al. (Global Ecology and Biogeography, 2021)
Aim Quantify direct and indirect relationships between soil microbial community properties (potential basal respiration, microbial biomass) and abiotic factors (soil, climate) in three major land‐cover types. Location Europe. Time period 2018. Major taxa studied Microbial community (fungi and bacteria). Methods We collected 881 soil samples from across Europe in the framework of the Land Use/Land Cover Area Frame Survey (LUCAS). We measured potential soil basal respiration at 20 ºC and microbial biomass (substrate‐induced respiration) using an O 2 ‐microcompensation apparatus. Soil and climate data were obtained from the same LUCAS survey and online databases. Structural equation models (SEMs) were used to quantify relationships between variables, and equations extracted from SEMs were used to create predictive maps. Fatty acid methyl esters were measured in a subset of samples to distinguish fungal from bacterial biomass. Results Soil microbial properties in croplands were more heavily affected by climate variables than those in forests. Potential soil basal respiration and microbial biomass were correlated in forests but decoupled in grasslands and croplands, where microbial biomass depended on soil carbon. Forests had a higher ratio of fungi to bacteria than grasslands or croplands. Main conclusions Soil microbial communities in grasslands and croplands are likely carbon‐limited in comparison with those in forests, and forests have a higher dominance of fungi indicating differences in microbial community composition. Notably, the often already‐degraded soils of croplands could be more vulnerable to climate change than more natural soils. The provided maps show potentially vulnerable areas that should be explicitly accounted for in future management plans to protect soil carbon and slow the increasing vulnerability of European soils to climate change.

Advancing the Interpretation of Shallow Water Marine Soundscapes - Megan F. McKenna; Simone Baumann-Pickering; Annebelle C. M. Kok; William K. Oestreich; Jeffrey D. Adams; Jack Barkowski; Kurt M. Fristrup; Jeremy A. Goldbogen; John Joseph; Ella B. Kim; Anke Kügler; Marc O. Lammers; et al. (Frontiers in Marine Science, 2021)
Soundscapes offer rich descriptions of composite acoustic environments. Characterizing marine soundscapes simply through sound levels results in incomplete descriptions, limits the understanding of unique features, and impedes meaningful comparisons. Sources that contribute to sound level metrics shift in time and space with changes in biological patterns, physical forces, and human activity. The presence of a constant or chronic source is often interwoven with episodic sounds. Further, the presence and intensity of sources can influence other sources, calling for a more integrated approach to characterizing soundscapes. Here, we illustrate this complexity using data from a national-scale effort, the Sanctuary Soundscape Monitoring Project (SanctSound), an initiative designed to support collection of biological, environmental, and human use data to compliment the interpretation of sound level measurements. Using nine examples from this diverse dataset we demonstrate the benefit of integrating source identification and site features to interpret sound levels across a diversity of shallow water marine soundscapes (<150 m). Sound levels from sites in high human use areas reflect the anthropogenic influences on the soundscape, especially when measuring broad frequency bands, whereas sites with relatively low human activity and high sound levels reveal biological features of the soundscape. At sites with large tidal changes, sound levels correlated with the magnitude of tidal flow, and sound levels during high tidal flow periods were similar to sound levels at sites near commercial shipping lanes. At sites in relatively close proximity (<30 km), sound levels diverge because of the presence of different proximate sound contributors and propagation features of the site. A review of emerging methodologies for integrated soundscape analysis, including acoustic scenes, provides a framework for interpreting soundscapes across a variety of conditions. With a global growth in monitoring efforts collecting standardized measurements over widely distributed arrays, more integrated methods are needed to advance the utility of soundscapes in marine resource management.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2021)
The California Current System (CCS) has experienced large fluctuations in environmental conditions in recent years that have dramatically affected the biological community. Here we synthesize remotely sensed, hydrographic, and biological survey data from throughout the CCS in 2019–2020 to evaluate how recent changes in environmental conditions have affected community dynamics at multiple trophic levels. A marine heatwave formed in the north Pacific in 2019 and reached the second greatest area ever recorded by the end of summer 2020. However, high atmospheric pressure in early 2020 drove relatively strong Ekman-driven coastal upwelling in the northern portion of the CCS and warm temperature anomalies remained far offshore. Upwelling and cooler temperatures in the northern CCS created relatively productive conditions in which the biomass of lipid-rich copepod species increased, adult krill size increased, and several seabird species experienced positive reproductive success. Despite these conditions, the composition of the fish community in the northern CCS remained a mixture of both warm- and cool-water-associated species. In the southern CCS, ocean temperatures remained above average for the seventh consecutive year. Abundances of juvenile fish species associated with productive conditions were relatively low, and the ichthyoplankton community was dominated by a mixture of oceanic warm-water and cosmopolitan species. Seabird species associated with warm water also occurred at greater densities than cool-water species in the southern CCS. The population of northern anchovy, which has been resurgent since 2017, continued to provide an important forage base for piscivorous fishes, offshore colonies of seabirds, and marine mammals throughout the CCS. Coastal upwelling in the north, and a longer-term trend in warming in the south, appeared to be controlling the community to a much greater extent than the marine heatwave itself.

Cetacean occurrence offshore of Washington from long-term passive acoustic monitoring - Ally Rice; Amanda J. Debich; Ana Širović; Erin M. Oleson; Jennifer S. Trickey; Leah M. Varga; Sean M. Wiggins; John A. Hildebrand; Simone Baumann-Pickering (Marine Biology, 2021)
A variety of cetacean species inhabit the productive waters offshore of Washington State, USA. Although the general presence of many of these species has been documented in this region, our understanding of fine-scale habitat use is limited. Here, passive acoustic monitoring was used to investigate the spatial and temporal distributions of ten cetacean species at three locations offshore of Washington. Between 2004 and 2013, a total of 2845 days of recordings were collected from sites on the continental shelf and slope, and in a submarine canyon. Acoustic presence was higher for all species at sites farther offshore. Detections were highest during the fall and winter for blue ( Balaenoptera musculus ), fin ( B. physalus ), and humpback whales ( Megaptera novaeangliae ), likely related to reproductive behavior, while minke whales ( B. acutorostrata ) were only detected on two days. Odontocetes showed temporal separation, with sperm whale ( Physeter macrocephalus ) detections highest in spring, Risso’s ( Grampus griseus ) and Pacific white-sided dolphins ( Lagenorhynchus obliquidens ) highest in summer, and Stejneger’s beaked whales ( Mesoplodon stejnegeri ), Cuvier’s beaked whales ( Ziphius cavirostris ), and the BW37V signal type highest in winter or spring. There was interannual variation in detections for most mysticete species, which may be linked to oceanographic conditions: blue and fin whale detections increased during 2007 and 2008, and fin and humpback whale detections increased in 2011. These results inform our understanding of cetacean behavior and habitat use in this region and may aid in the development of conservation strategies suited to the dynamic conditions that drive cetacean distribution.

Immunomodulatory properties of characellide A on human peripheral blood mononuclear cells - Simone Marcella; Sam Afoullouss; Olivier P. Thomas; A. Louise Allcock; Paul V. Murphy; Stefania Loffredo (Inflammopharmacology, 2021)
Marine sponges and their associated microbiota are multicellular animals known to produce metabolites with interesting pharmacological properties playing a pivotal role against a plethora of pathologic disorders such as inflammation, cancer and infections. Characellide A and B belong to a novel class of glycolipopeptides isolated from the deep sea marine sponge Characella pachastrelloides . In this study, we have evaluated the effects of characellide A and B on cytokine and chemokine release from human peripheral blood mononuclear cells (PBMC). Characellide A induces a concentration- and time-dependent CXCL8, IL-6 and TNF-α release from PBMC. This production is mediated by the induction of gene transcription. Moreover, cytokine/chemokine release induced by characellide A from PBMC is CD1d-dependent because a CD1d antagonist, 1,2-bis(diphenylphosphino)ethane [DPPE]-polyethylene glycolmonomethylether [PEG], specifically inhibits characellide A-induced activation of PBMC. In conclusion, characellide A is a novel modulator of adaptative/innate immune responses. Further studies are needed to understand its potential pharmacological application.

Removal of Imidacloprid from Water by Microalgae Nannochloropsis sp. and Its Determination by a Validated RP-HPLC Method - Telma Encarnação; Daniel Santos; Simone Ferreira; Artur J. M. Valente; J. C. Pereira; M. G. Campos; Hugh D. Burrows; Alberto A. C. C. Pais (Bulletin of Environmental Contamination and Toxicology, 2021)

Serum N-glycan profiles differ for various breast cancer subtypes - Gerda C. M. Vreeker; Kiki M. H. Vangangelt; Marco R. Bladergroen; Simone Nicolardi; Wilma E. Mesker; Manfred Wuhrer; Yuri E. M van der Burgt; Rob A. E. M. Tollenaar (Glycoconjugate Journal, 2021)
Breast cancer is the most prevalent cancer in women. Early detection of this disease improves survival and therefore population screenings, based on mammography, are performed. However, the sensitivity of this screening modality is not optimal and new screening methods, such as blood tests, are being explored. Most of the analyses that aim for early detection focus on proteins in the bloodstream. In this study, the biomarker potential of total serum N -glycosylation analysis was explored with regard to detection of breast cancer. In an age-matched case-control setup serum protein N -glycan profiles from 145 breast cancer patients were compared to those from 171 healthy individuals. N -glycans were enzymatically released, chemically derivatized to preserve linkage-specificity of sialic acids and characterized by high resolution mass spectrometry. Logistic regression analysis was used to evaluate associations of specific N -glycan structures as well as N -glycosylation traits with breast cancer. In a case-control comparison three associations were found, namely a lower level of a two triantennary glycans and a higher level of one tetraantennary glycan in cancer patients. Of note, various other N -glycomic signatures that had previously been reported were not replicated in the current cohort. It was further evaluated whether the lack of replication of breast cancer N -glycomic signatures could be partly explained by the heterogenous character of the disease since the studies performed so far were based on cohorts that included diverging subtypes in different numbers. It was found that serum N -glycan profiles differed for the various cancer subtypes that were analyzed in this study.

The role of anthropogenic habitats in freshwater mussel conservation - Ronaldo Sousa; Dariusz Halabowski; Anna M. Labecka; Karel Douda; Olga Aksenova; Yulia Bespalaya; Ivan Bolotov; Juergen Geist; Hugh A. Jones; Ekaterina Konopleva; Michael W. Klunzinger; Carlos A. Lasso; et al. (Global Change Biology, 2021)
Anthropogenic freshwater habitats may provide undervalued prospects for long‐term conservation as part of species conservation planning. This fundamental, but overlooked, issue requires attention considering the pace that humans have been altering natural freshwater ecosystems and the accelerated levels of biodiversity decline in recent decades. We compiled 709 records of freshwater mussels (Bivalvia, Unionida) inhabiting a broad variety of anthropogenic habitat types (from small ponds to large reservoirs and canals) and reviewed their importance as refuges for this faunal group. Most records came from Europe and North America, with a clear dominance of canals and reservoirs. The dataset covered 228 species, including 34 threatened species on the IUCN Red List. We discuss the conservation importance and provide guidance on how these anthropogenic habitats could be managed to provide optimal conservation value to freshwater mussels. This review also shows that some of these habitats may function as ecological traps owing to conflicting management practices or because they act as a sink for some populations. Therefore, anthropogenic habitats should not be seen as a panacea to resolve conservation problems. More information is necessary to better understand the trade‐offs between human use and the conservation of freshwater mussels (and other biota) within anthropogenic habitats, given the low number of quantitative studies and the strong biogeographic knowledge bias that persists.

Rice germ macro- and micronutrients: a new opportunity for the nutraceutics - Mariangela Rondanelli; Alessandra Miccono; Gabriella Peroni; Mara Nichetti; Vittoria Infantino; Daniele Spadaccini; Tariq A. Alalwan; Milena Anna Faliva; Simone Perna (Natural Product Research, 2021)

Cetacean occurrence in the Gulf of Alaska from long-term passive acoustic monitoring - Ally Rice; Ana Širović; Jennifer S. Trickey; Amanda J. Debich; Rachel S. Gottlieb; Sean M. Wiggins; John A. Hildebrand; Simone Baumann-Pickering (Marine Biology, 2021)
The Gulf of Alaska is an important habitat for a diverse array of marine mammals, many of which were severely depleted by historical whaling. To study current cetacean distributions in this region, passive acoustic monitoring was used to detect species-specific call types between 2011 and 2015 at five locations spanning the continental shelf, slope, and offshore seamounts. Spatial and temporal detection patterns were examined for nine species to compare differences in behavior and habitat use. Mysticetes showed seasonal increases in calling that indicated possible behavioral shifts between feeding and breeding in blue ( Balaenoptera musculus ), fin ( B. physalus ), and humpback ( Megaptera novaeangliae ) whales, and matched known migration timing of gray whales ( Eschrichtius robustus ). Interannual changes in blue and fin whale calling may relate to the marine heat wave that began in 2013 and lasted through the end of the monitoring period. Odontocete detections revealed unique spatial distributions, with killer whales ( Orcinus orca ) most common on the continental shelf and sperm whales ( Physeter macrocephalus ) most common on the continental slope, where detections occurred year-round. Beaked whales showed both spatial and temporal separation: Baird’s beaked whale ( Berardius bairdii ) detections were highest at Quinn Seamount in the spring, Cuvier’s ( Ziphius cavirostris ) at Pratt Seamount in winter, and Stejneger’s ( Mesoplodon stejnegeri ) on the continental slope in the fall. The year-round presence of many species highlights the ecological importance of the Gulf of Alaska and the spatiotemporal information reported here should inform future conservation efforts.

Subjective resource value affects aggressive behavior independently of resource-holding-potential and color morphs in male common wall lizard - Roberto Sacchi; Alan J. Coladonato; Mara Battaiola; Carlotta Pasquariello; Simone Buratti; Cristian Matellini; Marco Mangiacotti; Stefano Scali; Marco A. L. Zuffi (Journal of Ethology, 2021)
Game theory models predict the outcome of a dyadic contest to depend on opponents’ asymmetries in three main traits: resource-holding potential (RHP), resource value (RV) and aggressiveness. Using male common wall lizards Podarcis muralis , a polymorphic species showing three discrete morphs (white, yellow, and red), we investigated how the aggressive behavior varies according to a change in subjective RV and color morphs, while controlling for the asymmetry in RHP (using mirrors). By comparing the aggression of the same individual towards its mirror image in two different arenas (familiar = high subjective RV; novel = low subjective RV), we showed that lizard aggressive behavior was more intense and prolonged in the familiar arena than in the new one, thus supporting the occurrence of a direct relationship between motivation and aggression in this species. We also found the overall aggressiveness to differ from individual to individual, supporting the general hypothesis that aggressiveness is a trait associated with personality. By contrast, no effect of morphs was detected, ruling out the occurrence of morph specific variation in the aggressiveness. Our results highlight that an individual’s motivation and personality might be as important as RHP and RV in the resolution of animal contests.

Population structure, gene flow and relatedness of Natterer’s bats in Northern England - Simone Mordue; James Aegerter; Aileen Mill; Deborah A. Dawson; Carolina Crepaldi; Kirsten Wolff (Mammalian Biology, 2021)
There have been significant declines in population numbers of many bat species in the United Kingdom, including Natterer’s bats Myotis nattereri , over the last century, largely due to anthropogenic changes. The philopatry, which temperate-zone bats often exhibit to their natal landscapes, in combination with anthropogenic threats, can lead to fragmentation, isolation and sub-division of populations. This may result in bottlenecks and declines in genetic diversity. Multi-scaled research is required to disentangle how the variation in the physical traits of bat species (e.g. affecting flight), as well as their social and behavioural traits (e.g. community size, migration, breeding systems), may affect the genetic health of populations and provide a potential buffer against fragmentation. We used microsatellite markers to characterise the genetic diversity and population structure present in Natterer’s bat colonies to determine whether summer roosting bat colonies were spatially differentiated or part of a meta-population. Analyses of population structure and measures of genetic relatedness suggest spatially differentiated populations of bats exhibit long term site fidelity to summer roosting sites, whilst high genetic diversity at sites indicates gene exchange occurs via swarming sites. Natterer’s bats in northern England may travel greater distances to swarming sites than has been previously documented.

Oral administration of dermatan sulphate reduces venous thrombus formation in vivo: potential use as a formulation for venous thromboembolism - Simone A. Osborne; Paul P. Masci; Qianyun Sharon Du; Robyn A. Daniel; Kirthi Desilva; Luis Vitetta; Kong-Nan Zhao; Robert B. Seymour (Inflammopharmacology, 2021)

Using decision science to evaluate global biodiversity indices - Kate E. Watermeyer; Gurutzeta Guillera‐Arroita; Payal Bal; Michael J. Burgass; Lucie M. Bland; Ben Collen; Chris Hallam; Luke T. Kelly; Michael A. McCarthy; Tracey J. Regan; Simone Stevenson; Brendan A. Wintle; et al. (Conservation Biology, 2021)
Global biodiversity indices are used to measure environmental change and progress toward conservation goals, yet few indices have been evaluated comprehensively for their capacity to detect trends of interest, such as declines in threatened species or ecosystem function. Using a structured approach based on decision science, we qualitatively evaluated 9 indices commonly used to track biodiversity at global and regional scales against 5 criteria relating to objectives, design, behavior, incorporation of uncertainty, and constraints (e.g., costs and data availability). Evaluation was based on reference literature for indices available at the time of assessment. We identified 4 key gaps in indices assessed: pathways to achieving goals (means objectives) were not always clear or relevant to desired outcomes (fundamental objectives); index testing and understanding of expected behavior was often lacking; uncertainty was seldom acknowledged or accounted for; and costs of implementation were seldom considered. These gaps may render indices inadequate in certain decision‐making contexts and are problematic for indices linked with biodiversity targets and sustainability goals. Ensuring that index objectives are clear and their design is underpinned by a model of relevant processes are crucial in addressing the gaps identified by our assessment. Uptake and productive use of indices will be improved if index performance is tested rigorously and assumptions and uncertainties are clearly communicated to end users. This will increase index accuracy and value in tracking biodiversity change and supporting national and global policy decisions, such as the post‐2020 global biodiversity framework of the Convention on Biological Diversity.

Matching biodiversity indicators to policy needs - Simone L. Stevenson; Kate Watermeyer; Giovanni Caggiano; Elizabeth A. Fulton; Simon Ferrier; Emily Nicholson (Conservation Biology, 2021)
At the global scale, biodiversity indicators are typically used to monitor general trends, but are rarely implemented with specific purpose or linked directly to decision making. Some indicators are better suited to predicting future change, others are more appropriate for evaluating past actions, but this is seldom made explicit. We developed a conceptual model for assigning biodiversity indicators to appropriate functions based on a common approach used in economics. Using the model, indicators can be classified as leading (indicators that change before the subject of interest, informing preventative actions), coincident (indicators that measure the subject of interest), or lagging (indicators that change after the subject of interest has changed and thus can be used to evaluate past actions). We classified indicators based on ecological theory on biodiversity response times and management objectives in 2 case studies: global species extinction and marine ecosystem collapse. For global species extinctions, indicators of abundance (e.g., the Living Planet Index or biodiversity intactness index) were most likely to respond first, as leading indicators that inform preventative action, while extinction indicators were expected to respond slowly, acting as lagging indicators flagging the need for evaluation. For marine ecosystem collapse, indicators of direct responses to fishing were expected to be leading, while those measuring ecosystem collapse could be lagging. Classification defines an active role for indicators within the policy cycle, creates an explicit link to preventative decision‐making, and supports preventative action.

Loss of α7 nicotinic acetylcholine receptors in GABAergic neurons causes sex-dependent decreases in radial glia-like cell quantity and impairments in cognitive and social behavior - Samir A. Nacer; Ayland C. Letsinger; Simone Otto; Jemma Strauss DeFilipp; Viktoriya D. Nikolova; Natallia V. Riddick; Korey D. Stevanovic; Jesse D. Cushman; Jerrel L. Yakel (Brain Structure and Function, 2021)

Environmental Awareness Gained During a Citizen Science Project in Touristic Resorts Is Maintained After 3 Years Since Participation - Marta Meschini; Francesca Prati; Ginevra A. Simoncini; Valentina Airi; Erik Caroselli; Fiorella Prada; Chiara Marchini; Mariana Machado Toffolo; Simone Branchini; Viviana Brambilla; Claudia Covi; Stefano Goffredo (Frontiers in Marine Science, 2021)
Tourism is one of the largest economic sectors in the world. It has a positive effect on the economy of many countries, but it can also lead to negative impacts on local ecosystems. Informal environmental education through Citizen Science (CS) projects can be effective in increasing citizen environmental knowledge and awareness in the short-term. A change of awareness could bring to a behavioral change in the long-term, making tourism more sustainable. However, the long-term effects of participating in CS projects are still unknown. This is the first follow-up study concerning the effects of participating in a CS project on cognitive and psychological aspects at the basis of pro-environmental behavior. An environmental education program was developed, between 2012 and 2013, in a resort in Marsa Alam, Egypt. The study directly evaluated, through paper questionnaires, the short-term (after 1 week or 10 days) retention of knowledge and awareness of volunteers that had participated in the activities proposed by the program. After three years, participants were re-contacted via email to fill in the same questionnaire as in the short-term study, plus a new section with psychological variables. 40.5% of the re-contacted participants completed the follow-up questionnaires with a final sample size of fifty-five people for this study. Notwithstanding the limited sample size, positive trends in volunteer awareness, personal satisfaction regarding the CS project, and motivation to engage in pro-environmental behavior in the long-term were observed.

Recommendations for the Standardisation of Open Taxonomic Nomenclature for Image-Based Identifications - Tammy Horton; Leigh Marsh; Brian J. Bett; Andrew R. Gates; Daniel O. B. Jones; Noëlie M. A. Benoist; Simone Pfeifer; Erik Simon-Lledó; Jennifer M. Durden; Leen Vandepitte; Ward Appeltans (Frontiers in Marine Science, 2021)
This paper recommends best practice for the use of open nomenclature (ON) signs applicable to image-based faunal analyses. It is one of numerous initiatives to improve biodiversity data input to improve the reliability of biological datasets and their utility in informing policy and management. Image-based faunal analyses are increasingly common but have limitations in the level of taxonomic precision that can be achieved, which varies among groups and imaging methods. This is particularly critical for deep-sea studies owing to the difficulties in reaching confident species-level identifications of unknown taxa. ON signs indicate a standard level of identification and improve clarity, precision and comparability of biodiversity data. Here we provide examples of recommended usage of these terms for input to online databases and preparation of morphospecies catalogues. Because the processes of identification differ when working with physical specimens and with images of the taxa, we build upon previously provided recommendations for specific use with image-based identifications.

Evaluation of climate simulations produced with the Brazilian global atmospheric model version 1.2 - Caio A. S. Coelho; Dayana C. de Souza; Paulo Y. Kubota; Simone M. S. Costa; Layrson Menezes; Bruno S. Guimarães; Silvio N. Figueroa; José P. Bonatti; Iracema F. A. Cavalcanti; Gilvan Sampaio; Nicholas P. Klingaman; Jessica C. A. Baker (Climate Dynamics, 2021)

Experimental Assessment of a Conducting Polymer (PEDOT) and Microbial Biofilms as Deterrents and Facilitators of Macro-Biofouling: Larval Settlement of the Barnacle Notobalanus flosculus (Darwin, 1854) from Central Chile - Simone Baldanzi; Ignacio T. Vargas; Francisco Armijo; Miriam Fernández; Sergio A. Navarrete (Journal of Marine Science and Engineering, 2021)
Maritime enterprises have long sought solutions to reduce the negative consequences of the settlement and growth of marine biofouling (micro- and macro-organisms) on virtually all surfaces and materials deployed at sea. The development of biofouling control strategies requires solutions that are cost-effective and environmentally friendly. Polymer-based coatings, such as the poly (3,4-ethylenedioxythiophene) (PEDOT) and its potential applications, have blossomed over the last decade thanks to their low cost, nontoxicity, and high versatility. Here, using multiple-choice larval settlement experiments, we assessed the efficacy of PEDOT against the balanoid barnacle Notobalanus flosculus one of the most common biofouling species in Southeastern Pacific shores, and compared results against a commercially available antifouling (AF) coating, and biofilms at different stages of succession (1, 2, 4 and 8 weeks). We show that larval settlement on PEDOT-coated surfaces was similar to the settlement on AF-coated surfaces, while larvae settled abundantly on roughened acrylic and on early-to-intermediate stages of biofilm (one to four weeks old). These results are promising and suggest that PEDOT is a good candidate for fouling-resistant coating for specific applications at sea. Further studies to improve our understanding of the mechanisms of barnacle larval deterrence, as well as exposure to field conditions, are encouraged.

Diverse genomoviruses representing twenty-nine species identified associated with plants - Rafaela S. Fontenele; Philippe Roumagnac; Cécile Richet; Simona Kraberger; Daisy Stainton; Maketalena Aleamotu‘a; Denis Filloux; Pauline Bernardo; Gordon W. Harkins; James McCarthy; Lachlan S. Charles; Natalia S. Lamas; et al. (Archives of Virology, 2020)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Urban signals in high-resolution weather and climate simulations: role of urban land-surface characterisation - Denise Hertwig; Sue Grimmond; Margaret A. Hendry; Beth Saunders; Zhengda Wang; Marine Jeoffrion; Pier Luigi Vidale; Patrick C. McGuire; Sylvia I. Bohnenstengel; Helen C. Ward; Simone Kotthaus (Theoretical and Applied Climatology, 2020)
Two urban schemes within the Joint UK Land Environment Simulator (JULES) are evaluated offline against multi-year flux observations in the densely built-up city centre of London and in suburban Swindon (UK): (i) the 1-tile slab model, used in climate simulations; (ii) the 2-tile canopy model MORUSES (Met Office–Reading Urban Surface Exchange Scheme), used for numerical weather prediction over the UK. Offline, both models perform better at the suburban site, where differences between the urban schemes are less pronounced due to larger vegetation fractions. At both sites, the outgoing short- and longwave radiation is more accurately represented than the turbulent heat fluxes. The seasonal variations of model skill are large in London, where the sensible heat flux in autumn and winter is strongly under-predicted if the large city centre magnitudes of anthropogenic heat emissions are not represented. The delayed timing of the sensible heat flux in the 1-tile model in London results in large negative bias in the morning. The partitioning of the urban surface into canyon and roof in MORUSES improves this as the roof tile is modelled with a very low thermal inertia, but phase and amplitude of the grid box-averaged flux critically depend on accurate knowledge of the plan-area fractions of streets and buildings. Not representing non-urban land cover (e.g. vegetation, inland water) in London results in severely under-predicted latent heat fluxes. Control runs demonstrate that the skill of both models can be greatly improved by providing accurate land cover and morphology information and using representative anthropogenic heat emissions, which is essential if the model output is intended to inform integrated urban services.

Novel Long-Acting Drug Combination Nanoparticles Composed of Gemcitabine and Paclitaxel Enhance Localization of Both Drugs in Metastatic Breast Cancer Nodules - Jesse Yu; Qingxin Mu; Simone Perazzolo; James I Griffin; Linxi Zhu; Lisa A McConnachie; Danny D Shen; Rodney JY Ho (Pharmaceutical Research, 2020)

Putative adverse outcome pathways for female reproductive disorders to improve testing and regulation of chemicals - Hanna K. L. Johansson; Pauliina Damdimopoulou; Majorie B. M. van Duursen; Julie Boberg; Delphine Franssen; Marijke de Cock; Kersti Jääger; Magdalena Wagner; Agne Velthut-Meikas; Yuling Xie; Lisa Connolly; Pauline Lelandais; et al. (Archives of Toxicology, 2020)
Modern living challenges female reproductive health. We are witnessing a rise in reproductive disorders and drop in birth rates across the world. The reasons for these manifestations are multifaceted and most likely include continuous exposure to an ever-increasing number of chemicals. The cause–effect relationships between chemical exposure and female reproductive disorders, however, have proven problematic to determine. This has made it difficult to assess the risks chemical exposures pose to a woman’s reproductive development and function. To address this challenge, this review uses the adverse outcome pathway (AOP) concept to summarize current knowledge about how chemical exposure can affect female reproductive health. We have a special focus on effects on the ovaries, since they are essential for lifelong reproductive health in women, being the source of both oocytes and several reproductive hormones, including sex steroids. The AOP framework is widely accepted as a new tool for toxicological safety assessment that enables better use of mechanistic knowledge for regulatory purposes. AOPs equip assessors and regulators with a pragmatic network of linear cause–effect relationships, enabling the use of a wider range of test method data in chemical risk assessment and regulation. Based on current knowledge, we propose ten putative AOPs relevant for female reproductive disorders that can be further elaborated and potentially be included in the AOPwiki. This effort is an important step towards better safeguarding the reproductive health of all girls and women.

Rare earth elements (REE) in biology and medicine - P. Ascenzi; M. Bettinelli; A. Boffi; M. Botta; G. De Simone; C. Luchinat; E. Marengo; H. Mei; S. Aime (Rendiconti Lincei. Scienze Fisiche e Naturali, 2020)
This survey reports on topics that were presented at the workshop on “Challenges with Rare Earth Elements. The Periodic Table at work for new Science & Technology” hold at the Academia dei Lincei in November 2019. The herein reported materials refer to presentations dealing with studies and applications of rare earth elements (REE) in several areas of Biology and Medicine. All together they show the tremendous impact REE have in relevant fields of living systems and highlight, on one hand, the still existing knowledge gap for an in-depth understanding of their function in natural systems as well as the very important role they already have in providing innovative scientific and technological solutions in a number of bio-medical areas and in fields related to the assessment of the origin of food and on their manufacturing processes. On the basis of the to-date achievements one expects that new initiatives will bring, in a not too far future, to a dramatic increase of our understanding of the REE involvement in living organisms as well as a ramp-up in the exploitation of the peculiar properties of REE for the design of novel applications in diagnostic procedures and in the set-up of powerful medical devices. This scenario calls the governmental authorities for new responsibilities to guarantee a continuous availability of REE to industry and research labs together with providing support to activities devoted to their recovery/recycling.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Lithium concentrations and isotope signatures of Palaeozoic basement rocks and Cenozoic volcanic rocks from the Central Andean arc and back-arc - Anette Meixner; Carisa Sarchi; Friedrich Lucassen; Raúl Becchio; Pablo J. Caffe; Jan Lindsay; Martin Rosner; Simone A. Kasemann (Mineralium Deposita, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Towards a rigorous species delimitation framework for scleractinian corals based on RAD sequencing: the case study of Leptastrea from the Indo-Pacific - Roberto Arrigoni; Michael L. Berumen; Kiruthiga G. Mariappan; Pieter S. A. Beck; Ann Marie Hulver; Simone Montano; Michel Pichon; Giovanni Strona; Tullia Isotta Terraneo; Francesca Benzoni (Coral Reefs, 2020)

Moving Toward a Strategy for Addressing Climate Displacement of Marine Resources: A Proof-of-Concept - M. Cristina Mangano; Nova Mieszkowska; Brian Helmuth; Tiago Domingos; Tania Sousa; Giuseppe Baiamonte; Giuseppe Bazan; Angela Cuttitta; Fabio Fiorentino; Antonio Giacoletti; Magnus Johnson; Giuseppe D. Lucido; et al. (Frontiers in Marine Science, 2020)

Correction to: Rewiring of glucose metabolism defines trained immunity induced by oxidized low-density lipoprotein - Samuel T. Keating; Laszlo Groh; Kathrin Thiem; Siroon Bekkering; Yang Li; Vasiliki Matzaraki; Charlotte D. C. C. van der Heijden; Jelmer H. van Puffelen; Ekta Lachmandas; Trees Jansen; Marije Oosting; L. Charlotte J. de Bree; et al. (Journal of Molecular Medicine, 2020)

Rewiring of glucose metabolism defines trained immunity induced by oxidized low-density lipoprotein - Samuel T. Keating; Laszlo Groh; Kathrin Thiem; Siroon Bekkering; Yang Li; Vasiliki Matzaraki; Charlotte D. C. C. van der Heijden; Jelmer H. van Puffelen; Ekta Lachmandas; Trees Jansen; Marije Oosting; L. Charlotte J. de Bree; et al. (Journal of Molecular Medicine, 2020)
Stimulation of monocytes with microbial and non-microbial products, including oxidized low-density lipoprotein (oxLDL), induces a protracted pro-inflammatory, atherogenic phenotype sustained by metabolic and epigenetic reprogramming via a process called trained immunity . We investigated the intracellular metabolic mechanisms driving oxLDL-induced trained immunity in human primary monocytes and observed concomitant upregulation of glycolytic activity and oxygen consumption. In two separate cohorts of healthy volunteers, we assessed the impact of genetic variation in glycolytic genes on the training capacity of monocytes and found that variants mapped to glycolytic enzymes PFKFB3 and PFKP influenced trained immunity by oxLDL. Subsequent functional validation with inhibitors of glycolytic metabolism revealed dose-dependent inhibition of trained immunity in vitro. Furthermore, in vivo administration of the glucose metabolism modulator metformin abrogated the ability for human monocytes to mount a trained response to oxLDL. These findings underscore the importance of cellular metabolism for oxLDL-induced trained immunity and highlight potential immunomodulatory strategies for clinical management of atherosclerosis. Key messages Brief stimulation of monocytes to oxLDL induces a prolonged inflammatory phenotype. This is due to upregulation of glycolytic metabolism. Genetic variation in glycolytic genes modulates oxLDL-induced trained immunity. Pharmacological inhibition of glycolysis prevents trained immunity.

Individual factors increasing complexity of drug treatment—a narrative review - Steffen J. Schmidt; Viktoria S. Wurmbach; Anette Lampert; Simone Bernard; Walter E. Haefeli; Hanna M. Seidling; Petra A. Thürmann (European Journal of Clinical Pharmacology, 2020)
Purpose Complexity of drug treatment is known to be a risk factor for administration errors and nonadherence promoting higher healthcare costs, hospital admissions and increased mortality. Number of drugs and dose frequency are parameters often used to assess complexity related to the medication regimen. However, factors resulting from complex processes of care or arising from patient characteristics are only sporadically analyzed. Hence, the objective of this review is to give a comprehensive overview of relevant, patient-centered factors influencing complexity of drug treatment. Methods A purposeful literature search was performed in MEDLINE to identify potential complexity factors relating to the prescribed drug (i.e. dosage forms or other product characteristics), the specific medication regimen (i.e. dosage schemes or additional instructions), specific patient characteristics and process characteristics. Factors were included if they were associated to administration errors, nonadherence and related adverse drug events detected in community dwelling adult patients. Results Ninety-one influencing factors were identified: fourteen in “dosage forms”, five in “product characteristics”, twelve in “dosage schemes”, nine in “additional instructions”, thirty-one in “patient characteristics” and twenty in “process characteristics”. Conclusions Although the findings are limited by the non-systematic search process and the heterogeneous results, the search shows the influence of many factors on the complexity of drug treatment. However, to evaluate their relevance for individual patients, prospective studies are necessary.

Evaluation of the anti-apoptotic activity of bovine alphaherpesvirus type 5 US3 protein kinase in insect cells using a recombinant baculovirus - Alice M. Silva; Fabrício S. Morgado; Leonardo A. Silva; José R. J. Borges; Simone Perecmanis; Daniel M. P. Ardisson-Araújo; Bergmann M. Ribeiro; Fabrício S. Campos (Brazilian Journal of Microbiology, 2020)

Efficacy of a native isolate of the entomopathogenic fungus Metarhizium anisopliae against larval tick outbreaks under semifield conditions - Emily Mesquita; Allan F. Marciano; Amanda R. C. Corval; Jéssica Fiorotti; Thaís A. Corrêa; Simone Quinelato; Vânia R. E. P. Bittencourt; Patrícia S. Golo (BioControl, 2020)

Too hot to handle: Unprecedented seagrass death driven by marine heatwave in a World Heritage Area - Simone Strydom; Kathy Murray; Shaun Wilson; Bart Huntley; Michael Rule; Michael Heithaus; Cindy Bessey; Gary A. Kendrick; Derek Burkholder; Matthew W. Fraser; Katherine Zdunic (Global Change Biology, 2020)
The increased occurrence of extreme climate events, such as marine heatwaves (MHWs), has resulted in substantial ecological impacts worldwide. To date, metrics of thermal stress within marine systems have focussed on coral communities, and less is known about measuring stress relevant to other primary producers, such as seagrasses. An extreme MHW occurred across the Western Australian coastline in the austral summer of 2010–2011, exposing marine communities to summer seawater temperatures 2–5°C warmer than average. Using a combination of satellite imagery and in situ assessments, we provide detailed maps of seagrass coverage across the entire Shark Bay World Heritage Area (ca. 13,000 km 2 ) before (2002 and 2010) and after the MHW (2014 and 2016). Our temporal analysis of these maps documents the single largest loss in dense seagrass extent globally (1,310 km 2 ) following an acute disturbance. Total change in seagrass extent was spatially heterogeneous, with the most extensive declines occurring in the Western Gulf, Wooramel Bank and Faure Sill. Spatial variation in seagrass loss was best explained by a model that included an interaction between two heat stress metrics, the most substantial loss occurring when degree heating weeks (DHWm) was ≥10 and the number of days exposed to extreme sea surface temperature during the MHW (DaysOver) was ≥94. Ground truthing at 622 points indicated that change in seagrass cover was predominantly due to loss of Amphibolis antarctica rather than Posidonia australis , the other prominent seagrass at Shark Bay. As seawater temperatures continue to rise and the incidence of MHWs increase globally, this work will provide a basis for identifying areas of meadow degradation, or stability and recovery, and potential areas of resilience.

Porcine models for studying complications and organ crosstalk in diabetes mellitus - Simone Renner; Andreas Blutke; Sebastian Clauss; Cornelia A. Deeg; Elisabeth Kemter; Daphne Merkus; Rüdiger Wanke; Eckhard Wolf (Cell and Tissue Research, 2020)

Fluid–Structure Interaction Models of Bioprosthetic Heart Valve Dynamics in an Experimental Pulse Duplicator - Jae H. Lee; Alex D. Rygg; Ebrahim M. Kolahdouz; Simone Rossi; Stephen M. Retta; Nandini Duraiswamy; Lawrence N. Scotten; Brent A. Craven; Boyce E. Griffith (Annals of Biomedical Engineering, 2020)
Computer modeling and simulation is a powerful tool for assessing the performance of medical devices such as bioprosthetic heart valves (BHVs) that promises to accelerate device design and regulation. This study describes work to develop dynamic computer models of BHVs in the aortic test section of an experimental pulse-duplicator platform that is used in academia, industry, and regulatory agencies to assess BHV performance. These computational models are based on a hyperelastic finite element extension of the immersed boundary method for fluid–structure interaction (FSI). We focus on porcine tissue and bovine pericardial BHVs, which are commonly used in surgical valve replacement. We compare our numerical simulations to experimental data from two similar pulse duplicators, including a commercial ViVitro system and a custom platform related to the ViVitro pulse duplicator. Excellent agreement is demonstrated between the computational and experimental results for bulk flow rates, pressures, valve open areas, and the timing of valve opening and closure in conditions commonly used to assess BHV performance. In addition, reasonable agreement is demonstrated for quantitative measures of leaflet kinematics under these same conditions. This work represents a step towards the experimental validation of this FSI modeling platform for evaluating BHVs.

Neutralization of extracellular NAMPT (nicotinamide phosphoribosyltransferase) ameliorates experimental murine colitis - Giorgia Colombo; Nausicaa Clemente; Andrea Zito; Cristiano Bracci; Federico Simone Colombo; Sabina Sangaletti; Elena Jachetti; Davide Giuseppe Ribaldone; Gian Paolo Caviglia; Luca Pastorelli; Marco De Andrea; Samuele Naviglio; et al. (Journal of Molecular Medicine, 2020)

Tree diversity and above-ground biomass in the South America Cerrado biome and their conservation implications - Paulo S. Morandi; Beatriz Schwantes Marimon; Ben Hur Marimon-Junior; James A. Ratter; Ted R. Feldpausch; Guarino Rinaldi Colli; Cássia Beatriz Rodrigues Munhoz; Manoel Cláudio da Silva Júnior; Edson de Souza Lima; Ricardo Flores Haidar; Luzmila Arroyo; Alejandro Araujo Murakami; et al. (Biodiversity and Conservation, 2020)

Seal Bomb Noise as a Potential Threat to Monterey Bay Harbor Porpoise - Anne E. Simonis; Karin A. Forney; Shannon Rankin; John Ryan; Yanwu Zhang; Andrew DeVogelaere; John Joseph; Tetyana Margolina; Anna Krumpel; Simone Baumann-Pickering (Frontiers in Marine Science, 2020)

The Importance of Environmental Exposure History in Forecasting Dungeness Crab Megalopae Occurrence Using J-SCOPE, a High-Resolution Model for the US Pacific Northwest - Emily L. Norton; Samantha Siedlecki; Isaac C. Kaplan; Albert J. Hermann; Jennifer L. Fisher; Cheryl A. Morgan; Suzanna Officer; Casey Saenger; Simone R. Alin; Jan Newton; Nina Bednaršek; Richard A. Feely (Frontiers in Marine Science, 2020)

Keap1/Nrf2/HO-1 signaling pathway contributes to p-chlorodiphenyl diselenide antidepressant-like action in diabetic mice - Vanessa A. Zborowski; Suélen O. Heck; Marina Vencato; Simone Pinton; Luiza S. Marques; Cristina W. Nogueira (Psychopharmacology, 2020)

Climate‐driven habitat change causes evolution in Threespine Stickleback - Simone Des Roches; Michael A. Bell; Eric P. Palkovacs (Global Change Biology, 2020)
Climate change can shape evolution directly by altering abiotic conditions or indirectly by modifying habitats, yet few studies have investigated the effects of climate‐driven habitat change on contemporary evolution. We resampled populations of Threespine Stickleback ( Gasterosteus aculeatus ) along a latitudinal gradient in California bar‐built estuaries to examine their evolution in response to changing climate and habitat. We took advantage of the strong association between stickleback lateral plate phenotypes and Ectodysplasin A ( Eda ) genotypes to infer changes in allele frequencies over time. Our results show that over time the frequency of low‐plated alleles has generally increased and heterozygosity has decreased. Latitudinal patterns in stickleback plate phenotypes suggest that evolution at Eda is a response to climate‐driven habitat transformation rather than a direct consequence of climate. As climate change has reduced precipitation and increased temperature and drought, bar‐built estuaries have transitioned from lotic (flowing‐water) to lentic (still‐water) habitats, where the low‐plated allele is favoured. The low‐plated allele has achieved fixation at the driest, hottest southernmost sites, a trend that is progressing northward with climate change. Climate‐driven habitat change is therefore causing a reduction in genetic variation that may hinder future adaptation for populations facing multiple threats.

Inactivation of the dorsolateral periaqueductal gray matter impairs the promoting influence of stress on fear memory during retrieval - Marcelo Giachero; Eloisa Pavesi; Gastón Calfa; Simone C. Motta; Newton S. Canteras; Víctor A. Molina; Antonio P. Carobrez (Brain Structure and Function, 2019)

The management of the introduced grey squirrel seen through the eyes of the media - Simone Lioy; Andrea Marsan; Andrea Balduzzi; Lucas A. Wauters; Adriano Martinoli; Sandro Bertolino (Biological Invasions, 2019)

Unpacking Transient Event Dynamics in Electrophysiological Power Spectra - Andrew J. Quinn; Freek van Ede; Matthew J. Brookes; Simone G. Heideman; Magdalena Nowak; Zelekha A. Seedat; Diego Vidaurre; Catharina Zich; Anna C. Nobre; Mark W. Woolrich (Brain Topography, 2019)
Electrophysiological recordings of neuronal activity show spontaneous and task-dependent changes in their frequency-domain power spectra. These changes are conventionally interpreted as modulations in the amplitude of underlying oscillations. However, this overlooks the possibility of underlying transient spectral ‘bursts’ or events whose dynamics can map to changes in trial-average spectral power in numerous ways. Under this emerging perspective, a key challenge is to perform burst detection, i.e. to characterise single-trial transient spectral events, in a principled manner. Here, we describe how transient spectral events can be operationalised and estimated using Hidden Markov Models (HMMs). The HMM overcomes a number of the limitations of the standard amplitude-thresholding approach to burst detection; in that it is able to concurrently detect different types of bursts, each with distinct spectral content, without the need to predefine frequency bands of interest, and does so with less dependence on a priori threshold specification. We describe how the HMM can be used for burst detection and illustrate its benefits on simulated data. Finally, we apply this method to empirical data to detect multiple burst types in a task-MEG dataset, and illustrate how we can compute burst metrics, such as the task-evoked timecourse of burst duration.

Global mismatches in aboveground and belowground biodiversity - Erin K. Cameron; Inês S. Martins; Patrick Lavelle; Jérôme Mathieu; Leho Tedersoo; Mohammad Bahram; Felix Gottschall; Carlos A. Guerra; Jes Hines; Guillaume Patoine; Julia Siebert; Marten Winter; et al. (Conservation Biology, 2019)
Human activities are accelerating global biodiversity change and have resulted in severely threatened ecosystem services. A large proportion of terrestrial biodiversity is harbored by soil, but soil biodiversity has been omitted from many global biodiversity assessments and conservation actions, and understanding of global patterns of soil biodiversity remains limited. In particular, the extent to which hotspots and coldspots of aboveground and soil biodiversity overlap is not clear. We examined global patterns of these overlaps by mapping indices of aboveground (mammals, birds, amphibians, vascular plants) and soil (bacteria, fungi, macrofauna) biodiversity that we created using previously published data on species richness. Areas of mismatch between aboveground and soil biodiversity covered 27% of Earth's terrestrial surface. The temperate broadleaf and mixed forests biome had the highest proportion of grid cells with high aboveground biodiversity but low soil biodiversity, whereas the boreal and tundra biomes had intermediate soil biodiversity but low aboveground biodiversity. While more data on soil biodiversity are needed, both to cover geographic gaps and to include additional taxa, our results suggest that protecting aboveground biodiversity may not sufficiently reduce threats to soil biodiversity. Given the functional importance of soil biodiversity and the role of soils in human well‐being, soil biodiversity should be considered further in policy agendas and conservation actions by adapting management practices to sustain soil biodiversity and considering soil biodiversity when designing protected areas.

Responses of coppiced Eucalyptus to macro- and micronutrient application - José Henrique T. Rocha; Andréa V. A. Wenzel; Eduardo A. S. C. Melo; Ângela Simone Freitag Lima; Rodrigo Eiji Hakamada; Alexandre de Vicente Ferraz; José Carlos Arthur Junior; José Leonardo de Moraes Gonçalves; Gabriela Moreira; Antônio Natal Gonçalves (New Forests, 2019)

7-Chloro-4-(Phenylselanyl) Quinoline with Memory Enhancer Action in Aging Rats: Modulation of Neuroplasticity, Acetylcholinesterase Activity, and Cholesterol Levels - Anelise Barth; Ane G. Vogt; Angélica S. dos Reis; Mikaela P. Pinz; Roberta Krüger; William B. Domingues; Diego Alves; Vinicius F. Campos; Simone Pinton; Natália Paroul; Ethel A. Wilhelm; Cristiane Luchese (Molecular Neurobiology, 2019)

Optimum salinity for Nile tilapia (Oreochromis niloticus) growth and mRNA transcripts of ion-regulation, inflammatory, stress- and immune-related genes - Ahmed A. A. El-Leithy; Shaaban A. Hemeda; Walaa S. H. Abd El Naby; Abeer F. El Nahas; Seham A. H. Hassan; Simone T. Awad; Safaa I. El-Deeb; Zeinab A. Helmy (Fish Physiology and Biochemistry, 2019)

Potential of Solanum viarum Dunal in use for phytoremediation of heavy metals to mining areas, southern Brazil - Thays França Afonso; Carolina Faccio Demarco; Simone Pieniz; Flávio A. O. Camargo; Maurízio Silveira Quadro; Robson Andreazza (Environmental Science and Pollution Research, 2019)

The association between coffee consumption and bladder cancer in the bladder cancer epidemiology and nutritional determinants (BLEND) international pooled study - Evan Yi-Wen Yu; Anke Wesselius; Frits van Osch; Mariana Carla Stern; Xuejuan Jiang; Eliane Kellen; Chih-Ming Lu; Hermann Pohlabeln; Gunnar Steineck; James Marshall; Mohamed Farouk Allam; Carlo La Vecchia; et al. (Cancer Causes & Control, 2019)

A Systematic Review of How Multiple Stressors From an Extreme Event Drove Ecosystem-Wide Loss of Resilience in an Iconic Seagrass Community - Gary A. Kendrick; Robert J. Nowicki; Ylva S. Olsen; Simone Strydom; Matthew W. Fraser; Elizabeth A. Sinclair; John Statton; Renae K. Hovey; Jordan A. Thomson; Derek A. Burkholder; Kathryn M. McMahon; Kieryn Kilminster; et al. (Frontiers in Marine Science, 2019)

Global Observing Needs in the Deep Ocean - Lisa A. Levin; Brian J. Bett; Andrew R. Gates; Patrick Heimbach; Bruce M. Howe; Felix Janssen; Andrea McCurdy; Henry A. Ruhl; Paul Snelgrove; Karen I. Stocks; David Bailey; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2019)

Two epizootic Perkinsus spp. events in commercial oyster farms at Santa Catarina, Brazil - Ana C. Luz Cunha; Vitor de A. Pontinha; Maria Alcina M. de Castro; Simone Sühnel; Sthefanie C. Medeiros; Ângela M. Moura da Luz; Ricardo Harakava; Leonardo Tachibana; Danielle F. Mello; Naissa M. Danielli; Alcir L. Dafre; Aimê R. M. Magalhães; et al. (Journal of Fish Diseases, 2019)
Perkinsus spp. have been detected in various bivalve species from north‐east Brazil. Santa Catarina is a South Brasil state with the highest national oyster production. Considering the pathogenicity of some Perkinsus spp., a study was carried out to survey perkinsosis in two oyster species cultured in this State, the mangrove oyster Crassostrea gasar and the Pacific oyster Crassostrea gigas . Sampling involved eight sites along the state coast, and oyster sampling was collected during the period between January 2013 and December 2014. For the detection of Perkinsus , Ray's fluid thioglycollate medium (RFTM) and histology were used, and for the identification of the species, PCR and DNA sequencing were used. Perkinsus spp. was found by RFTM in C. gigas and C. gasar from São Francisco do Sul. This pathology was also detected in C. gasar from Balneário Barra do Sul both, by RFTM and histology. Perkinsus marinus was identified in C. gigas and C. gasar from São Francisco do Sul and Perkinsus beihaiensis in C. gasar from Balneário Barra do Sul. This is the first report of P. marinus in C. gigas from South America. Results of this preliminary study suggest that both oyster species tolerate the species of Perkinsus identified, without suffering heavy lesions.

Assessing Seasonality and Density From Passive Acoustic Monitoring of Signals Presumed to be From Pygmy and Dwarf Sperm Whales in the Gulf of Mexico - John A. Hildebrand; Kaitlin E. Frasier; Simone Baumann-Pickering; Sean M. Wiggins; Karlina P. Merkens; Lance P. Garrison; Melissa S. Soldevilla; Mark A. McDonald (Frontiers in Marine Science, 2019)

Natural products from Pluchea sagittalis act as inhibitors of photosynthesis in vitro - Ana C. Carvalho; João C. S. Lira; Thaís M. Pereira; Sebastião C. Silva; Simone Y. Simote-Silva; Fernando K. D. Oliveira; Beatriz King-Diaz; Blas Lotina-Hennsen; Thiago A. M. Veiga (Natural Product Research, 2019)

Marine CO2 Patterns in the Northern Salish Sea - Wiley Evans; Katie Pocock; Alex Hare; Carrie Weekes; Burke Hales; Jennifer Jackson; Helen Gurney-Smith; Jeremy T. Mathis; Simone R. Alin; Richard A. Feely (Frontiers in Marine Science, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Using meta‐omics of contaminated sediments to monitor changes in pathways relevant to climate regulation - Simone C. Birrer; Katherine A. Dafforn; Melanie Y. Sun; Rohan B. H. Williams; Jaimie Potts; Peter Scanes; Brendan P. Kelaher; Stuart L. Simpson; Staffan Kjelleberg; Sanjay Swarup; Peter Steinberg; Emma L. Johnston (Environmental Microbiology, 2019)
Summary Microbially mediated biogeochemical processes are crucial for climate regulation and may be disrupted by anthropogenic contaminants. To better manage contaminants, we need tools that make real‐time causal links between stressors and altered microbial functions, and the potential consequences for ecosystem services such as climate regulation. In a manipulative field experiment, we used metatranscriptomics to investigate the impact of excess organic enrichment and metal contamination on the gene expression of nitrogen and sulfur metabolisms in coastal sediments. Our gene expression data suggest that excess organic enrichment results in (i) higher transcript levels of genes involved in the production of toxic ammonia and hydrogen sulfide and (ii) lower transcript levels associated with the degradation of a greenhouse gas (nitrous oxide). However, metal contamination did not have any significant impact on gene expression. We reveal the genetic mechanisms that may lead to altered productivity and greenhouse gas production in coastal sediments due to anthropogenic contaminants. Our data highlight the applicability of metatranscriptomics as a management tool that provides an immense breadth of information and can identify potentially impacted process measurements that need further investigation.

Synthesis and evaluation of cadiolide analogues as inhibitors of bacterial biofilm formation - Simone Z. Mairink; Luiz C. A. Barbosa; John Boukouvalas; Silvia H. S. P. Pedroso; Simone G. Santos; Paula P. Magalhães; Luiz M. Farias (Medicinal Chemistry Research, 2018)

The genomic basis of adaptation to calcareous and siliceous soils in Arabidopsis lyrata - Alessia Guggisberg; Xuanyu Liu; Léonie Suter; Guilhem Mansion; Martin C. Fischer; Simone Fior; Marie Roumet; Ruben Kretzschmar; Marcus A. Koch; Alex Widmer (Molecular Ecology, 2018)
Edaphic conditions are important determinants of plant fitness. While much has been learnt in recent years about plant adaptation to heavy metal contaminated soils, the genomic basis underlying adaptation to calcareous and siliceous substrates remains largely unknown. We performed a reciprocal germination experiment and whole‐genome resequencing in natural calcareous and siliceous populations of diploid Arabidopsis lyrata to test for edaphic adaptation and detect signatures of selection at loci associated with soil‐mediated divergence. In parallel, genome scans on respective diploid ecotypes from the Arabidopsis arenosa species complex were undertaken, to search for shared patterns of adaptive genetic divergence. Soil ecotypes of A. lyrata display significant genotype‐by‐treatment responses for seed germination. Sequence (SNPs) and copy‐number variants (CNVs) point towards loci involved in ion transport as the main targets of adaptive genetic divergence. Two genes exhibiting high differentiation among soil types in A. lyrata further share trans‐specific single nucleotide polymorphisms with A. arenosa . This work applies experimental and genomic approaches to study edaphic adaptation in A. lyrata and suggests that physiological response to elemental toxicity and deficiency underlies the evolution of calcareous and siliceous ecotypes. The discovery of shared adaptive variation between sister species indicates that ancient polymorphisms contribute to adaptive evolution.

In situ phytoremediation characterization of heavy metals promoted by Hydrocotyle ranunculoides at Santa Bárbara stream, an anthropogenic polluted site in southern of Brazil - Carolina F. Demarco; Thays F. Afonso; Simone Pieniz; Maurízio S. Quadro; Flávio A. O. Camargo; Robson Andreazza (Environmental Science and Pollution Research, 2018)

Heard but not seen: Occurrence of Kogia spp. along the western North Atlantic shelf break - Lynne E. W. Hodge; Simone Baumann‐Pickering; John A. Hildebrand; Joel T. Bell; Erin W. Cummings; Heather J. Foley; Ryan J. McAlarney; William A. McLellan; D. Ann Pabst; Zachary T. Swaim; Danielle M. Waples; Andrew J. Read (Marine Mammal Science, 2018)

Ecological drivers of Hepacivirus infection in a neotropical rodent inhabiting landscapes with various degrees of human environmental change - Julian Schmid; Andrea Rasche; Georg Eibner; Lara Jeworowski; Rachel A. Page; Victor Max Corman; Christian Drosten; Simone Sommer (Oecologia, 2018)

Females’ sequential mating decisions depend on both the quality of the courting male and the quality of the potential mates in a blood-sucking bug - Gabriel A. De Simone; Gabriel Manrique; Lorena Pompilio (Behavioral Ecology and Sociobiology, 2018)

Paleolimnological records reveal biotic homogenization driven by eutrophication in tropical reservoirs - Simone Wengrat; Andre A. Padial; Erik Jeppesen; Thomas A. Davidson; Luciane Fontana; Sandra Costa-Böddeker; Denise C. Bicudo (Journal of Paleolimnology, 2018)

Effects of long-term dietary administration of estrogen receptor-beta agonist diarylpropionitrile on ovariectomized female ICR (CD-1) mice - Sherry A. Said; Rachel Isedowo; Christilynn Guerin; Navreek N. Nar; Leesa Lillie; Shawn Bukovac; Jonathan J. Simone; Matthew R. Green; Cheryl M. McCormick; Jeffrey A. Stuart (GeroScience, 2018)

Global Island Monitoring Scheme (GIMS): a proposal for the long-term coordinated survey and monitoring of native island forest biota - Paulo A. V. Borges; Pedro Cardoso; Holger Kreft; Robert J. Whittaker; Simone Fattorini; Brent C. Emerson; Artur Gil; Rosemary G. Gillespie; Thomas J. Matthews; Ana M. C. Santos; Manuel J. Steinbauer; Christophe Thébaud; et al. (Biodiversity and Conservation, 2018)

Fungal Endophyte Communities in Begonia Species from the Brazilian Atlantic Rainforest - Ana M. L. Correia; Simone P. Lira; Marco A. Assis; Andre Rodrigues (Current Microbiology, 2018)

Morphological and epigenetic variation in mussels from contrasting environments - R. G. A. Watson; Simone Baldanzi; A. Pérez-Figueroa; G. Gouws; F. Porri (Marine Biology, 2018)

Correction to: Cryptosporidium Spp. Contamination in Perna perna Mussels Destined for Human Consumption in Southeastern Rio de Janeiro, Brazil - A. L. Santos; L. T. F. de Oliveira; A. L. A. Souza; R. A. Hauser-Davis; S. G. De Simone (Bulletin of Environmental Contamination and Toxicology, 2018)

Latitudinal variation in maternal investment traits of the kelp crab Taliepus dentatus along the coast of Chile - Simone Baldanzi; Daniela Storch; Sergio A. Navarrete; Martin Graeve; Miriam Fernández (Marine Biology, 2018)

Cryptosporidium spp. Contamination in Perna perna Mussels Destined for Human Consumption in Southeastern Rio de Janeiro, Brazil - A. L. Santos; L. T. F. de Oliveira; A. L. A. Souza; R. A. Hauser-Davis; S. G. De Simone (Bulletin of Environmental Contamination and Toxicology, 2018)

Potential disease biomarkers: dipeptidyl peptidase 4 and fibroblast activation protein - Roger Yazbeck; Simone E. Jaenisch; Catherine A. Abbott (Protoplasma, 2018)

Investigation of different classifiers and channel configurations of a mobile P300-based brain–computer interface - Simone A. Ludwig; Jun Kong (Medical & Biological Engineering & Computing, 2017)

Gene networks for total number born in pigs across divergent environments - Lucas L. Verardo; Marcos S. Lopes; Pramod Mathur; Ole Madsen; Fabyano F. Silva; Martien A. M. Groenen; Egbert F. Knol; Paulo S. Lopes; Simone E. F. Guimarães (Mammalian Genome, 2017)

Transcriptional profiling by RNA sequencing of black pepper (Piper nigrum L.) roots infected by Fusarium solani f. sp. piperis - Edith C. O. Moreira; Daniel G. Pinheiro; Sheila M. C. Gordo; Simone M. Rodrigues; Elaine Pessoa; Hubert Schaller; Oriel F. de Lemos; Artur Silva; Horacio Schneider; Wilson A. Silva; Iracilda Sampaio; Sylvain Darnet (Acta Physiologiae Plantarum, 2017)

New protein sources and food legislation: the case of edible insects and EU law - Simone Belluco; A. Halloran; A. Ricci (Food Security, 2017)

Irreversible electroporation as treatment of locally advanced and as margin accentuation in borderline resectable pancreatic adenocarcinoma - P. Marsanic; A. Mellano; A. Sottile; M. De Simone (Medical & Biological Engineering & Computing, 2017)

Estimating Total Alkalinity in the Washington State Coastal Zone: Complexities and Surprising Utility for Ocean Acidification Research - Andrea J. Fassbender; Simone R. Alin; Richard A. Feely; Adrienne J. Sutton; Jan A. Newton; Robert H. Byrne (Estuaries and Coasts, 2017)

Characterization of carbon monoxide, methane and nonmethane hydrocarbons in emerging cities of Saudi Arabia and Pakistan and in Singapore - Barbara Barletta; Isobel J. Simpson; Nicola J. Blake; Simone Meinardi; Louisa K. Emmons; Omar S. Aburizaiza; Azhar Siddique; Jahan Zeb; Liya E. Yu; Haider A. Khwaja; Muhammad A. Farrukh; Donald R. Blake (Journal of Atmospheric Chemistry, 2017)

A multicenter assessment of single-cell models aligned to standard measures of cell health for prediction of acute hepatotoxicity - Rowena L. Sison-Young; Volker M. Lauschke; Esther Johann; Eliane Alexandre; Sébastien Antherieu; Hélène Aerts; Helga H. J. Gerets; Gilles Labbe; Delphine Hoët; Martina Dorau; Christopher A. Schofield; Cerys A. Lovatt; et al. (Archives of Toxicology, 2017)

Nonneurological Involvement in Late-Onset Friedreich Ataxia (LOFA): Exploring the Phenotypes - Alberto R. M. Martinez; Adriana Moro; Agessandro Abrahao; Ingrid Faber; Conrado R. Borges; Thiago J. R. Rezende; Carlos R. Martins; Mariana Moscovich; Renato P. Munhoz; Sandra Leistner Segal; Walter O. Arruda; Maria Luiza Saraiva-Pereira; et al. (The Cerebellum, 2017)

Characterization of Cinnamoyl Esterases from Different Lactobacilli and Bifidobacteria - Caroline Fritsch; André Jänsch; Matthias A. Ehrmann; Simone Toelstede; Rudi F. Vogel (Current Microbiology, 2017)

Common carp Cyprinus carpio responses to sub-chronic exposure to perfluorooctanoic acid - Luisa Giari; Fabio Vincenzi; Simone Badini; Cristiana Guerranti; Bahram S. Dezfuli; Elisa A. Fano; Giuseppe Castaldelli (Environmental Science and Pollution Research, 2016)

Changes in Menidia beryllina Gene Expression and In Vitro Hormone-Receptor Activation After Exposure to Estuarine Waters Near Treated Wastewater Outfalls - Bryan J. Cole; Susanne M. Brander; Ken M. Jeffries; Simone Hasenbein; Guochun He; Michael S. Denison; Nann A. Fangue; Richard E. Connon (Archives of Environmental Contamination and Toxicology, 2016)

Evidence for selection maintaining MHC diversity in a rodent species despite strong density fluctuations - Andrea C. Schuster; Antje Herde; Camila J. Mazzoni; Jana A. Eccard; Simone Sommer (Immunogenetics, 2016)

Antimicrobial Activity of ILTI, a Kunitz‐Type Trypsin Inhibitor from Inga laurina (SW.) Willd - Maria Lígia R. Macedo; Suzanna F. F. Ribeiro; Gabriel B. Taveira; Valdirene M. Gomes; Karina M. C. A. de Barros; Simone Maria-Neto (Current Microbiology, 2016)

Where is the best site for wave energy exploitation? Case study along the coast of northern Latium (ITALY) - Francesco Paladini de Mendoza; Simone Bonamano; Giuseppe Stella; Monica Giovacchini; Dario Capizzi; Fulvio Fraticelli; Sergio Muratore; Calogero Burgio; Sergio Scanu; Maximo A. Peviani; Marco Marcelli (Journal of Coastal Conservation, 2016)

Honey bee colonies regulate queen reproductive traits by controlling which queens survive to adulthood - D. R. Tarpy; M. Simone-Finstrom; T. A. Linksvayer (Insectes Sociaux, 2016)

Breeding on the leading edge of a northward range expansion: differences in morphology and the stress response in the arctic Gambel’s white-crowned sparrow - Jesse S. Krause; Helen E. Chmura; Jonathan H. Pérez; Lisa N. Quach; Ashley Asmus; Karen R. Word; Michaela A. McGuigan; Shannan K. Sweet; Simone L. Meddle; Laura Gough; Natalie Boelman; John C. Wingfield (Oecologia, 2016)

Seasonal differences in climate in the Chianti region of Tuscany and the relationship to vintage wine quality - Michael James Salinger; Marina Baldi; Daniele Grifoni; Greg Jones; Giorgio Bartolini; Stefano Cecchi; Gianni Messeri; Anna Dalla Marta; Simone Orlandini; Giovanni A. Dalu; Gianpiero Maracchi (International Journal of Biometeorology, 2015)

The Impact of Trampling on Reef Macrobenthos in Northeastern Brazil: How Effective are Current Conservation Strategies? - Gleice S. Santos; Douglas C. Burgos; Simone M. A. Lira; Ralf Schwamborn (Environmental Management, 2015)

Acoustic behavior of melon-headed whales varies on a diel cycle - Simone Baumann-Pickering; Marie A. Roch; Sean M. Wiggins; Hans-Ulrich Schnitzler; John A. Hildebrand (Behavioral Ecology and Sociobiology, 2015)

Early recruitment responses to interactions between frequent fires, nutrients, and herbivory in the southern Amazon - Tara Joy Massad; Jennifer K. Balch; Cândida Lahís Mews; Pábio Porto; Ben Hur Marimon Junior; Raimundo Mota Quintino; P. M. Brando; Simone A. Vieira; Susan E. Trumbore (Oecologia, 2015)

Antarctic beaked whale echolocation signals near South Scotia Ridge - Jennifer S. Trickey; Simone Baumann‐Pickering; John A. Hildebrand; Maria Vanesa Reyes Reyes; Mariana Melcón; Miguel Iñíguez (Marine Mammal Science, 2015)

Upper Palaeolithic archaeobotany of Ghar-e Boof cave, Iran: a case study in site disturbance and methodology - Jonathan A. Baines; Simone Riehl; Nicholas Conard; Mohsen Zeidi-Kulehparcheh (Archaeological and Anthropological Sciences, 2015)

Stewardship to tackle global phosphorus inefficiency: The case of Europe - Paul J. A. Withers; Kimo C. van Dijk; Tina-Simone S. Neset; Thomas Nesme; Oene Oenema; Gitte H. Rubæk; Oscar F. Schoumans; Bert Smit; Sylvain Pellerin (Ambio, 2015)

Cryptococcus vaughanmartiniae sp. nov. and Cryptococcus onofrii sp. nov.: two new species isolated from worldwide cold environments - Benedetta Turchetti; Laura Selbmann; Robert A. Blanchette; Simone Di Mauro; Elisabetta Marchegiani; Laura Zucconi; Brett E. Arenz; Pietro Buzzini (Extremophiles, 2015)

Purification and biochemical characterization of DnaK and its transcriptional activator RpoH from Neisseria gonorrhoeae - Shalini Narayanan; Simone A. Beckham; John K. Davies; Anna Roujeinikova (Molecular Biology Reports, 2014)

The hypotensive effect of the ruthenium complex [Ru(terpy)(bdq)NO]3+ is higher in male than in female spontaneously hypertensive rats (SHR) - Simone R. Potje; Mariana C. Hildebrand; Felipe C. Munhoz; Jéssica A. Troiano; Ariana A. F. Pereira; Ana Claúdia M. S. Nakamune; Roberto S. da Silva; Lusiane M. Bendhack; Cristina Antoniali (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Dissolution Testing of Hardly Soluble Materials by Surface Sensitive Techniques: Clotrimazole from an Insoluble Matrix - Heike M. A. Ehmann; Sascha Winter; Thomas Griesser; Roman Keimel; Simone Schrank; Andreas Zimmer; Oliver Werzer (Pharmaceutical Research, 2014)

Linalool and linalool complexed in β-cyclodextrin produce anti-hyperalgesic activity and increase Fos protein expression in animal model for fibromyalgia - Simone S. Nascimento; Enilton A. Camargo; Josimari M. DeSantana; Adriano A. S. Araújo; Paula P. Menezes; Waldecy Lucca-Júnior; Ricardo L. C. Albuquerque-Júnior; Leonardo R. Bonjardim; Lucindo J. Quintans-Júnior (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Origin and significance of poikilitic and mosaic peridotite xenoliths in the western Pannonian Basin: geochemical and petrological evidences - Antal Embey-Isztin; Gábor Dobosi; Jean-Louis Bodinier; Delphine Bosch; G. A. Jenner; Simone Pourtales; Olivier Bruguier (Contributions to Mineralogy and Petrology, 2014)

A diagnostic evaluation of modeled mercury wet depositions in Europe using atmospheric speciated high-resolution observations - J. Bieser; F. De Simone; C. Gencarelli; B. Geyer; I. Hedgecock; V. Matthias; O. Travnikov; A. Weigelt (Environmental Science and Pollution Research, 2014)

Early postnatal, but not late, exposure to chemical ambient pollutant 1,2-naphthoquinone increases susceptibility to pulmonary allergic inflammation at adulthood - Karen T. Santos; Juliana Florenzano; Leandro Rodrigues; Rodolfo R. Fávaro; Fernanda F. Ventura; Marcela G. Ribeiro; Simone A. Teixeira; Heloisa H. A. Ferreira; Susan D. Brain; Amílcar S. Damazo; Telma M. Zorn; Niels O. Câmara; et al. (Archives of Toxicology, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Monitoring Mercury Exposure in Reproductive Aged Women Inhabiting the Tapajós River Basin, Amazon - Tereza Cristina de Oliveira Corvelo; Érika Abdon Fiquene Oliveira; Amanda Magno de Parijós; Claudia Simone Baltazar de Oliveira; Rosane do Socorro Pompeu de Loiola; Amélia A. de Araújo; Carlos Araújo da Costa; Luiz Carlos de Lima Silveira; Maria da Conceição Nascimento Pinheiro (Bulletin of Environmental Contamination and Toxicology, 2014)

Nematode community shifts in response to experimental warming and canopy conditions are associated with plant community changes in the temperate-boreal forest ecotone - Madhav Prakash Thakur; Peter B. Reich; Nicholas A. Fisichelli; Artur Stefanski; Simone Cesarz; Tomasz Dobies; Roy L. Rich; Sarah E. Hobbie; Nico Eisenhauer (Oecologia, 2014)

In toto differentiation of human amniotic membrane towards the Schwann cell lineage - Asmita Banerjee; Sylvia Nürnberger; Simone Hennerbichler; Sabrina Riedl; Christina M. A. P. Schuh; Ara Hacobian; Andreas Teuschl; Johann Eibl; Heinz Redl; Susanne Wolbank (Cell and Tissue Banking, 2014)

Soil contaminated with chromium by tannery sludge and identified by vis-NIR-mid spectroscopy techniques - Suzana R. Araújo; José A. M. Demattê; Simone Vicente (International Journal of Remote Sensing, 2014)

Rapid estimation of potential yield for data-poor Tapes philippinarum fisheries in North Adriatic coastal lagoons - Simone Vincenzi; Giulio A. De Leo; Cristina Munari; Michele Mistri (Hydrobiologia, 2014)

Recurrent Varicella following Steroids and Fingolimod in a Multiple Sclerosis Patient - D. Ferraro; S. De Biasi; F. Vitetta; A. M. Simone; L. Federzoni; V. Borghi; A. Cossarizza; P. F. Nichelli; P. Sola (Journal of Neuroimmune Pharmacology, 2013)

A HPLC-based glycoanalytical protocol allows the use of natural O-glycans derived from glycoproteins as substrates for glycosidase discovery from microbial culture - Li Liu; Tharmala Tharmalingam; Eva Maischberger; Simone Albrecht; Mary E. Gallagher; Raúl Miranda-CasoLuengo; Wim G. Meijer; Pauline M. Rudd; Jane A. Irwin (Glycoconjugate Journal, 2013)

Disturbances, elevation, topography and spatial proximity drive vegetation patterns along an altitudinal gradient of a top biodiversity hotspot - Pedro V. Eisenlohr; Luciana F. Alves; Luís Carlos Bernacci; Maíra C. G. Padgurschi; Roseli B. Torres; Eduardo M. B. Prata; Flavio Antonio M. dos Santos; Marco Antônio Assis; Eliana Ramos; André Luís C. Rochelle; Fernando R. Martins; Mariana C. R. Campos; et al. (Biodiversity and Conservation, 2013)

Bioactives and nutraceutical phytochemicals naturally occurring in virgin olive oil. The case study of the Nocellara del Belice Italian olive cultivar - F. Ranalli; A. Ranalli; S. Contento; M. Casanovas; M. Antonucci; G. Di Simone (Natural Product Research, 2013)

Nitrate reductase is required for the transcriptional modulation and bactericidal activity of nitric oxide during the defense response of Arabidopsis thaliana against Pseudomonas syringae - Simone C. Vitor; Gustavo T. Duarte; Elzira E. Saviani; Michel G. A. Vincentz; Halley C. Oliveira; Ione Salgado (Planta, 2013)

Patterns, processes and vulnerability of Southern Ocean benthos: a decadal leap in knowledge and understanding - Stefanie Kaiser; Simone N. Brandão; Saskia Brix; David K. A. Barnes; David A. Bowden; Jeroen Ingels; Florian Leese; Stefano Schiaparelli; Claudia P. Arango; Renuka Badhe; Narissa Bax; Magdalena Blazewicz-Paszkowycz; et al. (Marine Biology, 2013)

Biosorption and Bioreduction of Copper from Different Copper Compounds in Aqueous Solution - Robson Andreazza; Benedict C. Okeke; Simone Pieniz; Fátima M. Bento; Flávio A. O. Camargo (Biological Trace Element Research, 2013)

Value-based healthcare in Lynch syndrome - Simone D. Hennink; Nandy Hofland; Jessica P. Gopie; Corinne van der Kaa; Kimberley de Koning; Maartje Nielsen; Carli Tops; Hans Morreau; Wouter H. de Vos tot Nederveen Cappel; Alexandra M. J. Langers; James C. Hardwick; Katja N. Gaarenstroom; et al. (Familial Cancer, 2013)

Interactions between repeated fire, nutrients, and insect herbivores affect the recovery of diversity in the southern Amazon - Tara Joy Massad; Jennifer K. Balch; Eric A. Davidson; Paulo M. Brando; Cândida Lahís Mews; Pábio Porto; Raimundo Mota Quintino; Simone A. Vieira; Ben Hur Marimon Junior; Susan E. Trumbore (Oecologia, 2013)

Automatic detection and segmentation of bovine corpora lutea in ultrasonographic ovarian images using genetic programming and rotation invariant local binary patterns - Meng Dong; Mark G. Eramian; Simone A. Ludwig; Roger A. Pierson (Medical & Biological Engineering & Computing, 2013)

Aleutian Islands beaked whale echolocation signals - Simone Baumann‐Pickering; Anne E. Simonis; Sean M. Wiggins; Robert L. Brownell, Jr.; John A. Hildebrand (Marine Mammal Science, 2013)

Mutualism from the inside: coordinated development of plant and insect in an active pollinating fig wasp - Sergio Jansen-González; Simone de Padua Teixeira; Rodrigo A. Santinelo Pereira (Arthropod-Plant Interactions, 2012)

A novel xylan degrading β-d-xylosidase: purification and biochemical characterization - Michele Michelin; Simone C. Peixoto-Nogueira; Tony M. Silva; João A. Jorge; Héctor F. Terenzi; José A. Teixeira; Maria de Lourdes T. M. Polizeli (World Journal of Microbiology and Biotechnology, 2012)

Tuberculosis: Finding a New Potential Antimycobacterium Derivative in a Aldehyde–Arylhydrazone–Oxoquinoline Series - Fernanda C. Santos; Helena C. Castro; Maria Cristina S. Lourenço; Paula A. Abreu; Pedro N. Batalha; Anna C. Cunha; Guilherme S. L. Carvalho; Carlos R. Rodrigues; Cid A. Medeiros; Simone D. Souza; Vitor F. Ferreira; Maria C. B. V. Souza (Current Microbiology, 2012)

Translocation of stream-dwelling salmonids in headwaters: insights from a 15-year reintroduction experience - Simone Vincenzi; Alain J. Crivelli; Dusan Jesensek; Giulio A. De Leo (Reviews in Fish Biology and Fisheries, 2012)

Goldilocks Meets Santa Rosalia: An Ephemeral Speciation Model Explains Patterns of Diversification Across Time Scales - Erica Bree Rosenblum; Brice A. J. Sarver; Joseph W. Brown; Simone Des Roches; Kayla M. Hardwick; Tyler D. Hether; Jonathan M. Eastman; Matthew W. Pennell; Luke J. Harmon (Evolutionary Biology, 2012)

Double-phase culture system for large scale production of pineapple - Jonny E. Scherwinski-Pereira; Elequisandra da C. Araruna Lima; Tatiane L. da Silva; Antonio G. Gomes Mesquita; Simone de A. Maciel; Frederico H. da Silva Costa (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Screening of Antimicrobials from Caribbean Sea Animals and Isolation of Bactericidal Proteins from the Littoral Mollusk Cenchritis muricatus - Carlos López-Abarrategui; Annia Alba; Loiane A. Lima; Simone Maria-Neto; Ilka M. Vasconcelos; Jose T. A. Oliveira; Simoni C. Dias; Anselmo J. Otero-Gonzalez; Octavio L. Franco (Current Microbiology, 2012)

Characterization of Copper-Resistant Rhizosphere Bacteria from Avena sativa and Plantago lanceolata for Copper Bioreduction and Biosorption - Robson Andreazza; Benedict C. Okeke; Simone Pieniz; Flávio A. O. Camargo (Biological Trace Element Research, 2012)

Effects of Stimulation of Copper Bioleaching on Microbial Community in Vineyard Soil and Copper Mining Waste - Robson Andreazza; Benedict C. Okeke; Simone Pieniz; Leandro Bortolon; Márcio R. Lambais; Flávio A. O. Camargo (Biological Trace Element Research, 2012)

Energy expenditure during egg laying is equal for early and late breeding free-living female great tits - Luc te Marvelde; Simone L. Webber; Harro A. J. Meijer; Marcel E. Visser (Oecologia, 2012)

The phylogeny of halichondrid demosponges: past and present re-visited with DNA-barcoding data - Dirk Erpenbeck; Kathryn Hall; Belinda Alvarez; Gabriele Büttner; Katharina Sacher; Simone Schätzle; Astrid Schuster; Sergio Vargas; John N. A. Hooper; Gert Wörheide (Organisms Diversity & Evolution, 2012)

Global assessment of experimental climate warming on tundra vegetation: heterogeneity over space and time - Sarah C. Elmendorf; Gregory H. R. Henry; Robert D. Hollister; Robert G. Björk; Anne D. Bjorkman; Terry V. Callaghan; Laura Siegwart Collier; Elisabeth J. Cooper; Johannes H. C. Cornelissen; Thomas A. Day; Anna Maria Fosaa; William A. Gould; et al. (Ecology Letters, 2012)
Ecology Letters (2011) Abstract Understanding the sensitivity of tundra vegetation to climate warming is critical to forecasting future biodiversity and vegetation feedbacks to climate. In situ warming experiments accelerate climate change on a small scale to forecast responses of local plant communities. Limitations of this approach include the apparent site‐specificity of results and uncertainty about the power of short‐term studies to anticipate longer term change. We address these issues with a synthesis of 61 experimental warming studies, of up to 20 years duration, in tundra sites worldwide. The response of plant groups to warming often differed with ambient summer temperature, soil moisture and experimental duration. Shrubs increased with warming only where ambient temperature was high, whereas graminoids increased primarily in the coldest study sites. Linear increases in effect size over time were frequently observed. There was little indication of saturating or accelerating effects, as would be predicted if negative or positive vegetation feedbacks were common. These results indicate that tundra vegetation exhibits strong regional variation in response to warming, and that in vulnerable regions, cumulative effects of long‐term warming on tundra vegetation – and associated ecosystem consequences – have the potential to be much greater than we have observed to date.

Potential Phytoextraction and Phytostabilization of Perennial Peanut on Copper-Contaminated Vineyard Soils and Copper Mining Waste - Robson Andreazza; Leandro Bortolon; Simone Pieniz; Marcelo Giacometti; Dione D. Roehrs; Mácio R. Lambais; Flávio A. O. Camargo (Biological Trace Element Research, 2011)

Bioreduction of Cu(II) by Cell-Free Copper Reductase from a Copper Resistant Pseudomonas sp. NA - Robson Andreazza; Benedict C. Okeke; Simone Pieniz; Adriano Brandelli; Mácio R. Lambais; Flávio A. O. Camargo (Biological Trace Element Research, 2011)

Pharmacokinetics and protein binding of cefazolin in morbidly obese patients - Simone van Kralingen; Margot Taks; Jeroen Diepstraten; Ewoudt M. van de Garde; Eric P. van Dongen; Marinus J. Wiezer; Bert van Ramshorst; Bart Vlaminckx; Vera H. Deneer; Catherijne A. Knibbe (European Journal of Clinical Pharmacology, 2011)

Stimulant effects of adenosine antagonists on operant behavior: differential actions of selective A2A and A1 antagonists - Patrick A. Randall; Eric J. Nunes; Simone L. Janniere; Colin M. Stopper; Andrew M. Farrar; Thomas N. Sager; Younis Baqi; Jörg Hockemeyer; Christa E. Müller; John D. Salamone (Psychopharmacology, 2011)

Slow $$ \dot{V}{\text{O}}_{2} $$ kinetics during moderate-intensity exercise as markers of lower metabolic stability and lower exercise tolerance - Bruno Grassi; Simone Porcelli; Desy Salvadego; Jerzy A. Zoladz (European Journal of Applied Physiology, 2011)

Solid Dispersions of Imidazolidinedione by PEG and PVP Polymers with Potential Antischistosomal Activities - Francimary L. Guedes; Boaz G. de Oliveira; Marcelo Z. Hernandes; Carlos A. De Simone; Francisco J. B. Veiga; Maria do Carmo A. de Lima; Ivan R. Pitta; Suely L. Galdino; Pedro José Rolim Neto (AAPS PharmSciTech, 2011)

Detection of cross-infection associated to a Brazilian PCR-ribotype of Clostridium difficile in a university hospital in Rio de Janeiro, Brazil - Ilana T. Balassiano; Joaquim dos Santos-Filho; Juliana M. Vital-Brazil; Simone A. Nouér; Claudia R. C. Souza; Jon S. Brazier; Eliane de O. Ferreira; Regina M. C. P. Domingues (Antonie van Leeuwenhoek, 2011)

Dynamics of Dissolved Forms of Carbon and Inorganic Nitrogen in Small Watersheds of the Coastal Atlantic Forest in Southeast Brazil - Tatiana M. B. Andrade; Plínio B. Camargo; Daniela M. L. Silva; Marisa C. Piccolo; Simone A. Vieira; Luciana F. Alves; Carlos A. Joly; Luiz A. Martinelli (Water, Air, & Soil Pollution, 2011)

Virulence of Brucella abortus isolated from cattle and water buffalo - Abiodun A. Adesiyun; Geoffrey T. Fosgate; Ravi Seebaransingh; Gabriel Brown; Simone Stoute; Alva Stewart-Johnson (Tropical Animal Health and Production, 2011)

Innocent until proven guilty? Stable coexistence of alien rainbow trout and native marble trout in a Slovenian stream - Simone Vincenzi; Alain J. Crivelli; Dusan Jesensek; Gianluigi Rossi; Giulio A. De Leo (The Science of Nature, 2011)

The aetiology of upper aerodigestive tract cancers among young adults in Europe: the ARCAGE study - Tatiana V. Macfarlane; Gary J. Macfarlane; Richard J. Oliver; Simone Benhamou; Christine Bouchardy; Wolfgang Ahrens; Hermann Pohlabeln; Pagona Lagiou; Areti Lagiou; Xavier Castellsague; Antonio Agudo; Franco Merletti; et al. (Cancer Causes & Control, 2010)

Future change of climate in South America in the late twenty-first century: intercomparison of scenarios from three regional climate models - Jose A. Marengo; Tercio Ambrizzi; Rosmeri P. da Rocha; Lincoln M. Alves; Santiago V. Cuadra; Maria C. Valverde; Roger R. Torres; Daniel C. Santos; Simone E. T. Ferraz (Climate Dynamics, 2010)

Experimental Validation of Modified Barton’s Model for Rock Fractures - Pooyan Asadollahi; Marco C. A. Invernizzi; Simone Addotto; Fulvio Tonon (Rock Mechanics and Rock Engineering, 2010)

Block training periodization in alpine skiing: effects of 11-day HIT on VO2max and performance - Fabio A. Breil; Simone N. Weber; Stefan Koller; Hans Hoppeler; Michael Vogt (European Journal of Applied Physiology, 2010)

Epidemiology of influenza-associated hospitalization in adults, Toronto, 2007/8 - S. P. Kuster; S. Drews; K. Green; J. Blair; I. Davis; J. Downey; R. Fowler; K. Katz; S. Lapinsky; D. McRitchie; J. Pataki; J. Powis; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Sugar and abscisic acid signaling orthologs are activated at the onset of ripening in grape - Gregory A. Gambetta; Mark A. Matthews; Tarana H. Shaghasi; Andrew J. McElrone; Simone D. Castellarin (Planta, 2010)

Saccharomyces cerevisiae strain UFMG 905 protects against bacterial translocation, preserves gut barrier integrity and stimulates the immune system in a murine intestinal obstruction model - Simone V. Generoso; Mirelle Viana; Rosana Santos; Flaviano S. Martins; José A. N. Machado; Rosa M. E. Arantes; Jacques R. Nicoli; Maria I. T. D. Correia; Valbert N. Cardoso (Archives of Microbiology, 2010)

Changes in non-core regions stabilise plastocyanin from the thermophilic cyanobacterium Phormidium laminosum - Francisco J. Muñoz-López; Simone Raugei; Miguel A. De la Rosa; Antonio J. Díaz-Quintana; Paolo Carloni (JBIC Journal of Biological Inorganic Chemistry, 2010)

Synthesis, molecular docking and biological evaluation as HDAC inhibitors of cyclopeptide mimetics by a tandem three-component reaction and intramolecular [3+2] cycloaddition - Tracey Pirali; Valeria Faccio; Riccardo Mossetti; Ambra A. Grolla; Simone Di Micco; Giuseppe Bifulco; Armando A. Genazzani; Gian Cesare Tron (Molecular Diversity, 2010)

Erratum to: Involvement of sensory nerves and TRPV1 receptors in the rat airway inflammatory response to two environment pollutants: diesel exhaust particles (DEP) and 1,2-naphthoquinone (1,2-NQ) - Aila Mirtes Teles; Yoshito Kumagai; Susan D. Brain; Simone A. Teixeira; Ana A. Varriano; Maria Alice A. G. Barreto; Wothan Tavares de Lima; Edson Antunes; Marcelo N. Muscará; Soraia K. P. Costa (Archives of Toxicology, 2010)

Involvement of sensory nerves and TRPV1 receptors in the rat airway inflammatory response to two environment pollutants: diesel exhaust particles (DEP) and 1,2-naphthoquinone (1,2-NQ) - Aila Mirtes Teles; Yoshito Kumagai; Susan D. Brain; Simone A. Teixeira; Ana A. Varriano; Maria Alice A. G. Barreto; Wothan Tavares de Lima; Edson Antunes; Marcelo N. Muscará; Soraia K. P. Costa (Archives of Toxicology, 2010)

Predation has a greater impact in less productive environments: variation in roe deer, Capreolus capreolus , population density across Europe - Claudia Melis; Bogumiła Jędrzejewska; Marco Apollonio; Kamil A. Bartoń; Włodzimierz Jędrzejewski; John D.C. Linnell; Ilpo Kojola; Josip Kusak; Miha Adamic; Simone Ciuti; Ivan Delehan; Ihor Dykyy; et al. (Global Ecology and Biogeography, 2009)
Aim We aimed to describe the large‐scale patterns in population density of roe deer Caprelous capreolus in Europe and to determine the factors shaping variation in their abundance. Location Europe. Methods We collated data on roe deer population density from 72 localities spanning 25° latitude and 48° longitude and analysed them in relation to a range of environmental factors: vegetation productivity (approximated by the fraction of photosynthetically active radiation) and forest cover as proxies for food supply, winter severity, summer drought and presence or absence of large predators (wolf, Canis lupus , and Eurasian lynx, Lynx lynx ), hunter harvest and a competitor (red deer, Cervus elaphus ). Results Roe deer abundance increased with the overall productivity of vegetation cover and with lower forest cover (sparser forest cover means that a higher proportion of overall plant productivity is allocated to ground vegetation and thus is available to roe deer). The effect of large predators was relatively weak in highly productive environments and in regions with mild climate, but increased markedly in regions with low vegetation productivity and harsh winters. Other potentially limiting factors (hunting, summer drought and competition with red deer) had no significant impact on roe deer abundance. Main conclusions The analyses revealed the combined effect of bottom‐up and top‐down control on roe deer: on a biogeographical scale, population abundance of roe deer has been shaped by food‐related factors and large predators, with additive effects of the two species of predators. The results have implications for management of roe deer populations in Europe. First, an increase in roe deer abundance can be expected as environmental productivity increases due to climate change. Secondly, recovery plans for large carnivores should take environmental productivity and winter severity into account when predicting their impact on prey.

Pulmonary toxicity following exposure to waterproofing grout sealer - G. Patrick Daubert; Henry A. Spiller; Barbara Insley Crouch; Steven A. Seiferta; Karen E. Simone; Susan C. Smolinske (Journal of Medical Toxicology, 2009)

Stratospheric ozone during the arctic winter: Brewer measurements in Ny-Ålesund - C. Rafanelli; S. De Simone; A. Damiani; C. Lund Myhre; K. Edvardsen; T. Svenoe; E. Benedetti (International Journal of Remote Sensing, 2009)

Karyotypic and molecular polymorphisms in Ctenomys torquatus (Rodentia: Ctenomyidae): taxonomic considerations - Fabiano A. Fernandes; Gislene L. Gonçalves; Simone S. F. Ximenes; Thales R. O. de Freitas (Genetica, 2009)

Loading PEG-Catalase into Filamentous and Spherical Polymer Nanocarriers - Eric A. Simone; Thomas D. Dziubla; Evguenia Arguiri; Vanessa Vardon; Vladimir V. Shuvaev; Melpo Christofidou-Solomidou; Vladimir R. Muzykantov (Pharmaceutical Research, 2009)

Trophic cascades initiated by fungal plant endosymbionts impair reproductive performance of parasitoids in the second generation - Simone A. Härri; Jochen Krauss; Christine B. Müller (Oecologia, 2008)

The role of density-dependent individual growth in the persistence of freshwater salmonid populations - Simone Vincenzi; Alain J. Crivelli; Dusan Jesensek; Giulio A. De Leo (Oecologia, 2008)

A New Missense Mutation Found in the FLNA Gene in a Family with Bilateral Periventricular Nodular Heterotopia (BPNH) Alters the Splicing Process - Simone S. Tsuneda; Fabio R. Torres; Maria A. Montenegro; Marilisa M. Guerreiro; Fernando Cendes; Iscia Lopes-Cendes (Journal of Molecular Neuroscience, 2008)

Water deficits accelerate ripening and induce changes in gene expression regulating flavonoid biosynthesis in grape berries - Simone D. Castellarin; Mark A. Matthews; Gabriele Di Gaspero; Gregory A. Gambetta (Planta, 2007)

Endocrine responsiveness to social challenges in northern and southern hemisphere populations of Zonotrichia - John C. Wingfield; Simone L. Meddle; Ignacio Moore; Shallin Busch; Douglas Wacker; Sharon Lynn; Aaron Clark; Rodrigo A. Vasquez; Elizabeth Addis (Journal of Ornithology, 2007)

[3H]Adenine is a suitable radioligand for the labeling of G protein-coupled adenine receptors but shows high affinity to bacterial contaminations in buffer solutions - Anke C. Schiedel; Heiko Meyer; Bernt B. A. Alsdorf; Simone Gorzalka; Hannelore Brüssel; Christa E. Müller (Purinergic Signalling, 2007)

Gene expression profiling reveals two separate mechanisms regulating apoptosis in rectal carcinomas in vivo - Elza C. de Bruin; Simone van de Pas; Cornelis J. H. van de Velde; J. Han J. M. van Krieken; Lucy T. C. Peltenburg; Corrie A. M. Marijnen; Jan Paul Medema (Apoptosis, 2007)

Density-dependent individual growth of marble trout (Salmo marmoratus) in the Soca and Idrijca river basins, Slovenia - Simone Vincenzi; Alain J. Crivellì; Dusan Jesensek; Jean-Francois Rubin; Giulio A. De Leo (Hydrobiologia, 2007)

Identification and characterization of proteases from skin mucus of tambacu, a Neotropical hybrid fish - C. M. C. Salles; P. Gagliano; S. A. T. Leitão; J. B. Salles; H. L. M. Guedes; V. P. F. Cassano; S. Giovanni De-Simone (Fish Physiology and Biochemistry, 2007)

Optimizing interpolation of shoot density data from a Posidonia oceanica seagrass bed - Michele Scardi; Lorenzo A. Chessa; Eugenio Fresi; Antonio Pais; Simone Serra (Marine Ecology, 2006)
A case study on the optimization of Posidonia oceanica density interpolation, using a data set from a large meadow at Porto Conte Bay (NW Sardinia, Italy), is presented. Ordinary point kriging, cokriging and a weighted average based on inverse square distance were used to interpolate density data measured in 36 sampling stations. The results obtained from different methods were then compared by means of a leave‐one‐out cross‐validation procedure. The scale at which interpolation was carried out was defined on the basis of the Hausdorff dimension of the variogram. Optimizing spatial scale and data points search strategy allowed obtaining more accurate density estimates independently of the interpolation method.

Microgravity effects on leaf morphology, cell structure, carbon metabolism and mRNA expression of dwarf wheat - G. W. Stutte; O. Monje; R. D. Hatfield; A. -L. Paul; R. J. Ferl; C. G. Simone (Planta, 2006)

HMG-CoA reductase and PPARα are involved in clofibrate-induced apoptosis in human keratinocytes - G. Muzio; G. Martinasso; A. Trombetta; D. Di Simone; R. A. Canuto; M. Maggiora (Apoptosis, 2006)

Osteopontin expression in coculture of differentiating rat fetal skeletal fibroblasts and myoblasts - Renata O. Pereira; Simone N. Carvalho; Ana Carolina Stumbo; Carlos A. B. Rodrigues; Luis Critóvão Porto; Anibal S. Moura; Laís Carvalho (In Vitro Cellular & Developmental Biology - Animal, 2006)

OSTEOPONTIN EXPRESSION IN COCULTURE OF DIFFERENTIATING RAT FETAL SKELETAL FIBROBLASTS AND MYOBLASTS - RENATA O. PEREIRA; SIMONE N. CARVALHO; ANA CAROLINA STUMBO; CARLOS A. B. RODRIGUES; LUIS CRITÓVÃO PORTO; ANIBAL S. MOURA; LAÍS CARVALHO (In Vitro Cellular & Developmental Biology - Animal, 2006)

Sustained attention in traumatic brain injury (tbi) and healthy controls: enhanced sensitivity with dual-task load - Paul M. Dockree; Mark A. Bellgrove; Fiadhnait M. O’Keeffe; Pauline Moloney; Lina Aimola; Simone Carton; Ian H. Robertson (Experimental Brain Research, 2006)

Antidepressants differentially affect expression of complexin I and II RNA in rat hippocampus - Mathias Zink; Simone Rapp; Peter J. Gebicke-Haerter; Fritz A. Henn; Johannes Thome (Psychopharmacology, 2005)

Paleolimnological investigations of anthropogenic environmental change in Lake Tanganyika: II. Geochronologies and mass sedimentation rates based on 14C and 210Pb data - Brent A. McKee; Andrew S. Cohen; David L. Dettman; Manuel R. Palacios-Fest; Simone R. Alin; Gerard Ntungumburanye (Journal of Paleolimnology, 2005)

Neotropical wetlands: New instruments in ecosystem management - Steven A. Loiselle; Simone Bastianoni; Luca Bracchini; Claudio Rossi (Wetlands Ecology and Management, 2004)

Wolbachia pipientis in Australian Spiders - Simone M. Rowley; Robert J. Raven; Elizabeth A. McGraw (Current Microbiology, 2004)

Distribution of Benthic Communities on the Tropical Rocky Subtidal of Armação dos Búzios, Southeastern Brazil - Simone Siag Oigman‐Pszczol; Marcia A. de O. Figueiredo; Joel C. Creed (Marine Ecology, 2004)
Few studies have described the spatial patterns of rocky sublittoral benthic communities in Brazil, where these habitats are almost exclusively located on the southeast and south coastline. The fauna and flora were analyzed using a quadrat method, and the species abundance and distribution were determined along transects down to the bottom sand plain on 10 rocky shores at Armação dos Búzios, Brazil. The 16 most common species accounted for around 97% of the benthos coverage and included cnidarians, algae, poriferans, and echinoderms. Cnidarians and algae were the most important groups, with abundance ranging from 13–66% and 27–68%, respectively. The species distribution indicated a clear depth zonation pattern. The algal community dominated the shallowest depths in sites more exposed to waves and steeper substrate slope, whereas the cnidarian community, divided into the zoanthidean Palythoa caribaeorum and the coral Siderastrea stellata , was more abundant from intermediate to greater (4 m) depths. Different community patterns were found between sites, demonstrating that different spatially discrete factors may be acting on each rocky shore.

The quantitative relationship between structure and polarized spectroscopy in the FMO complex of Prosthecochloris aestuarii: refining experiments and simulations - Markus Wendling; Milosz A. Przyjalgowski; Demet Gülen; Simone I. E. Vulto; Thijs J. Aartsma; Rienk van Grondelle; Herbert van Amerongen (Photosynthesis Research, 2002)

Increased dopamine D 2 receptor binding after long-term treatment with antipsychotics in humans: a clinical PET study - Simone Silvestri; Mary V. Seeman; Juan-Carlos Negrete; Sylvain Houle; C.M. Shammi; Garry J. Remington; Shitij Kapur; Robert B. Zipursky; Alan A. Wilson; Bruce K. Christensen; Philip Seeman (Psychopharmacology, 2000)

Organization of the human synphilin-1 gene, a candidate for Parkinson's disease - Simone Engelender; Tracy Wanner; John J. Kleiderlein; Koichi Wakabayashi; Shoji Tsuji; Hitoshi Takahashi; Roxann Ashworth; Russell L. Margolis; Christopher A. Ross (Mammalian Genome, 2000)

Two modes of sulfite oxidation in the extremely thermophilic and acidophilic archaeon Acidianus ambivalens - Peter Zimmermann; Simone Laska; A. Kletzin (Archives of Microbiology, 1999)

Genotypic and phenotypic characterization of six new recombinant congenic strains derived from NOD/Shi and CBA/J genomes - Peter C. Reifsnyder; Jeffry C. Flynn; Amanda L. Gavin; Eric A. Simone; John J. Sharp; Lieselotte Herberg; Edward H. Leiter (Mammalian Genome, 1999)

Sex Hormones Differentially Regulate Isoforms of UDP-Glucuronosyltransferase - Simone I. Strasser; Sheree A. Smid; Maurice L. Mashford; Paul V. Desmond (Pharmaceutical Research, 1997)

Flavodoxin from Wolinella succinogenes - Simone Biel; Oliver Klimmek; Roland Groß; A. Kröger (Archives of Microbiology, 1996)

False-negative results in examining foods for staphylococcal thermonuclease - Simone A. Bouwer-Hertzberger; Helga M. Sohl-Vos; D. A. A. Mossel; H. Mol (Antonie van Leeuwenhoek, 1981)